Optimization and Evaluation of Aceclofenac Loaded Solid Lipid Nanoparticles via Response Surface Methodology - Khadija Saleem; Nariman Shahid; Badarqa Tul Ayesha; Alia Erum; Amna Wajdan; Kashif Barkat; Ume Ruqia Tulain; Muhammad Umer Ashraf; Sana Hanif (Journal of Pharmaceutical Innovation, 2027)

Prediction of the sustainable concrete strength using machine Learning-based boosting and expression techniques - Muhammad Waqas Ashraf; Adnan Khan; Yongming Tu; Tongfang Wang; Chao Wang (European Journal of Environmental and Civil Engineering, 2026)

Accuracy in prediction of reinforcement corrosion initiation: effects of time, chloride binding, and multidirectional exposures on concrete diffusivity - Shamsad Ahmad; Muhammad Umar Khan; Ashraf A. Bahraq; Mohammed A. Al-Osta; Amin Al-Fakih (European Journal of Environmental and Civil Engineering, 2026)

Solid Waste Management Optimization Techniques: A Systematic Review - Imman Khalid; Imran Shafi; Jamil Ahmad; Tahir Khurshaid; Muhammad Shafiq; Imran Ashraf (International Journal of Environmental Research, 2026)

Curcumin: Bioavailability and therapeutic potential in metabolic disorders and chronic diseases - Humaira Ashraf; Iahtisham-Ul-Haq; Seydi Yıkmış; Gholamreza Abdi; Rana Muhammad Aadil (Food and Humanity, 2026)

Neuroprotective effect of Continentalic acid by targeting NF-κB/Bcl-2 and oxidative stress signaling in traumatic brain injury in male BALB/c mice - Sana Zafar; Maryam Jamil; Muhammad Ibrar Khan; Ashraf Ullah Khan; Kifayat Ullah Shah; Eun Kyoung Seo; Salman Khan (Molecular Biology Reports, 2026)

Core genome analysis reveals novel drug and vaccine targets in multidrug-resistant Citrobacter koseri - Zubda Ashraf; Fizza Arshad; Samina N. Shakeel; Faiz Ur Rahman; Khaled Fahmi Fawy; Sarah A. Altwaim; Saeed M. Alasmari; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2026)

Integrative QSAR-GaMD Approach Identifies Stable Repurposed Inhibitors Targeting Dengue Virus Proteins - Amna Shafqat; Muhammad Shahab; Alia Ashraf; Zakirullah; Rashid Ahmad; Shan Xu; Guojun zheng; Yigang Tong (Journal of Pharmaceutical Innovation, 2026)

Molecular epidemiology and resistance modulation of Streptococcus spp. in subclinical goat mastitis in Pakistan - Ashraf Ali; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Hamza Rasheed; Maria Batool; Kehkshan Shahid; Gulbaz Anwar; Mahpara Safdar (Small Ruminant Research, 2026)

Precision nanoparticles for plant thermotolerance: From molecular mechanisms to scalable agriculture - Muhammad Azeem Ashraf; Muhammad Ateeq; Muhammad Amjad; Qingfeng Dong; Hao Ren; Asad Shehzaib; Wang Xue; Liang Chen; Yin-Gang Hu (Plant Science, 2026)

Chitinase-primed ultrasound enhances Saccharomyces cerevisiae cell-wall deconstruction and yeast-protein remodelling in two complementary model systems - Talha Riaz; Xianjiang Ye; Te Yu; Zhijun Xia; Muhammad Moeid Khan; Xuan Yao; Rabiya Riaz; Sadia Ansar; Zhou Chen; Muhammad Atiq Ashraf; Chuanyan Pan; Yongguo Jin; et al. (Food Research International, 2026)

Plastic fragments impair soil organic carbon persistence through reshaping microbial metabolism and decreasing plant carbon supply in dryland ecosystems - Meng-Ying Li; Wei Wang; Yudi M. Lozano; Jia-Yao Yang; Yue Ma; Xiao-Bin Xiong; Shuang-Jin Huang; Muhammad Ashraf; Jian-Ming Li; Yun-Li Xiao; Zheng-Guo Cheng; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Microbial diversity enhancement in a bio-electro-fenton system driven by sediment microbial fuel cells for photocatalytic PAHs degradation in antibiotics applicate soil-water systems - Muhammad Usman; Zenhua Zhao; Muhammad Adnan; Muhammad Ibrahim; Olive Mekontchou Yemele; Ghulam Abbas Ashraf; Mukhtorjon Karimov; Alisher Abduvokhidov; Naoufel Ben Hamadi (Journal of Environmental Chemical Engineering, 2026)

Decoupling methanogenesis to boost hydrogen production via microalgae–wastewater co-digestion in a continuous stirred reactor - Muhammad Asad Javed; Ashraf Aly Hassan (Fuel, 2026)

Fabrication of polymeric bigels with locust bean gum and clove essential oil using tri-frequency ultrasonication to enhance the dispersion and gel properties for functional applications - Muhammad Awais; Jawad Ashraf; Muhammad Safiullah Virk; Sanabil Yaqoob; Qiufang Liang; Yufan Sun; Aysha Imtiaz; Mingming Zhong; Wenjing Zhu; Haile Ma; Xiaofeng Ren (Food Hydrocolloids, 2026)

Reusing end-of-life reverse osmosis membranes: Strategies, challenges, and future perspectives - Zeeshan Arshad; Muhammad Ashraf; Taha Demraoui; Tauqir Ahmad; Muhammad Bilal Asif; Niaz Ali Khan; Mukarram Zubair; Muhammad Irshad Baig; Nisar Ullah; Yasir Abbas; Almotasembellah Abushaban; Nadeem Baig (Desalination, 2026)

Synthesis and application of NiFe2O4/Nb2C-MXene composites for enhanced microbial fuel cell performance in wastewater treatment: Advancing sustainable bioelectricity generation - Muhammad Waseem Mumtaz; Haseeb Ashraf; Hamid Mukhtar; Memona Sadiqa; Uroosa Saeed; Waheed Miran; Tahir Iqbal; Aashir Waleed; Umer Rashid (Biomass and Bioenergy, 2026)

Molecular insights, resistance profiling, and in silico structural modeling of extended-spectrum beta-lactamase-producing E. coli in camels - Mahpara Safdar; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Kehkshan Shahid; Maria Batool; Gulbaz Anwar; Hamza Rasheed; Ashraf Ali (Veterinary Research Communications, 2026)

Development and Characterization of Proliposomes for Sustained Oral Delivery of the DPP-4 Inhibitor Vildagliptin - Shazia Ashraf; Asadullah Madni; Faizan Akram; Muhammad Farhan Hanif; Afifa Shafiq; Iqra Fatima Ayub (Journal of Pharmaceutical Innovation, 2026)

Interfacial Stabilization and Geochemical Transformation of Antimony in Contaminated Soil Using a Ferrihydrite-Functionalized Biochar–Montmorillonite Composite - Rabia Safeer; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muhammad Irtaza Sajjad Haider; Samra Ijaz; Ruijia Liu (International Journal of Environmental Research, 2026)

Effectiveness of machine learning and deep learning techniques for multi-horizon weather forecasting - Abdullah Sami; Muhammad Bilal; Usman Habib; Adeel Ashraf Cheema (Meteorology and Atmospheric Physics, 2026)

A small-scale experimental prototype for exhaust heat-based mechanical energy harvesting in passenger vehicles, with extrapolation to heavy vehicles - Muhammad Bader Munir; Muhammad Waheed Ashraf; Najam ul Qadir; Sibghat Ullah; Allah Ditta (Next Research, 2026)

Gastrodia elata Blume (Tianma) extract mitigates simulated microgravity–induced oxidative stress and enhance learning and memory in Caenorhabditis elegans - Muhammad Zulqarnain Shakir; Inam Ullah; Muhammad Wasim Usmani; Jiang Ning; Jixian Liu; Xuchen Zhou; Yufen Zhao; Guanghua Lu; Qiaobei Du; Huabiao Chen; Muhammad Imran; Muhammad Ashraf; et al. (Life Sciences in Space Research, 2026)

Integration of petrophysical and rock physics analysis to reservoir characterization in the Scarborough Field, Northwest Shelf, Australia - Ahmed Bakry; Qamar Yasin; Ashraf Ghoneimi; Muhammad Nabih (Journal of African Earth Sciences, 2026)

Retraction notice to ‘The combined supplementation of melatonin and salicylic acid effectively detoxifies arsenic toxicity by modulating phytochelatins and nitrogen metabolism in pepper plants’ [Environ. Pollut. 297, (2022) 118727] - Cengiz Kaya; Ali Sarıoglu; Muhammad Ashraf; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Environmental Pollution, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Bimetallic ferro and lanthanum impregnated on nano HZSM-5 catalysts for the Reutealis trisperma oil hydroprocessing to rich aromatic jet fuel range - Muhammad Al Muttaqii; Abdul Aziz; Sugeng Priyanto; Indri Yati; Muh. Nur Khoiru Wihadi; Amalia Kurnia Amin; Kiky Corneliasari Sembiring; Hendris Hendarsyah Kurniawan; Sudibyo; Didik Prasetyoko; Reva Edra Nugraha; Lenny Marlinda; et al. (Bioresource Technology Reports, 2026)

Robust prediction of advanced reservoir petrophysical parameters using conventional logs: Insights from XGB and neural network models - Ahmed Bakry; Ashraf Ghoneimi; Muhammad Nabih; Qamar Yasin; Mohamed Abd Elaziz; Ahmed Elgazar (Marine Geophysical Research, 2026)

Editorial Expression of Concern: Taurine decreases arsenic and microplastic toxicity in broccoli (Brassica oleracea L.) through functional and microstructural alterations - Shahar Yar; Muhammad Arslan Ashraf; Rizwan Rasheed; Umer Farooq; Arslan Hafeez; Shafaqat Ali; Mudassar Shahid; Pallab K. Sarker (BioMetals, 2026)

Structural and physiological adaptations conferring herbivory resistance in wild olive (Olea europaea L. subsp. cuspidata) - Faakeha Islam; Syed Mohsan Raza Shah; Farooq Ahmad; Mansoor Hameed; Sana Basharat; Sana Fatima; Ansar Mehmood; Zahida Parveen; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Khawaja Shafique Ahmad (Physiology and Molecular Biology of Plants, 2026)

Vitamin B12 and pregabalin combination restored brain waves dynamics and behavior in chronic unpredictable mild stress (CUMS) model of depression - Zain Raza; Muhammad Hussain Ali; Zohabia Rehman; Waseem Ashraf; Fakhir Hannan; Imran Imran; Faleh Alqahtani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retraction notice to “Machine learning based prediction and experimental validation of arsenite and arsenate sorption on biochars” [Sci. Total Environ. 904 (2023) 166678] - Wei Zhang; Waqar Muhammad Ashraf; Sachini Supunsala Senadheera; Daniel S. Alessi; Filip M.G. Tack; Yong Sik Ok (Science of The Total Environment, 2026)

Evaluation of anti-diabetic potential of Fagonia indica leaf, seed, and flower extracts via phytochemical profiling, In Vitro, In Silico, and In Vivo approaches - Muhammad Azmat; Muhammad Yasin Ashraf; Naila Ali; Imran Zafar; Ahsanullah Unar; Mohamed Mohany (Phytochemistry Letters, 2026)

Redox homeostasis and trace metal regulation drive allantoin-induced tolerance against combined microplastic and cadmium stress in pea (Pisum sativum L.) - Anshra Murtaza; Muhammad Munir; Rizwan Rasheed; Muhammad Arslan Ashraf; Fakhar Abbas; Sarah Owdah Alomrani; Abdulrahman Alasmari; Shafaqat Ali; Sajjad Hassan Askari (Journal of Trace Elements in Medicine and Biology, 2026)

An efficient peroxymonosulfate activation by Nb2CTx-MXene mediated with CQDs composite catalyst for carbamazepine degradation: Kinetics and mechanistic insights - Muhammad Adnan; Zhenhua Zhao; Liling Xia; Ghulam Abbas Ashraf; Arslan Tauqeer; Muhammad Usman; Saqib Bashir; Thamer Alomayri; Akmal Abilkasimov (Journal of Environmental Sciences, 2026)

Integrated molecular sensory profiling reveals the distinct aroma signatures of peach fruit types - Wei Zhu; Xiaolin Chen; Zhimeng Gan; Kaijie Zhu; Huaping He; Muhammad Atiq Ashraf; Furong Wang; Yuan Liu; Xizhou Hu; Yang Zhang; Juan Xu; Xiaoyan Ai (Food Research International, 2026)

Mapping the spatial heterogeneity of nitrogen species in road dust through integrated multi-source remote sensing and interpretable machine learning - Muhammad Nabil Ashraf; Suiliang Huang; Asad Basheer (Environmental Research, 2026)

Comparative experimental study on tower base load characteristics of a parked large-scale wind turbine under tornadoes and straight-line winds - Shiqin Zeng; Haiquan Jing; Xuhui He; Ashraf A. El Damatty; Baole Li; Dongqin Zhang; Muhammad Naeem (Engineering Structures, 2026)

Integrated molecular-to-process modelling of electrochemical furfural hydrogenation for sustainable biomass valorization - Muhammad Ashraf Sabri; Seba AlAreeqi; Daniel Bahamon; Lourdes F. Vega (Chemical Engineering Journal, 2026)

Utilizing Gamma Radiation for Sustainable Potato Farming: A Study to Enhance Potato Yield and Growth Parameters - Kalsoom Asghar Ali; Muhammad Junaid; Ashraf Ahmed Qurtam; Fahd A. Nasr; Zia-Ul-Haq (Potato Research, 2026)

Machine learning and response surface modeling for predicting strength loss of alkali-activated materials exposed to aggressive environment - Munir Iqbal; Sohaib Nazar; Muhammad Hasham Kashif; Muhammad Ashraf; Haji Sami Ullah (Innovative Infrastructure Solutions, 2026)

Sustainable approaches to alleviate salinity stress in two fenugreek cultivars through moringa leaf extract and salicylic acid - Sumreen Anjum; Iqra Tabassam; Mubeen Sarwar; Tanveer Hussain; Shoaib ur Rehman; Sumaira Maqsood; M. Irfan Ashraf; Muhammad Ashfaq; Qurban Ali (Plant Biosystems, 2026)

Impacts of microplastics on soil quality and productivity: Analysing shape- and dose-dependent responses - Peng-Yang Wang; Xiao-Bin Xiong; Jia-Cheng Guo; Hong-Yan Tao; Wen-Ying Wang; Muhammad Ashraf; Sheng-Jun Ji; Ze-Ying Zhao; Chang-Lang Yang; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2026)

Nickel and Cobalt Accumulation and Human Health Risk in Guava (Psidium guajava L.) Under Wastewater Irrigation: A Soil–Plant Transfer Assessment - Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Sana Anwar; Shahzad Akhtar; Ijaz Rasool Noorka; Muhammad Irfan Ashraf; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2026)

Development of an In Vitro Permeation Test Framework For Naloxone Hydrochloride Intranasal Spray: Establishing IVIVR for Bioequivalence Assessment - Tasmin Ara Sultana; Manar Al-Ghabeish; Steven Chopski; Ross Walenga; Diaa Shakleya; Bryan Newman; Muhammad Ashraf; Ahmed Zidan (Pharmaceutical Research, 2026)

Rutin as a multi-target anti-inflammatory phytochemical in arthritic disorders: pharmacological mechanisms and therapeutic potential - Muhammad Muzammil Nazir; Asma Ashraf (Inflammopharmacology, 2026)

Helenalin: a multifaceted sesquiterpene lactone with diverse biological activities—an integrative pharmacological and computational evidence - Iqra Farzeen; Zunaira Jaan; Maryam Batool; Muhammad Muzammil Nazir; Derya Karatas Yeni; Muhammad Umar Ijaz; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Unraveling Luteolin’s Modulatory Effects on α-Synuclein Aggregation: A Combined Biophysical, Computational, and C. elegans Approach - Syed Moasfar Ali; Md Nadir Hassan; Nida Zaidi; Muhammad Uzair Ashraf; Mahmood Akbar; Aamir Nazir; Rizwan Hasan Khan (Cell Biochemistry and Biophysics, 2026)

Jasmonic Acid and Abiotic Stress Tolerance: From Metabolic Flux to Hormone-Network Decision Making - Nazma Khan; Burhan Khalid; Muhammad Atiq Ashraf; Umair Khan; Rizwan Maqbool (Journal of Plant Growth Regulation, 2026)

Faster-developing buffalo embryos produced in vitro demonstrate higher quality, enhanced pregnancy rates, and distinct transcriptome profile - Muhammad Waqas; Qaisar Shahzad; Armughan Ahmad Wadood; Talha Ashraf; Ali Husnain; Muhammad Khurram Shahzad; Huiyan Xu; Liping Pu; Yangqing Lu (Theriogenology, 2026)

Bismuth nanostructures: catalytic pathways to sustainable technologies - Muhammad Khan; Mohamed Hassan Eisa; Xiaohui Sun; Muffarih Shah; Suleiman M. Suleiman; Abdul Hameed; Ilyas Khan; Xiangsheng Chen; Nasir A. Ibrahim; Ashraf A. Qurtam; Zainuriah Hassan; Katabathini Narasimharao; et al. (Fuel, 2026)

Tailoring strontium-nickel supported reduced graphene oxide nanostructure for synergistic catalytic hydrogen generation from sodium borohydride and photodegradation of organic pollutant - Rana Nauman Hassan; Faryal Ali; Shoaib Akhtar; Abu Bakar Siddique; Khaled Fahmy Fawy; Muhammad Sher; Muhammad Ashraf Shaheen; Muhammad Fayyaz ur Rehman; Umar Nishan; Tauqeer Ahmad; Arshad Ali; Azhar Abbas (Fuel, 2026)

Microbial consortia and bioinoculant strategies for enhancing crop salt tolerance and restoring fertility in salt-degraded soils - Cengiz Kaya; Muhammad Ashraf; Sergey Shabala (Plant and Soil, 2026)
Background Soil salinity is a major constraint to global agriculture, impairing ionic balance, nutrient acquisition, and water relations. This imposes significant economic penalties and threatens the sustainability of agricultural production systems. Aims This review synthesizes advances across multiple microbial groups, including plant growth-promoting rhizobacteria (PGPR), endophytes, extremophiles, arbuscular mycorrhizal fungi (AMF), cyanobacteria, and microalgae, to evaluate their role in rehabilitating salt-affected soils and strengthening crop resilience. Methods We analyzed recent evidence on the functional diversity of plant-associated microorganisms, focusing on the comparative efficacy of single versus multi-strain and cross-kingdom consortia. The review further examines case studies on synergistic approaches (e.g., AMF–cyanobacteria, microalgae–bacteria) and translational innovations such as nanocarrier encapsulation and AI-guided selection. Results Evidence indicates that microbial consortia outperform single inoculants by stabilizing rhizosphere microbiomes, enhancing nutrient cycling, and coordinating stress signaling. Specifically, synergistic applications reinforce redox regulation, ionic homeostasis, and pathogen defense under saline conditions. Furthermore, emerging bioformulation technologies and AI tools are shown to accelerate the effective application of these solutions in saline–alkali soils. Conclusions Integrating ecological mechanisms with biotechnological advances provides a roadmap for microbiome-informed precision agriculture. This review emphasizes that low-input and environmentally restorative strategies are essential for developing resilient cropping systems under increasing salinity pressures.

Genomic characterization of an isolate of tomato leaf curl New Delhi virus associated with tomato crops - Abdul Majid; Muhammad Taimoor Shakeel; Muhammad Naveed Aslam; Ambreen Maqsood; Muhammad Raheel; Waqas Ashraf; Tahir Farooq; Atta ur Rehman Khan; Mahmoud Ahmed Amer; Mohammed Ali Al-Saleh (European Journal of Plant Pathology, 2026)

Palmitic acid in cancer research: mechanistic insights from in vitro and in vivo studies - Muhammad Muzammil Nazir; Sehrish Muzaffar; Saima Muzammil; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Immunopharmacological and structural design of a polyprotein based multi epitope vaccine against Powassan virus - Aasia Kalsoom; Syed Hussain Abidi; Sohail Ameer Marwat; Ghulam Shabbir; Muhammad Naveed; Aiman Muhammad Ashraf Mughal; Muhammad Nouman Majeed; Shereen Magdy Korany; Basma Magdy Korany; Khaled Alzhrani; Tariq Aziz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effect of split applications of silicon nanoparticles and conventional sources of Si on growth, antioxidant enzymes, and cadmium uptake in wheat under Cd stress - Muhammad Aamer Maqsood; Nimra Ashraf; Muhammad Zia-ur-Rehman; Muhammad Usman; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Refaat A. Abohassan (South African Journal of Botany, 2026)

Unraveling the endocrine disruption potential of microplastics in testosterone regulation - Muhammad Babar Khawar; Ali Afzal; Kashifa Jalil; Tayyba Jan; Zaira Ahmad; Amna Rehman; Hanan Afzal; Sadia Ahmad; Afzal Nimra; Muhammad Ahsan Ashraf (Journal of Environmental Sciences, 2026)

Modelling methane production in trickle bed reactors: A biokinetic approach - Ahmed Taha; Muhammad Tahir Ashraf; Emil de Bekker Steffensen; Lars Yde; Jorge Rodríguez (Bioresource Technology, 2026)

Temporal and spatial variations in anaerobic microbiomes from different inoculum sources for carbon monoxide conversion in thermophilic trickle bed reactor - Rowayda Ali; Muhammad Tahir Ashraf; Lars Yde (Bioresource Technology Reports, 2026)

Bridging Lab to Land: Field Validation of Acinetobacter schindleri SR-5–1 for Nutrient Acquisition and Oxidative Stress Mitigation in Wastewater-Irrigated Pea (Pisum sativum L.) Plants - Sherjeel Hashmat; Muhammad Arslan Ashraf; Muhammad Tariq Javed; Umer Farooq; Mobeen Umer (Water, Air, & Soil Pollution, 2026)

A Critical Review on Advance Molecular Distortion Techniques for Textile Wastewater Treatment in Pakistan - Sahrish Ashraf; Muhammad Sultan; Muhammad Wakil Shahzad; Muhammad Imran; Rana M. A. Kanwar; Muhammad Nauman Ashraf; Zahid Mahmood Khan; Zubair Khaliq; Muhammad Bilal Qadir (Water, Air, & Soil Pollution, 2026)

Desert treasures: a comprehensive review of the diversity, phytochemistry, ethnobotany, and conservation of thar desert flora - Ummar Iqbal; Hafiza Zahra Naseem; Hadia Jabeen; Muhammad Faraz Gul; Saba Gul; Nargis Naz; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf (The Science of Nature, 2026)

Natural flavonoid isoorientin and its anticancer mechanisms: a systematic review - Muhammad Muzammil Nazir; Iqra Farzeen; Maryam Batool; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Immunopharmacological effects of shikonin in experimental rheumatoid arthritis: a systematic review and meta-analysis of in vivo studies - Muhammad Muzammil Nazir; Saima Muzammil; Muhammad Mujammil Nazir; Sara Nazir; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Silver-decorated ZnO nanorods for sunlight-assisted photocatalytic degradation of ciprofloxacin, methyl orange, and 2,4-dinitrophenol in water - Iqra Mazhar; Muhammad Afzaal; Muhammad Altaf; Manzar Sohail; Raja Shahid Ashraf; Abdul-Sattar Nizami (Nanotechnology for Environmental Engineering, 2026)

A charge conservative finite volume discretization of the Hodgkin-Huxley model - Muhammad Zeeshan Ashraf; Tanel Peets; Kert Tamm (Journal of Computational Neuroscience, 2026)

Understanding goat production systems in diverse agro-ecological zones under subtropical climate: a farmer-centered survey approach - Amjad Atta; Muhammad Irfan-ur-Rehman Khan; Abdul Rehman; Kamran Ashraf (International Journal of Biometeorology, 2026)

Anti-inflammatory role of metal and metal oxide nanoparticles: a review of toxicity, green synthesis, and immunomodulatory mechanisms - Rimsha Ashraf; Shaukat Ali; Muhammad Summer; Saima Riaz; Amina Iqbal; Ramzana Bibi; Haiqa Shabbir (Inflammopharmacology, 2026)

Phylogenetic and genome-wide analysis of codon usage reveals geographic and host-specific adaptation in Vaccinia virus - Hafsa Iqbal; Faisal Ahmad; Sajjad Ahmad; Iftikhar Ahmad; Muhammad Yar Sobhan Qadir; Ali Khalid; Zurva Ashraf; Zohra Ahmad; Ferjeni Zouidi (Archives of Virology, 2026)

Role of rituximab in treatment of patients with primary central nervous system lymphoma: An updated systematic review and meta-analysis - Kumail Mustafa Ali; Muhammad Farhan Ashraf; Zain Ul Abideen; Armish Rehman; Rumman Javed; Ayena Ghulam Mujtaba; Touba Diwan; Ukasha Khalid; Laiba Ikram (Acta Neurologica Belgica, 2026)

Cortinarius squamibrunneus sp. nov. ( Basidiomycota ; Agaricales ) in C . Section Safranopedes of Subgenus Telamonia from Swat District, Khyber Pakhtunkhwa, Pakistan - Hira Ijaz; Tasneem Ashraf; Muhammad Naveed; Gul Sanga; Sadiq Ullah; Sana Jabeen (New Zealand Journal of Botany, 2026)
Cortinarius squamibrunneus sp. nov. was collected from Swat District, Khyber Pakhtunkhwa, Pakistan. The species is distinguished from its closely related species, C . epipurrus , by its pale orangish‐brown to brown, fibrillose–squamulose pileus with a darker central disc and a rimose to radially cracked margin, smaller basidiospores (5.5–7.4 × 3.6–5 μm) with finely ornamented warts and variably shaped sterile cells. Comparative morphological analyses combined with molecular phylogenetic inference based on the ITS region of nrDNA confirm that this taxon is distinct from previously described species and represents a new species within C. sect. Safranopedes of C . subg. Telamonia .

Sustainable Laccase Production by Anoxybacteroides rupiense UE27 Using Desmostachya bipinnata Biomass: Optimisation and Application in Textile Effluent Treatment - Haniah Saeed; Bushra Rehman; Uroosa Ejaz; Maria Muhammad Ashraf; Amal Siraj; Areesha Mustafa; Muhammad Sohail (Environmental Microbiology, 2026)
Laccase has been widely reported for the detoxification of industrial effluents, yet large‐scale applications require cost‐effective production. This study utilised an innovative approach by employing biomass from the halophyte Desmostachya bipinnata, which has not been previously reported for microbial enzyme production. A newly discovered bacterial species, Anoxybacteroides rupiense, was used for laccase production. Initially, the factors impacting laccase production by the thermophilic strain of A. rupiense UE27 (Genome Project JBHLFH010000000.1) were screened for their significant effects using the Plackett–Burman design. Consequently, Response Surface methodology was adopted to optimise the significant factors, resulting in a maximum laccase yield of 51.69 U L −1 at pH 6.39 and in presence of 0.59 mM CuSO 4 , representing a 4.29‐fold increase compared to the unoptimised conditions. AFM revealed comminution in the plant biomass and FTIR analysis confirmed laccase‐mediated lignin degradation in D. bipinnata biomass, evidenced by shifts in aromatic CC (1597–1650 cm −1 ), CH methyl (2850–2918 cm −1 ) and phenolic OH (3300–3400 cm −1 ) regions. Moreover, growth of A. rupiense UE27 in the presence of textile effluent resulted in 70.6% decolourisation with the subsequent laccase production. Hence, this study presents a sustainable and innovative approach for developing wild biomass‐based processes for the cost‐effective production of laccase by thermophilic bacteria.

Mitigating salinity stress in wheat: employing biochemical parameters and stress tolerance index with foliar application of potassium and salicylic acid - Ilker Ugulu; Zafar Iqbal Khan; Farzana Shaheen; Muhammad Yasin Ashraf; Kafeel Ahmad; Muhammad Nadeem; Asma Ashfaq (Vegetos, 2026)

Structure-based virtual screening, molecular dynamics and MM-PBSA/GBSA analysis for the identification of novel CDK6 inhibitors against prostate cancer - Manzoor Ahmad; Muhammad Ajmal Khan; Ashraf Ullah Khan; Sadia Butt; Yahya Khan; Amir Zeb; Nadia Bibi; Aishma Khattak; Hina Ahsan; Ajaz Ahmad; Amin Ullah (In Silico Pharmacology, 2026)

From roadside soil to cow milk: a potentially toxic metal transfer study using Pennisetum glaucum as fodder - Zafar Iqbal Khan; Natasha Ameer; Asma Ashfaq; Kafeel Ahmad; Muhammad Irfan Ashraf; Ijaz Rasool Noorka; Aima Iram Batool; Ilker Ugulu (Environmental Monitoring and Assessment, 2026)

Processing sequence as a design lever: pectin pre-complexation enhances ultrasound-driven interfacial loading, functionality, and volatile profile of yeast protein - Talha Riaz; Yuan Ma; Zhijun Xia; Muhammad Moeid Khan; Xianjiang Ye; Muhammad Atiq Ashraf; Rabiya Riaz; Xing Fu; Yongguo Jin (Food Research International, 2026)

Antibiotic resistance pattern and molecular study of foodborne pathogenic bacteria isolated from Poultry meat in Bangladesh - Shahin Mahmud; Muhammad Wasim; Md. Firoz Ali; Md. Omar Faruque; Sourav Sarker; Md. Rayhan Ali; Ashraf Hossain Talukder; A.K.M. Mohiuddin; Somaresh Kumar Mondal; Shah Adil Ishtiyaq Ahmad (Food and Humanity, 2026)

Electrospinning of food-grade polysaccharides and proteins: Materials, challenges, and applications - Khubaib Ali; Nadia Niaz; Faizan Ul Haq; Muhammad Waseem; Waqas Ashraf; Chen Guoxun; Mangang Wu (Carbohydrate Polymers, 2026)

A comprehensive review on thermo-responsive targeted and functional therapy for management of rheumatoid arthritis - Huma Hameed; Syed Sharf ud Din; Muhammad Zaman; Muhammad Ahsan Waqar; Kainat Fatima; Abdullah Ashraf; Huzaifa Malik; Ahmad Salawi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Optimum N Fertilization Enhances Salinity Tolerance and N use Efficiency in Maize through Modulation of Antioxidant Defense and Biochemical Pathways - Syed Ayyaz Javed; Muhammad Tauseef Jaffar; Muhammad Ashraf; Muhammad Ahmed; Ali Raza Siddiqui; Hafiz Muhammad Bilal; Jawad Amin; Sanaullah Sattar (Journal of Plant Growth Regulation, 2026)

Dichlorvos toxicity on hemato-biochemical, histopathological, and behavioral parameters in the grass carp (Ctenopharyngodon idella) - Mehvish Saleem; Cristiana Roberta Multisanti; Sana Ullah; Wardah Fazal; Muhammad Sohail; Muhammad Bilal; Muhammad Kashif Ashraf; Caterina Faggio (Ecotoxicology, 2026)

The biological synthesis of iron oxide nanomaterials and their possible physiological and biochemical toxicities in Cyprinus carpio - Nadia Bibi; Nishita Narwal; Muhammad Anees; Huma Ayub; Mian Adnan Kakakhel; Tawaf Ali Shah; Ashraf Khalifa; Imran Ibrahim Shaikh (Ecotoxicology, 2026)

Validating the Efficiency of the AquaCrop Model Under Full and Deficit Irrigation Regimes to Simulate Future Climate Impacts on Wheat Crop - Shamim Ara Memon; Irfan Ahmed Shaikh; Mashooque Ali Talpur; Abdul Rahim Junejo; Munir Ahmed Mangrio; Nazar Gul; Zaheer Ahmed Khan; Hafiz Abdul Salam; Muhammad Ashraf (Irrigation and Drainage, 2026)
Wheat yield and water demand are affected by the ongoing disturbance of climatic factors and greenhouse gases (GHG). As a result, the AquaCrop model's ability to anticipate climate change impacts on wheat harvests under full and deficit irrigation regimes in Sindh, Pakistan, was evaluated using wheat trials conducted between 2018 and 2020. However, for its validation, the results of the deficit irrigation treatment ITS 50 (50% controlled irrigation at the tillering stage) for both seasons were employed. The model efficiently estimated yield with a normalised root‐mean‐square error (NRMSE) of 13% and 17%, a Willmott's d ‐index of 98% and a Nash–Sutcliffe efficiency (NME) of 95% under full and deficit irrigation treatments, respectively. The simulation results revealed an adverse effect of climate change on the yield and water productivity of wheat. Over the century, the model predicted an increase of 6% to 7% in wheat yield under full (well‐watered) irrigation and a decrease of 10 to 12% in 25% reduced water applied depth (RAD) and 21% to 24% under 50% RAD scenarios for both representative concentration pathway RCPs (4.5 and 8.5). The overall wheat water productivity increased under a well‐watered irrigation regime by 16% in RCP8.5 compared with RCP4.5.

Nanoplastics in soil and aquatic ecosystems: Sources, impacts, and nature-based remediation strategies - Cengiz Kaya; Muhammad Ashraf; Binoy Sarkar; Nanthi Bolan; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2026)

Mxene-chitosan composites in wastewater treatment: From adsorption and separation to catalytic remediation - Muhammad Khan; Mohamed Hassan Eisa; Abdul Hameed; Xiaohui Sun; Suleiman M. Suleiman; Muffarih Shah; Noor Majeed; Xiangsheng Chen; Nasir A. Ibrahim; Ashraf A. Qurtam; Katabathini Narasimharao; Zainuriah Hassan (Carbohydrate Polymers, 2026)

Comparative insights into molecular characterization and resistance profiling of methicillin-resistant Staphylococcus aureus across dairy livestock in Pakistan - Muhammad Ijaz; Maria Batool; Muhammad Umar Javed; Hamza Rasheed; Arslan Ahmed; Ali Abdullah Jabir; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2026)

Evaluation of immunogenicity and protective efficacy of Salmonella Gallinarum knockout purB mutant strain in chicken - Muhammad Umer Farooq; Masham Mukhtar; Muhammad Suleman; Minahil Ashraf; Muhammad Abu Bakr Shabbir; Muhammad Hassan Mushtaq; Umar Bin Zahoor; Shakil Abbas; Aamir Ghafoor (Veterinary Research Communications, 2026)

Zinc oxide nano-priming fortifies Triticum aestivum L. against salt stress through physio-morphological, biochemical and transcriptomic responses - Muhammad Ateeq; Muhammad Azeem Ashraf; Qingfeng Dong; Hao Ren; Tauqeer Ahmad Yasir; Linzhou Huang; Liang Chen; Yin-Gang Hu (Plant and Soil, 2026)

Ferruginol as multifunctional abietane diterpenoid-comprehensive pharmacological evaluation and computational drug discovery insight - Iqra Farzeen; Maryam Batool; Zunaira Jaan; Saira Saeed; Muhammad Muzammil Nazir; Shahla Faisal; Asma Ashraf (Phytochemistry Reviews, 2026)

Legume-based diversified cropping systems increase soil organic carbon labile pools and microbial carbon use efficiency in a 12-year long-term field trial - Muhammad Nadeem Ashraf; Zawar Haider; Muhammad Ahmed Waqas; Zia Ur Rahman Farooqi; Muhammad Sanaullah; Daniel Blackburn; Zhifeng Yan; Munazza Yousra; Ansa Rebi; Allah Nawaz (Journal of Soils and Sediments, 2026)

Anti-arthritic and anti-inflammatory potential of newly synthesized 2,3-disubsituted thiazolidine-4-one derivatives in CFA-induced arthritis model by targeting TLR4/NF-κB and MAPK signaling - Muhammad Ibrar Khan; Sana Zafar; Muzaffar Abbas; Ashraf Ullah Khan; Kifayat Ullah Shah; Salman Khan (Inflammopharmacology, 2026)

Metabolic reprogramming of neurons in alzheimer disease: a biochemical perspective - Iqra Farzeen; Maryam Batool; Saira Saeed; Ghanva Mustafa; Munaza Yasmeen; Muhammad Muzammil Nazir; Asma Ashraf (Metabolic Brain Disease, 2026)

Green photocatalytic degradation of methylene green dye using oxalic acid and its metal complexes: Mechanistic and predictive insights from ANN, RSM, and DFT studies - Mohammad Tauseef Haider; Rizwan Ashraf; Talib H. Mawat; Faisal Jamil; Adnan Majeed; Anam Shahzadi; Faisal Qaleel; Haris Nadeem; Sabha Khalid; Asma Rehman; Sadia Aziz; Maryam Khalid; et al. (Journal of Water Process Engineering, 2026)

Corrigendum to “Mitigating salt toxicity and overcoming phosphate deficiency alone and in combination in pepper (Capsicum annuum L.) plants through supplementation of hydrogen sulfide” [J. Environ. Manag. 351, (2024), 119759] - Cengiz Kaya; Ferhat Uğurlar; Muhammad Ashraf; Mohammed Nasser Alyemeni; Raf Dewil; Parvaiz Ahmad (Journal of Environmental Management, 2026)

Advancing seismic facies analysis and reservoir characterization: A synthetic data-augmented CNN and transfer learning workflow integrated with real seismic data - Muhammad Ali; Ning Wei; He Changxingyue; Keyao Lin; Wendong Wang; Muhsan Ehsan; Ren Jiang; Wakeel Hussain; Umar Ashraf (Gas Science and Engineering, 2026)

Deep eutectic solvent: a promising way to enhance the physicomechanical and antimicrobial properties of pullulan/carboxymethyl chitosan films impregnated with zein–nisin nanofillers for sustainable food packaging - Jawad Ashraf; Jiyao Zhang; Tabussam Tufail; Muhammad Awais; Shuyi liu; Yajing Qi; Zahoor Ahmed; Liming Yue; Zhou Sumei; Bin Xu (Food Hydrocolloids, 2026)

pH-responsive pea protein-sodium alginate hydrogel beads for freshness monitoring in protein drinks: Structural and molecular insight - Khubaib Ali; Nadia Niaz; Fedrick C. Mgomi; Faizan Ul Haq; Waqas Ashraf; Muhammad Umair Khalid; Qingling Wang; Mangang Wu (Food Hydrocolloids, 2026)

Transient mixed convection in coaxial pipes with temperature-dependent variable density - Bakhtawar Bibi; Ali B.M. Ali; Muhammad Ashraf; Ghulam Rasool; Muhammad Usman Rashid; Abduvali Sottarov (Dynamics of Atmospheres and Oceans, 2026)

Climate-driven Modifications in Structural and Functional Traits of Couch Grass [Cynodon Dactylon (L.) Pers.] along Elevation Gradient - Sana Fatima; Farooq Ahmad; Zahida Parveen; Sana Basharat; Mansoor Hameed; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Syed Mohsan Raza Shah; Raza Shah; Muhammad Ashraf; Muhammad Kaleem; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Gypsum and Manure Impacts on Contrasting Textured Saline-Sodic Soils and Greenhouse Gas Emissions - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Muhammad Sabir; Aftab Jamal; Ayesha Abdul Qadir; Bryan G. Hopkins; Muhammad Nadeem Ashraf (Journal of Soil Science and Plant Nutrition, 2026)

Integrated plant-soil-microbiome responses mediate greenhouse gas emissions in the restoration of a semiarid steppe - Zhen Wang; Xiaojiang Yang; Paul C. Struik; Muhammad Nadeem Ashraf; Carmeron N. Carlyle; Scott X. Chang; Yuanheng Li; Wenbo Zhang; Riliga Wu; Baoming Ji; Ke Jin (Applied Soil Ecology, 2026)

Trait dynamics of endemic Festuca species reveal cold-resilience across elevation gradient - Khawaja Shafique Ahmad; Syed Mohsan Raza Shah; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Ummar Iqbal; Ansar Mehmood; Sana Fatima; Wisal Muhammad Khan; Muhammad Ashraf; Hazem M. Kalaji; Manzer H. Siddiqui (Acta Physiologiae Plantarum, 2026)

Heavy-metal pollution in the Jhelum River (Pakistan) alters hematological and biochemical biomarkers and drives tissue bioaccumulation in Wallago attu - Muhammad Bilal; Sana Ullah; Muhammad Kashif Ashraf; Caterina Faggio; Cristiana Roberta Multisanti (Biological Trace Element Research, 2026)

Simultaneous quantification of hydroxycinnamate derivatives and antioxidant activity of Ziziphus oxyphylla Edgew. leaf methanolic extract - Surriya Naheed; Muhammad Wajid; Afsheen Ehsan; Khalid Hussain; Gulzar Muhammad; Naureen Shehzadi; Muhammad Tanveer Khan; Imran Ahmad; Adnan Ashraf (Natural Product Research, 2026)

Ligand modelling of Trachyspermum ammi phytocompounds for Aeromonas hydrophila cell wall synthesis enzyme in Labeo rohita - Muhammad Burhan Sabir; Aqeela Ashraf; Rashid Saif; Malaika Saeed; Muhammad Osama Zafar (Natural Product Research, 2026)

In Vitro Permeation Testing of Sunscreens using Reconstructed Human Skin versus Human Cadaver Skin Models - Kartik R. Roy; Apipa Wanasathop; Lijing Xu; Jiang Wang; Sergio G. Coelho; Steven A. Adah; Theresa M. Michele; Patrick J. Faustino; Muhammad Ashraf; Xiaoming Xu; Yang Yang (AAPS PharmSciTech, 2026)

Wastewater based microbial fuel cells (MFCs) for electric power harnessing: A review - L. Syam Sundar; Syed M. Hasnain; Muhammad Waqar Ashraf (Next Research, 2026)

Enhancing transgender mobility on public transport through equitable transport policies in a culturally conservative society - Nazam Ali; Muhammad Ashraf Javid; Ryan Cheuk Pong Wong; Muhammad Abdullah; Syed Sift-E-Hassan; Punyaanek Srisurin; Qudeer Hussain (Journal of Transport Geography, 2026)

Tracing nutrient pollution pathways from road dust to water bodies in South Tianjin using remote sensing and machine learning - Muhammad Nabil Ashraf; Suiliang Huang; Deze Liu (Journal of Hazardous Materials, 2026)

Investigation of photocatalytic efficiency and antimicrobial activity via Mn doped SnO2 using an eco-friendly green synthesis method - Laraib Bibi; Tahir Iqbal; Mariam Seemab; Sumera Afsheen; I.M. Ashraf; Faiza Saeed; Atif Mossad Ali; Muhammad Yousaf; M.A. Sayed (Journal of Environmental Chemical Engineering, 2026)

Enhanced charge carrier separation in greenly synthesized ZnO-NiO NCs-based Z-scheme heterojunction for photodegradation of ciprofloxacin hydrochloride and hydrogen evolution reaction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Shoaib Akhtar; Muhammad Shahzad; Akbar Ali; Nadeem Ahmad; Hatem A. Abuelizz; Rashad Al-Salahi (Fuel, 2026)

Root microstructural traits regulate ion homeostasis in bush morning glory (Ipomoea carnea Jacq.) for invasiveness success in saline environments - Syed Mohsan Raza Shah; Naila Hadayat; Jazab Shafqat; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Maham Zia; Zaheer Abbas; Zahida Parveen; Muhammad Ashraf; Ummar Iqbal; Ansa Asghar; et al. (The Science of Nature, 2026)

Lipid Nanoparticle Development in Practice: Challenges and Collective Insights - Xiuling Lu; Sheyda Ranjbar; Fan Zhang; Yahya Choonara; Ryan M. Pearson; John Fetse; Rui He; Esraa Mohamed; Amalendu Ranjan; Muhammad Delwar Hussain; Ashraf Hatim Osman Mohamed Kheir; Chun-Wan Yen; et al. (Pharmaceutical Research, 2026)

Precision Rewiring of Stress-Responsive Gene Networks Via CRISPR: Mechanistic Pathways Toward Climate-Smart Agriculture - Burhan Khalid; Muhammad Umer Javed; Muhammad Ikram; Muhammad Ateeq; Muhammad Atiq Ashraf; Talha Riaz; Shumaila Nawaz; Rizwan Maqbool (Journal of Crop Health, 2026)

Anti-arthritic effect of Helicteres isora L. ethanolic extract via modulation of cytokines and oxidative stress in CFA-induced arthritic rats - Muhammad Muzammil Nazir; Azhar Rafique; Salma Sultana; Asma Ashraf (Inflammopharmacology, 2026)

Drimiopsis maculata methanol extract attenuates inflammation in experimental rat model of polyarthritis: a biochemical and molecular insight - Malik Saadullah; Farwa Tahir; Maryam Farrukh; Samina Afzal; Rabia Munir; Usman Ashraf; Uzma Saleem; Muhammad Ajmal Shah; Ibrahim Aljaezi; Ana Sanchez Silva; Norah K. Algarzae; Musaad Bedah Alsahly (Inflammopharmacology, 2026)

Unraveling the Genetic Diversity of Lernaea Parasites Infecting Carp Through 18 S rRNA Gene Analysis - Farzana Abbas; Muhammad Hafeez-ur-Rehman; Farzana Ashraf (Acta Parasitologica, 2026)

Photoperiod and temperature: Key abiotic drivers of horticultural crop physiology in a changing climate - Muhammad Atiq Ashraf; Shumaila Nawaz; Uzma Bilal; Maria Abubakar; Shumaila Anam; Muhammad Azam; Burhan Khalid; Abdullah; Muhammad Asim; Rabbya Rayan Shah; Muhammad Ateeq (Biologia, 2026)

Magnoflorine and its structural diversity: mechanisms, and drug discovery opportunities a review - Muhammad Muzammil Nazir; Ghanva Mustafa; Saira Saeed; Warisha Ghaffar; Iqra Farzeen; Aamir Masood; Asma Ashraf (Molecular Diversity, 2026)

Enhancing resilience and sustainability: an inductive approach to innovations in cruise industry - Muhammad Hasan Ashraf; Naima Saeed; Kevin Cullinane; Martin Dresner (Transportation Research Part D: Transport and Environment, 2026)

Corrigendum to “Zein nanoparticles in emerging food packaging: Mechanistic insights into self-assembly, structural driving forces, and functional applications” [Trends in Food Science & Technology 167 (2026) 105447] - Jawad Ashraf; Jiyao Zhang; Tabussam Tufail; Muhammad SafiUllah Virk; Ma Yuling; Muhammad Awais; Zahoor Ahmed; Zhou Sumei; Bin Xu (Trends in Food Science & Technology, 2026)

Zein nanoparticles in emerging food packaging: Mechanistic insights into self-assembly, structural driving forces, and functional applications - Jawad Ashraf; Jiyao Zhang; Tabussam Tufail; Muhammad SafiUllah Virk; Ma Yuling; Muhammad Awais; Zahoor Ahmed; Zhou Sumei; Bin Xu (Trends in Food Science & Technology, 2026)

Short dry period improves postpartum energy balance and reproduction but reduces milk yield in dairy cows - Melad Ahmed; Amjad Riaz; Nasim Ahmad; Muhammad Naveed ul Haque; Hifz ul Rahman; Muhammad Yaseen; Talha Ashraf; Muhammad Abdullah; Ali Hassan; Ali Husnain (Theriogenology, 2026)

Synergistic effects of biochar and silicon dioxide nanoparticles abate cadmium uptake and oxidative stress in tomato: Achieving crop resilience and environmental sustainability - Muhammad Kashif Irshad; Muhammad Waseem; Saba Saleem; Jamilur R. Ansari; Sana Ashraf; Wasim Javed; Ali Noman; Muhammad Aqeel; Muhammad Rizwan; Afrah E. Mohammed; Modhi O. Alotaibi; Muhammad Rizwan; et al. (Plant Science, 2026)

Natural resource wealth and corporate innovation: Governance, managerial discipline, and environmental management implications - Ahmad Ghazali; Muhammad Ashraf; Muhammad Saeed Meo; Khayrilla Kurbonov (Journal of Environmental Management, 2026)

From rock waste to reactive surfaces: Natural gabbro rocks for solar remediation of gaseous and aqueous contaminants - Gregor Žerjav; Muhammad Ashraf Sabri; Samar Al Jitan; Riccardo Tribuzio; Hebah Jarusheh; Albin Pintar; Khalid Al-Ali; Andrea Ceriani; Alessandro Decarlis; Giovanni Palmisano (Journal of Environmental Management, 2026)

Ambroxol’s Role in PTZ-Induced Anxiety-Like Conditions in Mice: Targeting Neuroinflammation and Oxidative Stress via In Vivo and In Silico Approaches - Hafeeza Zafar Ali; Sarwat Jahan; Laila Ilahi; Sami Siraj; Muhammad Zakria; Najeeb Ullah; Muhammad Ikram; Ashraf Ullah Khan; Manzoor Khan; Fawad Ali Shah; Hafsah Muhammad (Molecular Neurobiology, 2026)

Seed Priming with Osmolytes Ameliorates Salinity Tolerance in Maize (Zea mays L.) Through Embryonic Modifications - Paris Riaz; Ansa Asghar; Sana Fatima; Sana Basharat; Zahida Parveen; Mansoor Hameed; Farooq Ahmad; M. Sajid Aqeel Ahmad; Muhammad Ashraf; Faakeha Islam; Syed Mohsan Raza Shah; Qasim Ali (Journal of Plant Growth Regulation, 2026)

Mitigating cadmium-stressed spinach by the synergistic effect of vermicompost and selenium: associated heath risks assessment - Taiba Rauf; Kamran Ashraf; Zeeshan Ahmed; Rabiya Nasir; Muhammad Zeeshan Mansha; Qamar uz Zaman; Ghulam Murtaza; M. Ajmal Ali; Mohamed S. Elshikh; Rashid Iqbal; Lala Gurbanova; Nazim S. Gruda (Environmental Geochemistry and Health, 2026)

Bentonite clay in aflatoxin mitigation: advances, efficiency and perspectives - Syed Ali Raza Naqvi; Muhammad Kaleem Khan Khosa; Ameer Fawad Zahoor; Matloob Ahmad; Ariba Abdullah; Muhammad Ramzan Saeed Ashraf Janjua; Syed Ansar Abidi; Fatma Mohamed Ameen Khalil; Mohamed Fawzy Ramadan; João Miguel Rocha (Archives of Microbiology, 2026)

First-principles study on structural, elastic, acoustic and optoelectronic properties of hexagonal magnesium oxide (MgO) - Maryam Tariq; Tariq Mahmood; Robina Ashraf; Imran Aslam; Muhammad Rizwan; Arbab Arif; Ch. Omer Javed; Afshan Urooj (Next Research, 2025)

Electrochemical CO2 reduction: Converting greenhouse gas into high-value products for a sustainable future - Muhammad Wasim Afzal; Muhammad Imran Kanjal; RuiFeng Ren; Shazia Ashraf; Syed Rizwan Shafqat; Jiang Shao; Lutong Wang; Ma Jingye; Xue Liu; Yan Bai; Dongbin Dang (Journal of Environmental Chemical Engineering, 2025)

A novel hybrid MOF–metal oxide electrochemical sensor for ultra-trace detection of cadmium ions - Sabah Haider; Mujahid Mustaqeem; Maria Zaib; Mohammed Ashraf Gondal; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa (Journal of Environmental Chemical Engineering, 2025)

Ecological resilience of Gallon's curse (Cenchrus biflorus Roxb.) in hyperarid and hypersaline environments - Sana Basharat; Farooq Ahmad; Mansoor Hameed; Zahida Parveen; Muhammad Sajid Aqeel Ahmad; Muhammad Waseem; Ansa Asghar; Sana Fatima; Liu Pingwu; Mehwish Noor; Syed Mohsan Raza Shah; Muhammad Ashraf (Journal of Arid Environments, 2025)

Biochar Amendment Improved Growth and Yield of Fragrant Rice and Reduced Arsenic (As) Accumulation under As-contaminated Irrigation Water - Umair Ashraf; Talat Mansha; Shakeel Ahmad Anjum; James DeDecker; Abrar Hussain; Fahd Rasul; Muhmmad Abrar; Muhammad Ishfaq (Water, Air, & Soil Pollution, 2025)

Correction: Citrulline enhances salinity tolerance via photosynthesis, redox balance, osmotic and hormonal regulation, and nutrient assimilation in sunflower (Helianthus annuus L.) - Umer Farooq; Muhammad Arslan Ashraf; Rizwan Rasheed (Physiology and Molecular Biology of Plants, 2025)

Modulating depression through the gut–brain axis: the role of gut microbiota in therapeutic interventions - Muhammad Muzammil Nazir; Warisha Ghaffar; Ghanva Mustafa; Saira Saeed; Muhammad Umar Ijaz; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Assessing hazardous flash flood susceptibility using multivariate zonation mapping techniques in Pishin District, Balochistan province of Pakistan - Muhammad Ashraf; Qahir Shah; Adnan Arshad; Ghulam Murtaza (Natural Hazards, 2025)

Dynamics of urinary tract infections: a comprehensive study on antimicrobial susceptibility, virulence profiling and molecular epidemiology of uropathogenic Escherichia coli from Pakistan - Zia Ashraf; Muhammad Hidayat Rasool; Bilal Aslam; Hasan Ejaz; Fatima Mujahid; Mohsin Khurshid (Molecular Biology Reports, 2025)

Beyond traditional diagnosis: aptamer-based microRNA detection for the early diagnosis of periodontitis - Muhammad Usman Ashraf; Khairul Mohd Fadzli Mustaffa; Nurul Wahida Mohd Hasan; Maaz Anwer Memon; Danial Qasim Butt; Rizwan Mahmood; Wan Nazatul Shima Shahidan (Molecular Biology Reports, 2025)

Exome sequencing in a Pakistani male infertility cohort: perspective on molecular diagnosis, genetic heterogeneity, and diagnostic yield - Dapeng Zhou; Ambrin Fatima; Afrasiab Ahmed; Tehseen Ullah Khan Afridi; Haq Nawaz Khan; Mussarat Ashraf; Muhammad Naeem; Syed Babar Jamal; Ishtiaq Hassan; Erica E. Davis; Feng Zhang; Rehana Rehman; et al. (Molecular Genetics and Genomics, 2025)

Sofosbuvir containing ph-responsive hydrogel microparticulate system: design, characterization, and biocompatibility assessment - Muhammad Aun; Muhammad Umar Ashraf; Salim Albukhaty; Umaira Rehman; Asif Mahmood; Asma Razzaq; Hira Ijaz; Rai Muhammad Sarfraz; Mohamed M. Salem; Areej Alsubaie; Mounir M. Bekhit (Journal of Pharmaceutical Innovation, 2025)

Regulation of Physiological Attributes in Wheat Crops Under Terminal Drought Stress: A Review - Mohammad Hossein Izadi; Muhammad Ashraf; Yahya Emam (International Journal of Plant Production, 2025)

Nutlet micromorphology and systematic implications of genus Nepeta (Lamiaceae): correct taxonomic tool for taxa identifications - Shaista Jabeen; Mushtaq Ahmad; Muhammad Zafar; Shabir Ahmad; Hussain Shah; Ateef Ullah; Syed Waseem Gillani; Muhammad Manzoor; Ashraf M. M. Abdelbacki; Ali M. Sayed (Genetic Resources and Crop Evolution, 2025)

Arsenic Accumulation in Soil, Forage, and Milk Samples from Rainfed and Groundwater Irrigated Areas in Chakwal, Pakistan - Zafar Iqbal Khan; Asma Ashfaq; Sidra Khan; Kafeel Ahmad; Ijaz Rasool Noorka; Allah Bakhsh Gulshan; Shehnaz Fatima; Saqib Bashir; Saif Ullah; Muhammad Irfan Ashraf; Ilker Ugulu; Abdullah H. Alshahri (Bulletin of Environmental Contamination and Toxicology, 2025)

Effect of citrulline seed priming on growth, photosynthesis, redox equilibrium, secondary metabolic enzymes, metal sequestration and nutrient acquisition in sunflower (Helianthus annuus L.) under chromium toxicity - Umer Farooq; Muhammad Arslan Ashraf; Muhammad Iqbal; Rizwan Rasheed (BioMetals, 2025)

Impact of Silicon Application on the Mineral Nutrient Profile and Fruit Quality of Mandarin Citrus Hybrid ‘Kinnow’ - Hafiz Faiq Bakhat; Muhammad Imran Razzaq; Muhammad Shafique Khalid; Sunaina Abbas; Natasha; Masood Iqbal Awan; Hasnain Anwar; Ghulam Mustafa Shah; Saira Afzal; Muhammad Rizwan Ashraf; Hafiz Mohkum Hammad (Applied Fruit Science, 2025)

Enhancing Rice Water Productivity: Insights From Crop Water Needs and Irrigation in Pakistan - Ghani Akbar; Noman Latif Sadozai; Muhammad Ashraf (Irrigation and Drainage, 2025)
Excessive irrigation significantly reduces rice ( Oryza sativa L.) water productivity in Pakistan. This study evaluated crop water requirements, irrigation trends and water productivity across Pakistan's rice‐growing regions. Field data on crop yield, soil characteristics, irrigation practices and 10 years of weather data were collected from 11 districts across four provinces. The FAO AquaCrop model was used to assess crop water requirements (evapotranspiration, ET), the root zone water balance and water productivity. The crop water requirements ranged from 787 to 1151 mm, while irrigation consistently exceeded these needs by 95% to 123%. The irrigation water productivity (WPi) ranged from 0.09 to 0.19 kg/m 3 , and the evapotranspiration (ET) water productivity (WPet) ranged from 0.20 to 0.41 kg/m 3 . Excessive irrigation, 2 to 3 times the actual crop water needs, is attributed to traditional practices, a lack of knowledge and suboptimal irrigation schedules. Optimizing irrigation scheduling, adopting advanced technologies, and using high‐yielding, drought‐tolerant rice varieties could reduce water losses and improve crop yields. These findings offer actionable strategies to increase water productivity and ensure food security in Pakistan's rice‐growing regions, with potential applications in other water‐scarce, rice‐producing countries facing similar challenges.

Loliolide: green monoterpenoid lactone with therapeutic and ecological significance-a comprehensive review with computational validation - Iqra Farzeen; Saima Zafar; Nimrah Zafar; Sehrish Fatima; Muhammad Muzammil Nazir; Asma Ashraf (Molecular Diversity, 2025)

From 2-D seismic refraction to 3-D subsurface characterization: Unpacking the role of univariate spatial interpolation techniques with borehole validation - Nirandoal Cheng; Mohd Ashraf Mohamad Ismail; Nordiana Mohd Muztaza; Fatin Nadhirah Ahmad Pauzi; Muhammad Taqiuddin Zakaria; Yasuhiro Yokota (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Synergistic PMS activation by SnBi@ZrC under visible light for enhanced organic pollutant removal - Rana Mohsin Ali; Jie Wang; Tianhong Zhou; Yue Tian; Muhammad Usman; Hamza Khaliq; Muhammad Adnan; Zunaira Nasir; Ghulam Abbas Ashraf; Yusuke Yamauchi (Journal of Water Process Engineering, 2025)

High-performance clay and K2CO3-Modified sludge biochar for efficient reactive black-5 Removal: Mechanistic insights and alleviation of phytotoxicity - Muhammad Arif; Guijian Liu; Muhammad Zia-ur-Rehman; Qumber Abbas; Aniqa Ashraf; Muhammad Saqib Rashid; Krzysztof Pikon; Balal Yousaf (Biomass and Bioenergy, 2025)

Ultraviolet processing for mycotoxin mitigation: A sustainable approach to enhancing food safety and security - Abuzar; Hafiz Rizwan Sharif; Rizwan Arshad; Mian Kamran Sharif; Waqas Ashraf; Iahtisham Ul-Haq; Zafarullah Muhammad; Mohamed A. Fahmy; Sameh A. Korma; João M. Rocha (Toxicon, 2025)

Functionalized biochar with enhanced interfacial properties for synergistic adsorption and photodegradation mechanisms of levofloxacin in industrial effluents - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Ruijia Liu (Process Safety and Environmental Protection, 2025)

Bimetallic metal-organic frameworks as versatile electrocatalysts for water splitting in neutral and alkaline environments - Syed Arfan Haider; Tehseen Mushtaq; Bakhtawar Sajjad; Munazza Shahid; Muhammad Altaf; Ayman Nafady; Ghayoor Abbas Chotana; Manzar Sohail; Shahid Rasul; Raja Shahid Ashraf (Fuel, 2025)

Multi-biomarker assessment of essential and toxic elements accumulation in Labeo gonius from Khushab Lake (Pakistan) - Muhammad Kashif Ashraf; Sana Ullah; Muhamamd Bilal; Cristiana Roberta Multisanti; Caterina Faggio (Environmental Toxicology and Pharmacology, 2025)

Fluorine segment integrated copolymer electrolyte for enhanced electrochemical stability in high-voltage lithium metal batteries - Asif Javid; Tapabrata Dam; Muhammad Abaid Ashraf; Seung-Ju Baek; Chan-Jin Park (Chemical Engineering Journal, 2025)

Electro-microbial destruction of ‘forever chemicals’: Recent advances and imminent challenges - Muhammad Hassan; Miao Lv; Jedsada Chuiprasert; Zhiqi Zou; Ibrahim Abusallout; Sikai Chen; Hugo Olvera-Vargas; Ghulam Abbas Ashraf; Hisham S.M. Abd-Rabboh; Suwanna Kitpati Boontanon (Chemical Engineering Journal, 2025)

Isorhapontigenin: exploring a promising resveratrol analog for disease management through diverse signaling pathways—a review with computational insights - Muhammad Muzammil Nazir; Ghanva Mustafa; Saira Saeed; Warisha Ghaffar; Muhammad Umar Ijaz; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Heat stress in riverine buffaloes: regulatory mechanism, physiological changes, production and reproductive performance, and mitigation strategies - Faiz-ul Hassan; Nouman Ashraf; Muhammad Asif Arain; Muhammad Mushahid; Muhammad Safdar; Muhammad Saif-ur-Rehman; Atique Ahmed Behan (International Journal of Biometeorology, 2025)

Evaluating the preclinical efficacy of naringenin in rheumatoid arthritis: a meta-analysis of in vivo studies - Muhammad Muzammil Nazir; Ayesha Batool; Muhammad Asad Sajid; Asma Ashraf (Inflammopharmacology, 2025)

Lead toxicity to earthworms (Eisenia fetida) and their accumulation mechanisms in soil - Maodong Qi; Wenzhi Lei; Jingran Sun; Yaohui Mu; Pingping Wang; Suilong Ai; Muhammad Ashraf; Lixin Zhang (Environmental Geochemistry and Health, 2025)

Amino acid-modified nano-magnetite boosts okra [Abelmoschus esculentus (L.) Moench] yield and iron enrichment for improved nutrition - Maham Ishfaq; Fahad Shafiq; Sumera Anwar; Muhammad Iqbal; Syed Hammad Raza; Arslan Mahmood; Muhammad Ashraf (BioMetals, 2025)

Quantitative Analysis of Pesticide Residues in Guava (Psidium guajava L.) Fruit by Using High Performance Liquid Chromatography - Rashad Qadri; Abdul Haseeb Ahmed; Muhammad Umair Ashraf; Muhammad Tahir Akram; Khalid Hussain; Muhammad Azam; Muhammad Imran Khan; Muhammad Mumtaz Khan (Applied Fruit Science, 2025)

Larvicidal Effects of Nanoliposomes Containing p-Cresol and Myristica fragrans Houtt. Essential Oil Against Aedes aegypti and Aedes albopictus Mosquitoes - Aamir Ali; Hafiz Muhammad Tahir; Muniba Tariq; Hooria Ashraf Khan; Ayesha Muzamil; Kiran Zainab; Asjid Ghaffar (Neotropical Entomology, 2025)

Evaluation of altered biochemical and physiological responses and expression of defense-related genes in wheat following the application of plant growth regulators under drought stress - Husnain Jawad; Muhammad Bilawal Junaid; Habib Ali; Saba Saba; Shehnaz Kousar; Muhammad Saqib; Aniqa Mubeen; Ghulam Abbas; Rafique Ahmed; Amal Mohamed AlGarawi; Ashraf Atef Hatamleh; Sadam Hussain (South African Journal of Botany, 2025)

Effects of replacement of soybean meal with fermented soybean meal on growth performance, nutrient digestibility and carcass characteristics in broiler - Ali Husnain; Urooj Anwar; Asfa Fatima; Riaz Mustafa; Umar Farooq; Waseem Abbas; Muhammad Farooq Khalid; Muhammad Ashraf; Muhammad Aziz ur Rahman (Livestock Science, 2025)

Passage performance of three small-sized fish species in a Vertical Slot Fishway with and without overhead cover - Fabio Tarena; Claudio Comoglio; Michele Spairani; Alessandro Candiotto; Muhammad Usama Ashraf; Margherita Abbà; Carlo Ruffino; Daniel Nyqvist (Ecological Engineering, 2025)

Polymeric carbon nitride-based semiconductors as a beneficial candidate in photocatalysis diversity: A comprehensive review - Sidra Tul Muntaha; Jawad Ali Shah Syed; Muhammad Mateen; Muhammad Ali Shahzad; Anand Parkash; Aqsa Asrar; Adil Emin; Ghulam Abbas Ashraf; Inaam Ullah; Muhammad Ahsan Farooq Qaisar; Salamat Ali; Ahmed Mahmoud Idris (Chemical Engineering Journal, 2025)

Citrulline Reduces Copper Toxicity in Sunflower (Helianthus annuus L.) by Modulating Photosynthesis, Osmoregulation, Redox Homeostasis, and Nutrient Relations - Arslan Hafeez; Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Novel MAX-phase Nb2AlC@Biochar: A dual-functional peroxymonosulfates activator for antibiotics and dyes degradation via Nb4+/Nb5+ redox switches; DFT insight and mechanistic elicitation - Muhammad Adnan; Zhenhua Zhao; Ghulam Abbas Ashraf; Saqib Bashir; Binglu Teng; Jureeporn Yuennan; Saqer S. Alotaibi; Muhammad Mushtaq (Journal of Water Process Engineering, 2025)

Corrigendum to “Dual-modification strategy for efficient inverted perovskite solar cells via thermally induced liquid crystals and boosting of phenethylammonium by carbazole” [Chem. Eng. J. 516 (2025) 163918] - Bilal Mehmood; Chen Zhang; Shan Wu; Jiangying Lu; Xu Zheng; Wei Jiang; Kamran Amin; Shudi Lu; Muhammad Iftikhar Khan; Muhammad Sultan; Tanveer Ashraf; Zhijie Wang; et al. (Chemical Engineering Journal, 2025)

Exploring evolutionary perspectives and antibiogram analysis of biofilm-forming Staphylococcus aureus in goat mastitis - Muhammad Umar Javed; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Ali Abdullah Jabir; Maria Batool; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2025)

Bergamottin a bioactive compound unveiled: exploring its potential in disease managments and in-silico insights - Iqra Farzeen; Muhammad Muzammil Nazir; Saima Muzammil; Saima Zafar; Derya karatas Yeni; Asma Ashraf (Phytochemistry Reviews, 2025)

Proline-Induced Changes in Cellular Redox Balance by Modulating Photosystem-II, Photosystem-I, and Activities of Antioxidants in Bread Wheat (Triticum aestivum L.) Under Salinity Stress - Ayesha Khalid; Sarah Ambreen; Aneela Kanwal Shahzadi; Nadeem Hussain; Azra Manzoor; Habib-ur-Rehman Athar; Zafar Ullah Zafar; Muhammad Ashraf (Journal of Plant Growth Regulation, 2025)

Therapeutic efficacy of celastrol in experimental polyarthritis: insights from a meta-analysis of in vivo studies - Muhammad Muzammil Nazir; Iqra Farzeen; Asma Ashraf (Inflammopharmacology, 2025)

Anti-arthritic and immunomodulatory effects of geniposide: a systematic review and meta-analysis of preclinical studies - Muhammad Muzammil Nazir; Asma Ashraf; Muhammad Mubashir Nazir; Mohammad Rameez Hashmi (Inflammopharmacology, 2025)

Effect of Aloe Vera-Based Coating on Physicochemical and Phytochemical Properties of Wild Apricot Variety - Nazish Ashraf; Imran Hayat; Nagina Rafique; Khawaja Shafique Ahmad; Muhammad Zubair Khan; Khalid J. Alzahrani; Khalaf F. Alsharif (Applied Fruit Science, 2025)

Driving innovation in fast-food industry: integrating green HRM, green empowerment, and green CSR - Jamshed Khalid; Mi Chuanmin; Muhammad Umair Ashraf; Muhammad Haroon Rasheed; Muhammad Shahid Rasheed (Environment, Development and Sustainability, 2025)

The role of market forces and regulatory factors on green innovation in China: a panel data analysis - Sumran Ali; Jawaria Ashraf; Muhammad Ghufran; Peng Xiaobao (Environment, Development and Sustainability, 2025)

Elucidating the synergistic activity of biocontrol agents in combating Xanthomonas citri pv. malvacearum and promoting of physio-chemical responses in cotton - Usman Arshad; Yaxing Feng; Muhammd Raheel; Waqas Ashraf; Muhammad Amjad Ali; Iqra Naeem; Kexin Liu (Physiological and Molecular Plant Pathology, 2025)

Stage-dependent synergistic impacts of AM fungi and rhizobacteria on phytohormone mediation and field productivity in dryland maize - Muhammad Abrar; Ying Zhu; Wen-Shan Li; Muhammad Aqeel; Umair Ashraf; Muhammad Maqsood Ur Rehman; Jian-Ming Li; Xiao-Fang Gong; Wasim Khan; Wei Wang; You-Cai Xiong (Field Crops Research, 2025)

Dual-modification strategy for efficient inverted perovskite solar cells via thermally induced liquid crystals and boosting of phenethylammonium by carbazole - Bilal Mehmood; Chen Zhang; Shan Wu; Jiangying Lu; Xu Zheng; Wei Jiang; Kamran Amin; Shudi Lu; Muhammad Iftikhar Khan; Muhammad Sultan; Tanveer Ashraf; Zhijie Wang; et al. (Chemical Engineering Journal, 2025)

Biological potential and therapeutic effectiveness with diverse signaling pathways of phyto-product chicoric acid: a comprehensive review with computational evidence - Muhammad Muzammil Nazir; Iqra Farzeen; Saima Zafar; Sehrish Fatima; Nimrah Zafar; Asma Ashraf; Sogolo Lucky Lebelo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Kaempferol as a multi-targeted phytotherapeutic for arthritis: systematic review and meta-analysis of preclinical models - Muhammad Muzammil Nazir; Iqra Farzeen; Saira Saeed; Asma Ashraf (Inflammopharmacology, 2025)

Latent class analysis of carpooling intentions considering the motives, barriers, and benefits: policy insights for behavioral change - Muhammad Ashraf Javid; Abdus Samad Farooq; Nazam Ali (Environment, Development and Sustainability, 2025)
The rapid growth in traffic on road networks demands smart and sustainable mobility patterns to reduce traffic congestion and externalities while fulfilling the travel needs of the people. Carpooling is a sustainable alternative that can shift from single occupancy to high occupancy vehicles and reduce users’ travel costs in the era of rising fuel prices. This study aims to categorize travelers into latent classes considering the carpooling barriers, motives, and benefits, and derive suitable transport policies. A questionnaire was designed and conducted online with travelers ( N = 400) in Islamabad and Rawalpindi, Pakistan. The data were analyzed using factor analysis, latent class analysis (LCA), and logistic regression analysis. The LCAs yielded three classes of carpooling barriers, i.e., barriers conscious, apathetic about barriers, and carpooling spectators; three classes of carpooling motives, i.e., non-carpoolers, apathetic carpoolers, and dedicated carpoolers; and also, three classes of carpooling benefits, i.e., non-believers of benefits, casual believers of benefits, and benefits passionate. The comparison based on average scores and ANOVA results showed significant heterogeneity in perceptions about various carpooling attributes and characteristics across three classes of barriers, motives, and benefits. The binary logistic regression showed that gender, profession, travel mode, income level, driving a car, trip distance, and cost reduction expectation are significant attributes in predicting the specific class of travelers. Travelers who are in classes of dedicated carpoolers, carpooling spectators, and ‘benefits passionate’ have a higher likelihood of carpooling. Travelers with a 6–15 km trip distance are likely to fall in the non-carpoolers class and less likely to fall in the ‘benefits passionate’ class. A 50% cost reduction with carpooling positively impacts the propensity to carpool and the belief in carpooling benefits. These findings would provide useful insight to transport planners in designing appropriate carpooling programs that focus on specific classes of travelers.

Utilizing silica-rich waste material for enhancing the properties of concrete and its environmental assessment - Mohammed Ibrahim; Muhammad Kalimur Rahman; Ashraf A. Bahraq (Environmental Science and Pollution Research, 2025)

Engineering innovative catalysts for efficient CO2 reduction toward carbon neutrality - Muhammad Awais; Naveed Ashraf; Younes Abghoui (Journal of Environmental Chemical Engineering, 2025)

Decolorization of Dye-Loaded Textile Wastewater: Elucidating the Potential of Chlorella sorokiniana Strain HIN-3 and Effect of Effluent Characteristics - Hadeeqa Arshad; Muhammad Imran; Muhammad Ashraf; Asif Naeem; Muhammad Atif Riaz (Water, Air, & Soil Pollution, 2025)

Carissa macrocarpa Extract Based Greenly Synthesized AuNPs: A Sustainable Approach for Lead Ion Detection, Azo Dye Degradation, and Antimicrobial Applications - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Mamoon Ur Rasheed; Abdul Karim; Muhammad Mustaqeem; Muhammad Fayyaz ur Rehman; Mohammad Mahtab Alam; Amirah S. Alahmari (Water, Air, & Soil Pollution, 2025)

Citrulline enhances salinity tolerance via photosynthesis, redox balance, osmotic and hormonal regulation, and nutrient assimilation in sunflower (Helianthus annuus L.) - Umer Farooq; Muhammad Arslan Ashraf; Rizwan Rasheed (Physiology and Molecular Biology of Plants, 2025)

Spectral Induced Polarization Characterization and Petrophysical Properties of Podiform Chromite Deposits and Their Host Rocks’ Electrical Response: An Experimental Study - Ashraf T. Mohamed; Rujun Chen; Muhammad Yaseen; Lanfang He; Pandurang Balwant (Natural Resources Research, 2025)

Exploring Synergistic Effects of Pantoea agglomerans BCH-1 and Bacillus pseudomycoides BCH-3 To Enhance Maize Adaptations Under Drought Condition - Anam Tariq; Mahwish Salman; Muhammad Arslan Ashraf; Shazia Anwer Bukhari; Ghulam Mustafa (Journal of Soil Science and Plant Nutrition, 2025)

Correction: Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Mechanistic Insights into Pressmud-Mediated Improvement in Wheat Growth, Quality and Productivity under Lead Contaminated Salt-Affected Soil - Basit Haider; Muhammad Imran; Muhammad Ashraf; Sajid Mahmood (Journal of Soil Science and Plant Nutrition, 2025)

Gamma-Aminobutyric Acid and Salicylic Acid Regulated Osmolyte Accumulation, Nutrient Acquisition, and ROS Metabolism to Decrease Arsenic Effects on Sunflower (Helianthus annuus L.) at Vegetative Stage - Muhammad Nawaz; Iqbal Hussain; Rizwan Rasheed; Muhammad Arslan Ashraf; Mahmood-ur-Rahman (Journal of Soil Science and Plant Nutrition, 2025)

Nitric Oxide and Hydrogen Peroxide Coordinate to Improve Photosynthesis, Oxidative Defense, Osmoregulation, and Ions Homeostasis in Pea (Pisum sativum L.) Under Drought - Muhammad Kamran Afzal; Noman Habib; Muhammad Arslan Ashraf; Qasim Ali; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)

Comprehensive Genomic, Mutation, Phylogenetic, and Statistical Analysis of the Monkeypox Virus Across Multiple Countries - Imran Zafar; Faheem kanwal; Muhammad Azmat; Ahsanullah Unar; Ijaz Ali; Waqas Yousaf; Qurat ul Ain; Mohd Ashraf Rather; Nemat Ali; Mohammad Rashid Khan; Amandeep Singh Dhanju; Rohit Sharma (Indian Journal of Microbiology, 2025)

Genome-wide identification and characterization of light-responsive FAR1 gene family in finger millet (Eleusine coracana) under abiotic stress - Urooba Abid; Azhar Iqbal; Mahnoor Mazher; Shabana Bibi; Sara Ashraf; Mohamed Kamel; Ghadeer M. Albadrani; Muath Q. Al-Ghadi; Mohamed M. Abdel-Daim; Muhammad Sajid (Genetic Resources and Crop Evolution, 2025)

Development and Optimization of Stimuli-Responsive Fenugreek/Carrageenan-Co-poly (Methacrylate) Hydrogel Matrices for Controlled Delivery of 5-Fluorouracil - Muhammad Arslan; Muhammad Umer Ashraf; Ayman M. Al-Qaaneh; Aysha Aslam; Asif Mahmood; Hira Ijaz; Rai Muhammad Sarfraz; Mohamed M. Salem; Milad A. Mezher; Mounir M. Bekhit (AAPS PharmSciTech, 2025)

The functional role of arbuscular mycorrhizal fungi in enhancing soil organic carbon stocks and stability in dryland - Meng-Ying Li; Wei Wang; Hai-Hong Yin; Yinglong Chen; Muhammad Ashraf; Hong-Yan Tao; Shi-Sheng Li; Wen-Ying Wang; Chang-Lang Yang; Yun-Li Xiao; Li Zhu; You-Cai Xiong (Soil and Tillage Research, 2025)

Energy metabolism, antioxidant defense system, metal transport, and ion homeostasis are key contributors to Cd tolerance in SSSL derived from wild rice - Humera Ashraf; Fozia Ghouri; Lixia Sun; Weiwei Xia; Sawaira Ashraf; Muhammad Zahid Ashraf; Xuelin Fu; Shafaqat Ali; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2025)

Prospecting high-altitude springs in the Upper Indus Basin, Pakistan: Knowledge towards policy development - Arshad Ashraf; Muhammad Bilal Iqbal; Ali Kamran; Naveed Mustafa (Groundwater for Sustainable Development, 2025)

Synergistic TaW-based catalysts on date seed-derived activated carbon for sustainable cleaner energy fuel production via electrochemical valorization of furfural - Muhammad Ashraf Sabri; Israa Othman; G. Bharath; Hanifa Taher Alblooshi; Mohammad Abu Haija; Ricardo P. Nogueira; Fawzi Banat (Fuel, 2025)

Advances in Physiologically Based Pharmacokinetic (PBPK) Modeling and its Regulatory Utility to Support Oral Drug Product Development and Harmonization - Yi-Hsien Cheng; Sherin Thomas; Yu Chung Tsang; Susana Almeida; Muhammad Ashraf; Nikoletta Fotaki; Tycho Heimbach; Nikunjkumar Patel; Harshil Shah; Xiaojian Jiang; Myong-Jin Kim; Rebecca Moody; et al. (Pharmaceutical Research, 2025)
This report summarizes the proceedings of Session 1 of the one-day public workshop titled “ Advances in PBPK Modeling and its Regulatory Utility for Oral Drug Product Development ” hosted by the U.S. Food and Drug Administration (FDA) and the Center for Research on Complex Generics (CRCG) on October 12, 2023. This report focuses on cutting-edge developments, ongoing challenges, and potential solutions in the field of physiologically based pharmacokinetic (PBPK) absorption modeling for systemic and gastrointestinal (GI) locally acting oral drug products, as well as exploring opportunities to enhance global harmonization for generic drug development. Despite significant advancements and several successful case studies of utilizing PBPK models in generic drug development, developing patient-centric dissolution quality standards using PBPK modeling that account for food effects or different disease states remains challenging. Combining multiple dissolution studies at different pH ranges can aid in developing patient-centric dissolution specifications. Additionally, a major challenge for GI locally acting drug products is the inability to validate the PBPK model for local bioavailability due to the lack of measured data for local drug concentration along the different sections of the GI tract. A totality of evidence-based approach, taking account of all available data in addition to PBPK modeling-based evidence, should be considered. Moving forward, it is crucial to promote global collaboration and research by sharing knowledge and experiences for utilizing PBPK models in regulatory contexts to advance both internal and international harmonization.

Exploring the potential of a pH-sensitive hydrogel sponge: interpenetrating network of tragacanth and pectin for controlled delivery of levosulpiride - Muhammad Umer Ashraf; Muhammad Awais Iqbal; Kashif Barkat; Irfan Anjum; Muhammad Naveed Mushtaq; Rabia Gul; Muhammad Aamir; Samir Ibenmoussa; Ahmad Mohammad Salamatullah; Mohammed Bourhia; Gamal A. Shazly; Gezahign Fentahun Wondmie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Quantifying LID impact: A modified metric for enhanced flood mitigation and urban resilience - Shakeel Ahmad; Haifeng Jia; Anam Ashraf; Dingkun Yin; Zhengxia Chen; Rasheed Ahmed; Muhammad Israr (Resources, Conservation and Recycling, 2025)

Improving flood hazard susceptibility assessment by integrating hydrodynamic modeling with remote sensing and ensemble machine learning - Izhar Ahmad; Rashid Farooq; Muhammad Ashraf; Muhammad Waseem; Donghui Shangguan (Natural Hazards, 2025)
Floods are natural disasters with significant economic and infrastructural impacts. Assessing flood susceptibility in mountainous urban regions is particularly challenging due to the complicated interaction in which urban structures and mountainous terrain affect flood behavior. This study employs two ensemble machine learning algorithms, Extreme Gradient Boosting (XGBoost) and Random Forest (RF), to develop flood susceptibility maps for the Hunza-Nagar region, which has been experiencing frequent flooding for the past three decades. An unsteady flow simulation is carried out in HEC-RAS utilizing a 100-year return period flood hydrograph as an input boundary condition, the output of which provided the spatial inundation extents necessary for developing the flood inventory. Ten explanatory factors, including climatic, geological, and geomorphological features namely elevation, slope, curvature, topographic wetness index (TWI), normalized difference vegetation index (NDVI), land use land cover (LULC), rainfall, lithology, distance to roads and distance to rivers are considered for the flood susceptibility mapping. For developing flood inventory, random sampling technique is adopted to create a spatial repository of flood and non-flood points, incorporating the ten geo-environmental flood conditioning factors. The models’ accuracy is assessed using the area under the curve (AUC) of receiver operating characteristics (ROC). The prediction rate AUC values are 0.912 for RF and 0.893 for XGBoost, with RF also demonstrating superior performance in accuracy, precision, recall, F1-score, and kappa evaluation metrics. Consequently, the RF model is selected to represent the flood susceptibility map for the study area. The resulting flood susceptibility maps will assist national disaster management and infrastructure development authorities in identifying high flood susceptible zones and carrying out early mitigation actions for future floods.

Nanoparticle-Mediated Phytohormone Interplay: Advancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Fozia Farhat; Saher Nawaz; Muhammad Ahmad (Journal of Crop Health, 2025)

Removal of structurally different textile dyes from water by adsorption onto biomass of non-viable Chlorella sorokiniana strain HIN-3: Kinetics and adsorption isotherms - Hadeeqa Arshad; Muhammad Imran; Muhammad Ashraf; Asif Naeem; Muhammad Atif Riaz (Journal of Applied Phycology, 2025)

Taurine decreases arsenic and microplastic toxicity in broccoli (Brassica oleracea L.) through functional and microstructural alterations - Shahar Yar; Muhammad Arslan Ashraf; Rizwan Rasheed; Umer Farooq; Arslan Hafeez; Shafaqat Ali; Mudassar Shahid; Pallab K. Sarker (BioMetals, 2025)

Immunological assessment of NSFu1: A novel fusion molecule constructed from structural proteins of SARS-CoV-2 for improving COVID-19 antibody detection - Shaista Arif; Mohsina Akhter; Aqsa Anwar; Sania Javaid; Zara Ashi; Mohsin Shad; Asad Rahman; Huda Abbas; Fouzia Ashraf; M. Waheed Akhtar; Muhammad Sajjad (Archives of Microbiology, 2025)

Long-term grass lawn management increases soil organic carbon sequestration and microbial carbon use efficiency - Muhammad Nadeem Ashraf; Irfa Mehmood; Zia Ur Rahman Farooqi; Muhammad Itazaz Hassan; Muhammad Sanaullah; Muhammad Mubashar Zafar; Khalid M. Elhindi (Environmental Monitoring and Assessment, 2025)

Optimisation led energy-efficient arsenite and arsenate adsorption on various materials with machine learning - Jinsheng Huang; Waqar Muhammad Ashraf; Talha Ansar; Muhammad Mujtaba Abbas; Mehdi Tlija; Yingying Tang; Yunxue Guo; Wei Zhang (Water Research, 2025)

Production of IgY in egg yolk of Gallus gallus Domesticus by oral vaccination and its characterization with outer membrane of Ornithobacterium rhinotracheale - Muhammad Shahbaz Aslam; Summiya Khalid; Nadia Dar; Zaigham Abbas; Iram Gull; Zoha Khan; Sehreen Ashraf; Zahoor Qadir Samra (Veterinary Immunology and Immunopathology, 2025)

Effect of human chorionic gonadotropin on oocyte maturation and developmental competence in buffalo - Muhammad Bilal; Muhammad Kamran Ashraf; Talha Ashraf; Muhammad Yaseen; Ali Husnain; Muhammad Bilal Bin Majeed; Muhammad Imran; Burhan E. Azam Rana; Muhammad Hassan Mushtaq; Amjad Riaz (Theriogenology, 2025)

Advancements in metal selenide nanocomposites for efficient photocatalytic water splitting applications - Zeshan Ali Sandhu; Soha Ghaffar; Muhammad Asam Raza; Noor ul Huda; Sufyan Ashraf; Umair Talat; Areej Chauhdary; Hamza Gulzarab; Abdullah G. Al-Sehemi (Fuel, 2025)

Retraction notice to “Bio-mitigation of organic pollutants using horseradish peroxidase as a promising biocatalytic platform for environmental sustainability” [Environ. Res. 239-P1 (2023) 117192] - Muhammad Bilal; Anil Kumar Singh; Hafiz M.N. Iqbal; Tak H. Kim; Grzegorz Boczkaj; Khawlah Athmaneh; Syed Salman Ashraf (Environmental Research, 2025)

Advancing electrochemical water desalination: Machine learning-driven prediction and RSM optimization of activated carbon electrodes - Abdul Hai; Muhamad Fazly Abdul Patah; Muhammad Ashraf Sabri; G. Bharath; Fawzi Banat; Wan Mohd Ashri Wan Daud (Desalination, 2025)

Expression and characterization of the immunogenicity of rec-gp45 of Babesia bigemina using cattle - Zia-Ul-Rehman; Sarfraz-ur-Rahman; Kamran Ashraf; Muhammad Suleman; Sikandar Ali; Muhammad Imran Rashid (Tropical Animal Health and Production, 2025)

Increasing Salinity and Cadmium Enhanced Leaf Membrane Damage and H2O2 Production Irrespective of Reduced Sodium and Cadmium Accumulation in Wheat (Triticum aestivum L.) - Sajid Masood; Muhammad Ashraf; Mubshar Hussain; M. Farooq Azhar; M. Zafar-ul-Hye; Omer Farooq; Muhammad Aon; M. Tariq Javed (Journal of Soil Science and Plant Nutrition, 2025)

Chitosan Induced Modification in Morpho-Physiological, Biochemical and Yield Attributes of Pea (Pisum Sativum L.) Under Salt Stress - Sumreen Anjum; Qurat-ul Ain; Mubeen Sarwar; Muhammad Waqar Alam; Zain Mushtaq; Adnan Mukhtar; M. Irfan Ashraf; Abdulrahman Alasmari (Journal of Soil Science and Plant Nutrition, 2025)

Implications of nociceptor receptors and immune modulation: emerging therapeutic targets for autoimmune diseases - Syeda Asloob Fatima; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Muhammad Shahid; Fozia Anjum; Fatma Hussain; Aisha Mobashar; Maham Ashraf (Inflammopharmacology, 2025)

Appraisal of the physio-biochemical efficacy of exogenously applied natural and synthetic sources of plant growth stimulants in modulating drought stress tolerance in maize (Zea mays L.) - Abrar Ahmad; Nudrat Aisha Akram; Muhammad Ashraf (Acta Physiologiae Plantarum, 2025)

Identification and quantification of selected heavy metals by ICP-OES in skin whitening creams marketed in Pakistan - Mirza Nadeem Ahmad; Umm-e-Khadija Ashraf; Muhammad Naveed Anjum; Shumaila Kiran; Shazia Abrar; Muhammad Fayyaz Farid (Environmental Monitoring and Assessment, 2025)

ECCDN-Net: A deep learning-based technique for efficient organic and recyclable waste classification - Md. Sakib Bin Islam; Md. Shaheenur Islam Sumon; Molla E. Majid; Saad Bin Abul Kashem; Mohammad Nashbat; Azad Ashraf; Amith Khandakar; Ali K. Ansaruddin Kunju; Mazhar Hasan-Zia; Muhammad E.H. Chowdhury (Waste Management, 2025)

Exploring the phytochemical profile, antioxidant activity, and anticancer potential of Achillea millefolium extracts: In-vitro and in-silico investigation - Asia Kiran; Awais Altaf; Muhammad Sarwar; Tahir Maqbool; Muhammad Abdul Basit Ashraf; Muhammad Naveed; Tariq Aziz; Metab Alharbi (South African Journal of Botany, 2025)

Crosstalk between strigolactones and major hormones in plants under abiotic stresses - Farukh Ameen; Iqbal Hussain; Sunnia Afzal; Rizwan Rasheed; Muhammad Arslan Ashraf; Muhammad Iqbal (South African Journal of Botany, 2025)

Biomitigation of noxious metal ions using engineered lignin-based nanocomposites for sustainable environment - Zaeem Bin Babar; Rashid Iftikhar; Komal Rizwan; Shahid Munir; Mashhood Urfi; Fawad Ashraf; Muhammad Ali Inam; Shahid Iqbal; Muhammad Saad; Sajid Mahmood; Nasser S. Awwad; Hala A. Ibrahium (Journal of Water Process Engineering, 2025)

Building resilient urban drainage systems by integrated flood risk index for evidence-based planning - Shakeel Ahmad; Xuanrong Peng; Anam Ashraf; Dingkun Yin; Zhengxia Chen; Rasheed Ahmed; Muhammad Israr; Haifeng Jia (Journal of Environmental Management, 2025)

Key function mechanism of Na3PO4-modified NaX for enhanced performance and stability in side chain alkylation of toluene with methanol: DFT and experimental perspectives - Faraz Ahmad; Yueli Wen; Muhammad Zeeshan; Bin Wang; Awais Ashraf; Bai Hui; Zheng Cui; Chengda Li; Samia Kausar; Wei Huang (Fuel, 2025)

Xylooligosaccharides: A comprehensive review of production, purification, characterization, and quantification - Khubaib Ali; Nadia Niaz; Muhammad Waseem; Waqas Ashraf; Mudassar Hussain; Muhammad Umair Khalid; Assam Bin Tahir; Ali Raza; Imran Mahmood Khan (Food Research International, 2025)

GABA (γ-aminobutyric acid) enrichment and detection methods in cereals: Unlocking sustainable health benefits - Tabussam Tufail; Huma Bader Ul Ain; Muhammad Safiullah Virk; Jawad Ashraf; Zahoor Ahmed; Anees Ahmed Khalil; Amara Rasheed; Bin Xu (Food Chemistry, 2025)

Corrigendum to ‘The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system’ [Environ. Pollut. 364P1 (2024) 125311] - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

De Novo synthesis of selenium-doped CeO2@Fe3O4 nanoparticles for improving secondary metabolite biosynthesis in Carthamus tinctorius cell suspension culture - Kamran Ashraf; Zebo Liu; Qamar uz Zaman; Muhammad Arshad; Waqas Qamar Zaman; Ali Shan; Junxiong Yu; Touseef ur Rehman; Yingping Zhuang; Meijin Guo; Ali Mohsin (Chemical Engineering Journal, 2025)

Unveiling the potential of Loigolactobacillus coryniformis BCH-4 to ameliorate drought stress in Zea mays L. - Anam Tariq; Mahwish Salman; Muhammad Arslan Ashraf; Muhammad Rizwan Javed; Abdul Tawab (World Journal of Microbiology and Biotechnology, 2025)

A Novel Optimized Vibration-based Energy Harvester for Leak Detection in Wall-mounted Water Pipelines - Muhammad Faizan Mysorewala; Mati-Ur-Rasool Ashraf Virk; Mujahid Naqeebuddin Syed; Abdul-Wahid Saif; Lahouari Cheded; Saifullah Shafiq; Karim Sattar (Water Resources Management, 2025)

A comprehensive review on phytochemistry, pharmacology, preclinical, and clinical trials of Cydonia oblonga - Tuba; Muhammad Ajaz Hussain; Gulzar Muhammad; Muhammad Arshad Raza; Adnan Ashraf; Muhammad Tahir Haseeb; Muhammad Mushtaq; Zahid Shafiq (Phytochemistry Reviews, 2025)

Non-effervescent Polymeric Floating Tablets of Clarithromycin and Pantoprazole: Preparation and In-Vitro Evaluation for Improved Gastric Drug Retention - Fahad Ashraf; Kifayat Ullah Shah; Muhammad Danish Saeed; Faiqa Falak Naz; Fahad Y. Sabei; Tahseen Ahmed; Syed Shafqat Ali Shah; Amir Badshah; Naeem Ur Rehman; Kausar Ali Mahsud (Journal of Pharmaceutical Innovation, 2025)

Retraction Note: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2025)

Next-generation vaccines for influenza B virus: advancements and challenges - Muhammad Awais Ashraf; Muhammad Asif Raza; Azka Imran; Muhammad Nabeel Amjad (Archives of Virology, 2025)

Exploring hotspots of traffic accidents in Chiniot-Sargodha Road, Punjab, Pakistan - Taimoor Ashraf; Muhammad Irfan Ahamad; Shakeel Mahmood; Jiangtao Fu; Muhammad Sajid Mehmood; Adnanul Rehman; Sohail Abbas; Syed Ali Asad Naqvi; Rana Muhammad Zulqarnain (Environment, Development and Sustainability, 2025)

The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Combating Lead (Pb) Contamination: Integrating Biomonitoring, Advanced Detection, and Remediation for Environmental and Public Health - Saima Zafar; Sehrish Fatima; Farkhanda Asad; Muhammad Muzammil Nazir; Sania Batool; Asma Ashraf (Water, Air, & Soil Pollution, 2025)

Berberine in rheumatoid arthritis: a comprehensive review and meta-analysis of its anti-inflammatory and immunomodulatory mechanisms in animal models - Muhammad Muzammil Nazir; Iqra Farzeen; Shahla Fasial; Asma Ashraf (Inflammopharmacology, 2025)

Retraction Note: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2024)

Optimization of hydrogen production using a coculture of Chlamydomonas reinhardtii and activated sludge bacteria - Abdelsalam Zidan; Muhammad Asad Javed; Ashraf Aly Hassan (Chemosphere, 2024)

Effective synergism of Moringa oleifera with antibiotics, body growth, and decoction replacement - Qandeel Ashraf; Amjad Islam Aqib; Hamid Majeed; Shahbaz Ul Haq; Muhammad Farrukh Nisar; Muhammad Usman; Afshan Muneer; Saba Batool; Farid S. Ataya (South African Journal of Botany, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

Bioaugmentation of a novel bacterial consortium in cotton-planted soil for lambda-cyhalothrin degradation - Samina ANWAR; Anusha LIAQAT; Asma MUNIR; Muhammad F. ASHRAF; Samina IQBAL (Pedosphere, 2024)

Investigating the potential of 1,2,4-triazoles as corrosion inhibitors for copper and steel: A comprehensive review - Aqsa Ashraf; Naheed Riaz; Saima Muzaffar; Muhammad Atif; Bushra Bashir (Next Research, 2024)

Encapsulation, optimization, and characterization of lycopene using soy protein isolate-peach gum conjugate as wall material - Arif Hussain; Muhammad Hussain; Waqas Ashraf; Khubaib Ali; Abid Hussain; Hsu Mon Phyo; Muhammad Umair Khalid; Mudassar Hussain; Zhang Lianfu (Food Bioscience, 2024)

Overexpression of Gossypium arboreum 3-ketoacyl-CoA synthase 6 (GaKCS6) gene enhanced leaf epicuticle wax in Gossypium hirsutum L. and improved tolerance against whitefly - Muhammad Umair Majid; Rabiah Ashraf; Basit Jabbar; Usman Arif; Fatima Batool; Sameera Hassan; Bushra Rashid (Biocatalysis and Agricultural Biotechnology, 2024)

Interactive use of biochar and chemical fertilizer for improving nutrient availability and crop growth in rainfed area - Saddam Hussain; Rifat Hayat; Saleem Ullah; Muhammad Ashraf; Rebwar Nasir Dara; Muhammad Adeel Ashraf; Sami Ullah Khan; Muyassar Norberdiyeva; Manish Gupta; M. Ijaz Khan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Allelic variation in rice blast resistance: a pathway to sustainable disease management - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Ashraf M.M. Abdelbacki; Nimra Rajput; Xiaohong Jiang; Bisma Rao; Shimin Zuo (Molecular Biology Reports, 2024)

Unveiling the sweetness: evaluating yield and quality attributes of early generation sweet corn (Zea mays subsp. sachharata) inbred lines through morphological, biochemical and marker-based approaches - Shah Mohammad Usman; Raheel Shafeeq Khan; Asif Bashir Shikari; Nida Yousuf; Showkat Ahmad Waza; Shabir Hussain Wani; Muhammad Ashraf Bhat; F. Shazia; Faroq Ahmad Sheikh; Asma Majid (Molecular Biology Reports, 2024)

Identification and mechanism determination of the efflux pump subunit amrB gene mutations linked to gentamicin susceptibility in clinical Burkholderia pseudomallei from Malaysian Borneo - Ainulkhir Hussin; Sheila Nathan; Muhammad Ashraf Shahidan; Mohd Yusof Nor Rahim; Mohamad Yusof Zainun; Nurul Aiman Nafisah Khairuddin; Nazlina Ibrahim (Molecular Genetics and Genomics, 2024)

Plant Biostimulants: Mechanisms and Applications for Enhancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Kanza Asif; Humaira Ashraf; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Rehana Sardar; Fasih Ullah Haider (Journal of Soil Science and Plant Nutrition, 2024)

Exogenous Myo-inositol Weakens Salinity Effects by Improving Photosynthesis, ROS Homeostasis, Osmotic Adjustment, and Nutrient Acquisition in Maize (Zea mays L.) - Naheed Fatima; Muhammad Arslan Ashraf; Rizwan Rasheed; Mudassir Iqbal Shad; Shafaqat Ali (Journal of Plant Growth Regulation, 2024)

Comparative assessment of pantothenic, aspartic, ascorbic and tartaric acids assisted Pb-phytoextraction by sunflower (Helianthus annuus L.) - Asif Ghafoor; Fahad Shafiq; Sumera Anwar; Lixin Zhang; Muhammad Ashraf (BioMetals, 2024)

Drug resistance and possible therapeutic options against influenza A virus infection over past years - Muhammad Asif Raza; Muhammad Awais Ashraf (Archives of Microbiology, 2024)

Knockdown of the glucosamine-6-phosphate N-acetyltransferase gene by RNA interference enhances the virulence of entomopathogenic fungi against rice leaffolder Cnaphalocrocis medinalis - Muhammad Shakeel; Ashraf Khan; Juan Du; Abdul Basit; Guangming Yang; Khalid Haddi; Sohail Abbas; Aleena Alam; Shangwei Li (Pesticide Biochemistry and Physiology, 2024)

Climate change impact on water scarcity in the Hub River Basin, Pakistan - Muhammad Nabeel Aslam; Saqib Ashraf; Sangam Shrestha; Mustajab Ali; Nguyen Cong Hanh (Groundwater for Sustainable Development, 2024)

Leading report regarding the molecular epidemiology of Taenia hydatigena from Pakistan and global overview of the genetic diversity and population structure of the parasite - Naunain Mehmood; Hira Muqaddas; Aqsa Ashraf; Mahnoor Aslam; Maryam Khan; Madiha Fatima; Rahman Qadir; Samir Ibenmoussa; Turki M. Dawoud; Muhammad Irfan Ullah; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Characterization of cellulases from softening fruit for enzymatic depolymerization of cellulose - Hilary Edema; Muhammad Furqan Ashraf; Amos Samkumar; Laura Jaakola; Katja Karppinen (Carbohydrate Polymers, 2024)

Performance improvement of compression ignition engine fueled by second generation biodiesel fuel blends enriched with ZnO nanoparticles: Experimental study and Gaussian process regression AI modeling - Mohammed El-Adawy; Mohamed E. Zayed; Bashar Shboul; Waqar Muhammad Ashraf; Medhat A. Nemitallah (Process Safety and Environmental Protection, 2024)

Assessing the physicochemical properties of surface/groundwater of Sudhnoti district, Azad Jammu and Kashmir: Impacts on lindane degradation by photocatalysis - Taj Ur Rahman; Lubna Saba; Ashraf Ali; Wajiha Liaqat; Sanaullah Khan; Javed Ali Khan; Muhammad Aurang Zeb; Sajjad Hussain; Eman Y. Santali; Changseok Han (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Architecting high-performance photocatalysts: A review of modified 2D/2D graphene/g-C3N4 heterostructures - Muhammad Yasir Akram; Tuba Ashraf; Lei Tong; Xiulian Yin; Hongjun Dong; Huiling Lu (Journal of Environmental Chemical Engineering, 2024)

Synergistic inhibition effect of anisaldehyde and cinnamaldehyde (SAC) against Aspergillus species (A. flavus & A. niger) in vitro and on bread - Muhammad Umair Khalid; Hsu Mon Phyo; Yuhang Du; Khubaib Ali; Waqas Ashraf; Hang Yu; Imad Khan; Weirong Yao (Food Bioscience, 2024)

Field validation of NDVI to identify crop phenological signatures - Muhammad Tousif Bhatti; Hammad Gilani; Muhammad Ashraf; Muhammad Shahid Iqbal; Sarfraz Munir (Precision Agriculture, 2024)
Purpose and Methods Crop identification using remotely sensed imagery provides useful information to make management decisions about land use and crop health. This research used phonecams to acquire the Normalized Difference Vegetation Index (NDVI) of various crops for three crop seasons. NDVI time series from Sentinel (L121-L192) images was also acquired using Google Earth Engine (GEE) for the same period. The resolution of satellite data is low therefore gap filling and smoothening filters were applied to the time series data. The comparison of data from satellite images and phenocam provides useful insight into crop phenology. The results show that NDVI is generally underestimated when compared to phenocam data. The Savitzky-Golay (SG) and some other gap filling and smoothening methods are applied to NDVI time series based on satellite images. The smoothened NDVI curves are statistically compared with daily NDVI series based on phenocam images as a reference. Results The SG method has performed better than other methods like moving average. Furthermore, polynomial order has been found to be the most sensitive parameter in applying SG filter in GEE. Sentinel (L121-L192) image was used to identify wheat during the year 2022–2023 in Sargodha district where experimental fields were located. The Random Forest Machine Leaning algorithm was used in GEE as a classifier. Conclusion The classification accuracy has been found 97% using this algorithm which suggests its usefulness in applying to other areas with similar agro-climatic characteristics.

Allantoin regulated oxidative defense, secondary metabolism and ions homeostasis in maize (Zea mays L.) under heat stress - Humaira Yasmeen; Rizwan Rasheed; Muhammad Arslan Ashraf; Sadia Zafar; Shafaqat Ali (Physiology and Molecular Biology of Plants, 2024)

Photocatalytic degradation of rhodamine B dye pollutants by Fe3O4/SiO2 core–shell magnetic nanocomposite functionalized with TiO2 - Maisari Utami; Aditya Rianjanu; Muhammad Miqdam Musawwa; Selfi Citra Nur; Puji Lestari; Fatimah S. Al-Khattaf; Ashraf Atef Hatamleh; Murugesan Chandrasekaran; Woo Jin Chung; Soon Woong Chang; Balasubramani Ravindran (Environmental Geochemistry and Health, 2024)

Eco-toxicological impacts of industrial wastewater and the role of bio-electrochemical systems (BES) in remediation: a review - Muhammad Usman; Zhenhua Zhao; Olive Mekontchou Yemele; Muhammad Ibrahim; Waleed Raza; Zia Ur Rehman; Abduelrahman Adam Omer; Mir Moazzam Ali Talpur; Mouna Jeridi; Ghulam Abbas Ashraf; Hafsat Alhassan Danjaji (Clean Technologies and Environmental Policy, 2024)

Inflammatory response of nanoparticles: Mechanisms, consequences, and strategies for mitigation - Muhammad Summer; Rimsha Ashraf; Shaukat Ali; Horacio Bach; Shehzeen Noor; Qudsia Noor; Saima Riaz; Rana Rashad Mahmood Khan (Chemosphere, 2024)

Effect of supplementing epinephrine in maturation media on in-vitro developmental competence of cattle and buffalo oocytes - Abdul Khaliq; Muhammad Ameer Hamza; Talha Ashraf; Ali Husnain; Muhammad Yaseen; Abdul Rehman; Muhammad Binyameen; Muhammad Yasir Zahoor; Amjad Riaz (Theriogenology, 2024)

Oryza glumaepatula and calcium oxide nanoparticles enhanced Cr stress tolerance by maintaining antioxidant defense, chlorophyll and gene expression levels in rice - Humera Ashraf; Fozia Ghouri; Minghui Zhong; Sardar Alam Cheema; Fasih Ullah Haider; Lixia Sun; Shafaqat Ali; Mohammed Ali Alshehri; Xuelin Fu; Muhammad Qasim Shahid (Journal of Environmental Management, 2024)

Preparation, characterization and functional evaluation of soy protein isolate-peach gum conjugates prepared by wet heating Maillard reaction - Arif Hussain; Muhammad Hussain; Waqas Ashraf; Aiman Karim; Sahibzada Muhammad Aqeel; Adil Khan; Asif Hussain; Salman Khan; Zhang Lianfu (Food Research International, 2024)

Synergistic interactions and reaction mechanisms of biochar surface functionalities in antibiotics removal from industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Krzysztof Pikon (Environmental Pollution, 2024)

Seed Priming with Taurine Debilitates Copper Phytotoxic Effects by Maintaining Redox Balance, Ions Homeostasis and Photosynthetic Efficiency in Canola (Brassica napus L.) - Sadia Zafar; Rizwan Rasheed; Umer Farooq; Muhammad Arslan Ashraf; Shafaqat Ali; Mohammed Ali Alshehri; Khalid A. Al-Ghanim; Pallab K. Sarker (Journal of Soil Science and Plant Nutrition, 2024)

Exogenous Application of Silicon and Zinc Attenuates Drought Tolerance in Eruca sativa L. Through Increasing Chlorophyll Pigments, Osmoprotectants, and Modulating Defense Mechanisms - Iqbal Hussain; Atif Ayub; Airish Nayab; Muhammad Arslan Ashraf; Muhammad Arslan Ashraf; Sadam Hussain; Manzer H. Siddiqui; Muhammad Azeem Sabir; Usman Zulfiqar; Tanveer Hussain Khan (Journal of Plant Growth Regulation, 2024)

Evaluation of in vitro Skin Permeation of Clascoterone From Clascoterone Topical Cream, 1% (w/w) - Yang Yang; Jiang Wang; Apipa Wanasathop; Mengmeng Niu; Priyanka Ghosh; Ahmed Zidan; Jianghong Gu; Robert Hunt; Patrick Faustino; Muhammad Ashraf; Xiaoming Xu (AAPS PharmSciTech, 2024)

An ensemble-based strategy for robust predictive volcanic rock typing efficiency on a global-scale: A novel workflow driven by big data analytics - Umar Ashraf; Hucai Zhang; Aqsa Anees; Muhammad Ali; Hassan Nasir Mangi; Xiaonan Zhang (Science of The Total Environment, 2024)

A Robust Strategy of Geophysical Logging for Predicting Payable Lithofacies to Forecast Sweet Spots Using Digital Intelligence Paradigms in a Heterogeneous Gas Field - Umar Ashraf; Hucai Zhang; Hung Vo Thanh; Aqsa Anees; Muhammad Ali; Zhenhua Duan; Hassan Nasir Mangi; Xiaonan Zhang (Natural Resources Research, 2024)

CRISPR-Cas9 mediated understanding of plants’ abiotic stress-responsive genes to combat changing climatic patterns - Muhammad Waqas Choudry; Rabia Riaz; Pashma Nawaz; Maria Ashraf; Bushra Ijaz; Allah Bakhsh (Functional & Integrative Genomics, 2024)

Characterization of Exopolysaccharides Having Potential Antiviral Properties from Priestia Aryabattai Strain MK1 and Bacillus sp. Strain MK2 - Maham Khan; Muhammad Imran; Muhammad Ashraf; Wajid Ishaque; Mudasser Habib (Current Microbiology, 2024)

Historical review of surveillance methods, insecticide spray, and epidemiology of malaria in Bannu zone, Khyber Pakhtunkhwa, Pakistan - Muhammad Ashraf Khan (International Journal of Tropical Insect Science, 2024)

Retraction Note: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2024)

Silicon oxide nanoparticle mitigated the vanadium toxicity in Cucumber (Cucumis sativus L.) - Muhammad Mohsin Altaf; Sahrish Ashraf; Muhammad Qaisar Naeem Khan; Sibgha Noreen; Muhammad Anwar; Rafa Almeer; Rattandeep Singh; Atique ur Rehman (South African Journal of Botany, 2024)

Ameliorative potential of eriocitrin against cadmium instigated hepatotoxicity in rats via regulating Nrf2/keap1 pathway - Muhammad Faisal Hayat; Muhammad Zohaib; Muhammad Umar Ijaz; Moazama Batool; Asma Ashraf; Bader O. Almutairi; Usman Atique (Journal of Trace Elements in Medicine and Biology, 2024)

Melatonin induced reversibility of vanadium toxicity in muskmelon by regulating antioxidant defense and glyoxalase systems - Muhammad Mohsin Altaf; Zoia Arshad Awan; Sahrish Ashraf; Muhammad Ahsan Altaf; Zhiqiang Zhu; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Hazardous Materials, 2024)

Advanced photocatalysis as a viable and sustainable wastewater treatment process: A comprehensive review - Muhammad Ahtasham Iqbal; Sumia Akram; Shahreen khalid; Basant Lal; Sohaib Ul Hassan; Rizwan Ashraf; Gulmira Kezembayeva; Muhammad Mushtaq; Nurzhan Chinibayeva; Ahmad Hosseini-Bandegharaei (Environmental Research, 2024)

Corrigendum to “Current challenges of hydrothermal treated wastewater (HTWW) for environmental applications and their perspectives: A review” [Environ. Res. 212 Part D (2022) 113532] - Muhammad Usman; Zhijian Shi; Nalok Dutta; Muhammad Awais Ashraf; Bushra Ishfaq; Mohamed Gamal El-Din (Environmental Research, 2024)

Recent advancements in polyurethane-based membranes for gas separation - Noureen Arshad; Syeda Rubab Batool; Sadia Razzaq; Mubeen Arshad; Abher Rasheed; Munir Ashraf; Yasir Nawab; Muhammad Anwaar Nazeer (Environmental Research, 2024)

Graphene: A diamond hammer for cracking hard nuts in reverse osmosis desalination membranes - Muhammad Kashif; Muhammad Ashraf Sabri; Ning Zhang; Fawzi Banat (Desalination, 2024)

Air pollution and climate change as grand challenges to sustainability - Afifa; Kashaf Arshad; Nazim Hussain; Muhammad Hamza Ashraf; Muhammad Zafar Saleem (Science of The Total Environment, 2024)

Machine learning assisted improved desalination pilot system design and experimentation for the circular economy - Waqar Muhammad Ashraf; Muhammad Ahmad Jamil; Ghulam Moeen Uddin; Bashar Shboul; Kashif Ishfaq; Kim Choon Ng; Mike Dixon; Ben Bin Xu; Muhammad Wakil Shahzad (Journal of Water Process Engineering, 2024)

Towards artificial intelligence empowered performance enhancement of EDM process using nano-graphene mixed bio-dielectric supporting the carbon neutrality and sustainable development - Kashif Ishfaq; Muhammad Asad; Waqar Muhammad Ashraf; Muhammad Sana; Saqib Anwar; Wei Zhang; Vivek Dua (Journal of Cleaner Production, 2024)

Photocatalytic and biological efficacy of Carissa macrocarpa fruit extract-mediated one-pot synthesized ternary metal oxide dual S-scheme heterojunction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Akbar Ali; Muhammad Naeem-ul-Hassan; Javed Iqbal (Journal of Environmental Chemical Engineering, 2024)

Insights into the biogeochemical transformation, environmental impacts and biochar-based soil decontamination of antimony - Rabia Safeer; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muhammad Irtaza Sajjad Haider; Ayesha Imtiyaz Cheema; Samra Ijaz; Audil Rashid; Anila Sikandar; Krzysztof Pikoń (Environmental Research, 2024)

Insights into the involvement of male Hyalomma anatolicum ticks in transmitting Anaplasma marginale, lumpy skin disease virus and Theileria annulata - Sikandar Ali; Abdullah Saghir Ahmad; Kamran Ashraf; Jawaria Ali Khan; Muhammad Imran Rashid (Tropical Animal Health and Production, 2024)

Enhancing Plant Stress Resilience with Osmolytes and Nanoparticles - Yumna Rasheed; Faizan Khalid; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Nargis Naz; Muhammad Shahbaz; Usman Zulfiqar; Qasim Ali; Shamsa Rana (Journal of Soil Science and Plant Nutrition, 2024)

Thiamine Regulated Osmolyte Accumulation, Nutrient Acquisition, and ROS Metabolism to Lessen Salinity Effects on Wheat (Triticum aestivum L.) - Sunaira Urooj; Rizwan Rasheed; Muhammad Arslan Ashraf; Shafaqat Ali; Iqbal Hussain (Journal of Soil Science and Plant Nutrition, 2024)

Soil Organic Carbon and Nitrogen Mineralization Potential of Manures Regulated by Soil Microbial Activities in Contrasting Soil Textures - Waqar Ahmed; Muhammad Nadeem Ashraf; Muhammad Sanaullah; Muhammad Aamir Maqsood; Muhammad Ahmed Waqas; Shafeeq Ur Rahman; Saddam Hussain; Hammad Raza Ahmad; Adnan Mustafa; Xu Minggang (Journal of Soil Science and Plant Nutrition, 2024)

Morpho-Physiological and Enzymatic Responses of Zinnia (Zinnia elegans L.) to Different Metal Hoarded Wastewaters - Muhammad Ahsan; Adnan Younis; Muhammad Raheel; Imran Khalid; Hafiz Tassawar Abbas; Waqas Ashraf; Adil Mihoub; Emanuele Radicetti; Muhammad Farhan Saeed; Sajjad Ali; Mohammad Valipour; Aftab Jamal (Journal of Soil Science and Plant Nutrition, 2024)

Correction: Taurine Enervates Nickel Stress in Lagenaria siceraria by Regulating Redox Balance, Methylglyoxal Detoxification, H2S Production, and Nickel Uptake - Arslan Hafeez; Rizwan Rasheed; Muhammad Rizwan; Noman Habib; Sadia Zafar; Mudassir Iqbal Shad; Shafaqat Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2024)

Taurine Enervates Nickel Stress in Lagenaria siceraria by regulating Redox Balance, Methylglyoxal Detoxification, H2S Production, and Nickel Uptake - Arslan Hafeez; Rizwan Rasheed; Muhammad Rizwan; Noman Habib; Sadia Zafar; Mudassir Iqbal Shad; Shafaqat Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2024)

Interactive Effect of Drought Stress and l-Methionine on the Growth and Physio-Biochemical Changes in Broccoli (Brassica oleracea L. var. italica): Leaf and Head - Nudrat Aisha Akram; Kaneez Fatima; Haiyan Kong; Nimra Zafar; Seema Mahmood; Muhammad Ashraf; Arafat Abdel Hamed Abdel Latef (Journal of Plant Growth Regulation, 2024)

Genotoxicity of Copper, Silver and Green Synthetic Gold Nanoparticles in Fish (Ctenopharyngodon idella) - Ajmal Khan; Maghfoor Khan; Nazish Shah; Mansoor Khan; Abidullah Dawar; Ashraf Ali Shah; Farmanullah Dawar; Muhammad Khisroon (Biological Trace Element Research, 2024)

Unraveling the Endocannabinoid System: Exploring Its Therapeutic Potential in Autism Spectrum Disorder - Ankit Jana; Arnab Nath; Palash Sen; Swikriti Kundu; Badrah S. Alghamdi; Turki S. Abujamel; Muhammad Saboor; Chan Woon-Khiong; Athanasios Alexiou; Marios Papadakis; Mohammad Zubair Alam; Ghulam Md Ashraf (NeuroMolecular Medicine, 2024)
The salient features of autism spectrum disorder (ASD) encompass persistent difficulties in social communication, as well as the presence of restricted and repetitive facets of behavior, hobbies, or pursuits, which are often accompanied with cognitive limitations. Over the past few decades, a sizable number of studies have been conducted to enhance our understanding of the pathophysiology of ASD. Preclinical rat models have proven to be extremely valuable in simulating and analyzing the roles of a wide range of established environmental and genetic factors. Recent research has also demonstrated the significant involvement of the endocannabinoid system (ECS) in the pathogenesis of several neuropsychiatric diseases, including ASD. In fact, the ECS has the potential to regulate a multitude of metabolic and cellular pathways associated with autism, including the immune system. Moreover, the ECS has emerged as a promising target for intervention with high predictive validity. Particularly noteworthy are resent preclinical studies in rodents, which describe the onset of ASD-like symptoms after various genetic or pharmacological interventions targeting the ECS, providing encouraging evidence for further exploration in this area.

Pervasive influence of heavy metals on metabolic pathways is potentially relieved by hesperidin to enhance the phytoremediation efficiency of Bassia scoparia - Mazhar Hussain; Arslan Hafeez; Muhammad Rizwan; Rizwan Rasheed; Mahmoud F. Seleiman; Muhammad Arslan Ashraf; Shafaqat Ali; Umer Farooq; Muhammad Nafees (Environmental Science and Pollution Research, 2024)

Impact of green space and built environment on metabolic syndrome: A systematic review with meta-analysis - Muhammad Mainuddin Patwary; Mohammad Javad Zare Sakhvidi; Sadia Ashraf; Payam Dadvand; Matthew H.E.M. Browning; Md Ashraful Alam; Michelle L. Bell; Peter James; Thomas Astell-Burt (Science of The Total Environment, 2024)

Isolation and characterization of novel cadmium-resistant Escherichia fergusonii ZSF-15 from industrial effluent for flocculant production and antioxidant enzyme activity - Saima Zafar; Asma Ashraf; Sumreen Hayat; Muhammad Hussnain Siddique; Muhammad Waseem; Mudassir Hassan; Hira Qaisar; Saima Muzammil (Environmental Monitoring and Assessment, 2024)

Corrigendum to “Mimicking the cementation mechanism of ancient Roman seawater concrete using calcined clays” [Applied Clay Science 230 (2022) 106696] - Warda Ashraf; Ishrat Baki Borno; Rakibul I. Khan; Salman Siddique; Muhammad Intesarul Haque; Adhora Tahsin (Applied Clay Science, 2024)

Supplementation of nano-biochar improved growth and physiological attributes in wheat seedlings exposed to salt stress through enhanced activity of hydrolysing and nitrogen metabolic enzymes and regulation of crucial metabolites - Waqas Yousaf; Anis Ali Shah; Muhammad Bilal Afzal; Zaib-un Nisa; Naila Ali; Muhammad Yasin Ashraf; Hosam O. Elansary; Aqeel Ahmad (South African Journal of Botany, 2024)

Machine learning assisted prediction of solar to liquid fuel production: a case study - Muhammad Wakil Shahzad; Viet Hung Nguyen; Ben Bin Xu; Rasikh Tariq; Muhammad Imran; Waqar Muhammad Ashraf; Kim Choon Ng; Muhammad Ahmad Jamil; Amna Ijaz; Nadeem Ahmed Sheikh (Process Safety and Environmental Protection, 2024)

The development of plastic waste and sewage sludge co-pyrolyzed biochar composites with improved interfacial characteristics for the effective removal of ciprofloxacin - Aniqa Ashraf; Guijian Liu; Muhammad Arif; Balal Yousaf; Pervaiz Akhtar; Audil Rashid; Humaira Gulzaman; Rabia Safeer; Muhammad Saqib Rashid; Muhammad Irtaza Sajjad Haider (Process Safety and Environmental Protection, 2024)

Development of Maghemite Nanoparticles to Effectively Adsorb Methylene Blue Dye from Water - Muhammad Azeem Ashraf; Mumtaz Hasan Malik; Assad Farooq; Muhammad Tayyab Noman; Nayab Khan (Water, Air, & Soil Pollution, 2024)

Preharvest Application of Hydrogen Sulfide and Nitric Oxide Improves Floral Traits and Postharvest Performance of Cut Gladiolus Inflorescences - Faisal Zulfiqar; Anam Moosa; Anastasios Darras; Muhammad Nafees; Muhammad Ashraf; Ibrahim Al-Ashkar; Ayman El Sabagh; John T. Hancock (Journal of Plant Growth Regulation, 2024)

Geochemical Investigation of OCPs in the Rivers Along with Drains and Groundwater Sources of Eastern Punjab, Pakistan - Asmat Ali; Zahid Ullah; Maria Siddique; Junaid Ghani; Abdur Rashid; Warda Khalid; Muhammad Inayat Ullah Khan; Waqas Ashraf (Exposure and Health, 2024)

Water requirements of banana and papaya under different water table depths and soil types in the Lower Indus Basin of Pakistan - Nazar Gul; Hafiz Abdul Salam; Muhammad Ashraf (Irrigation and Drainage, 2024)
The water requirements of banana and papaya, the two most important fruit crops of Pakistan, are not known because farmers continue to apply water even if the crop does not need it. In this study, the evapotranspiration (ET), groundwater contribution (GW) and crop coefficient ( K c ) values of banana (1995–1999) and papaya (2013–2016) were determined under different water table depths (WTDs) and soil types using drainage‐type lysimeters. The WTDs were maintained at 1.50, 2.00 and 2.50 m from the ground surface by means of Mariotte bottles. The banana ET during the first year was between 1653 and 1992 mm with a GW contribution of 11–20%, whereas during the second to fifth years, it was between 2430 and 3023 mm with a GW contribution of 10–16%. The banana yield was in the range of 58,638–79,780 kg ha −1 , and the water use efficiency (WUE) was between 2.65 and 3.31 kg m −3 . The papaya ET was between 1478 and 1766 mm with a GW contribution of 7–18% at 1.50–2.50 m WTDs. The papaya yield was in the range of 61,184–83,004 kg ha −1 with a WUE of 4.13–4.70 kg m −3 . Therefore, GW contribution is an important component of the water balance under shallow water table conditions and should be considered when devising irrigation scheduling for banana and papaya crops.

Retraction Note: Environmental factors affecting the frequency of road traffic accidents: a case study of sub-urban area of Pakistan - Hafiz Mohkum Hammad; Muhammad Ashraf; Farhat Abbas; Hafiz Faiq Bakhat; Saeed A. Qaisrani; Muhammad Mubeen; Shah Fahad; Muhammad Awais (Environmental Science and Pollution Research, 2024)

Socio-environmental factors and solar housing system adoption: moderating effect of attitude - Ahsen Maqsoom; Muhammad Hammad; Muhammad Umer; Wesam Salah Alaloul; Hassan Ashraf; Muhammad Ali Musarat; Tahira Nazir (Innovative Infrastructure Solutions, 2024)

Rooftop rainwater harvesting potential for kitchen gardening in the Rawal watershed, Pakistan - Ghani Akbar; Shahid Hameed; Zafar Islam; Muhammad Asif; Arshad Ashraf (Arabian Journal of Geosciences, 2024)

Adopting Marine Spatial Planning (MSP) using coral health assessment as indicator: A case study in Pulau Redang Marine Park, Malaysia - Farhana Razak; Wei Yien Lua; Nor Hafzan Abd Rasid; Nazli Aziz; Izarenah Md Repin; Xiong-Zhi Xue; Abdul Rahman Muhammad Ashraf; Zainudin Bachok; Aminudin Afiq-Firdaus; Wan Izatul Asma Wan Talaat; Abdul Rahman Abdul Latip; Che Din Mohd Safuan (Ocean & Coastal Management, 2024)

GCDN-Net: Garbage classifier deep neural network for recyclable urban waste management - Md Mosarrof Hossen; Azad Ashraf; Mazhar Hasan; Molla E. Majid; Mohammad Nashbat; Saad Bin Abul Kashem; Ali K. Ansaruddin Kunju; Amith Khandakar; Sakib Mahmud; Muhammad E.H. Chowdhury (Waste Management, 2024)

Mitigating salt toxicity and overcoming phosphate deficiency alone and in combination in pepper (Capsicum annuum L.) plants through supplementation of hydrogen sulfide - Cengiz Kaya; Ferhat Uğurlar; Muhammad Ashraf; Mohammed Nasser Alyemeni; Raf Dewil; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Impact of Various Combinations of Organic and Inorganic Fertilizers on Fruit Production and Quality of ‘Kinnow’ Mandarin (Citrus reticulata Blanco.) - Muhammad Asim; Faisal Hayat; Tehseen Ashraf; Fakhara Khanum; Juan Li; Yang Peng; Yanxiao Ma; Shahid Iqbal; Ummara Khan; Sitwat Riaz; Panfeng Tu; Fiaz Hussain; et al. (Applied Fruit Science, 2024)

Field‐scale measurements of soil physico‐chemical profiles of the Potohar region in the Indus basin of Pakistan - Manzoor Ahmad Malik; Muhammad Ashraf (Irrigation and Drainage, 2024)
Soil physico‐chemical properties are important for best management practices. We measured infiltration, bulk density, texture, water retention and chemical profiles from the surface to 1.0 m and lithology to 50 m depths at 30 sites. The infiltration data were fitted to the cumulative and infiltration rate models of Philip and Horton. The same sites were used for water retention, physico‐chemical properties and lithological assessment. The cumulative models fit persistently better than their infiltration rate forms. The Horton cumulative model fitted statistically better than the corresponding Philip model. The dominant steady‐state infiltration rates were 15–30 and 30–45 mm h −1 over the entire profile. Sandy loam, loam and silt loam were the dominant soils. The percentages of sandy loam decreased, whereas silt loam increased, with depth. Water retention parameters and lithological strata were diverse and in harmony with physiography. Soil organic matter varied up to 2.5%. No sodicity or salinity was detected except in sparse saline seeps. The central tendency and extrema of the measured parameters were compatible with the literature, and the CVs of the soil hydraulic parameters were greater than those of the physical parameters. Comprehensive data are presented, which will serve as an important reference for regional and global repositories.

Potential of two entomopathogenic fungi, Beauveria bassiana and metarhizium anisopliae as biocontrol agents of Rhpalosiphum padi and Shizaphis graminum, (Homoptera: Aphididae) in laboratory and field - Misbah Ashraf; Dilbar Hussain; Shahbaz Hussain; Naima Din; Qurban Ali; Muhammad Shah Jahan; Muhammad Yasin; Muhammad Farooq (International Journal of Tropical Insect Science, 2024)

Physiological and biochemical effects of biochar nanoparticles on spinach exposed to salinity and drought stresses - Aimun Rasheed; Sumera Anwar; Fahad Shafiq; Zaib-un-Nisa; Shahbaz Khan; Muhammad Ashraf (Environmental Science and Pollution Research, 2024)

WITHDRAWN: Valorization of Algal Biomass to Synthesize Heterogeneous gCN-Biochar Photocatalyst for the Treatment of Industrial Wastewater using Photocatalysis-Persulfate Oxidation Process - Aqsa Shafique; Hafiz Muhammad Uzair Ayub; Javed Iqbal; Shanawar Hamid; Fawad Ashraf; Muhammad Saif Ur Rehman; S. Boukhari; Mohamed A. Habila; Alam Nawaz; Tahir Fazal (Chemosphere, 2024)

How can natural resource dependence, environmental-related technologies and digital trade protect the environment: Redesigning SDGs policies for sustainable environment? - Muhammad Zubair Ashraf; Wei Wei; Muhammad Usman; Shahid Mushtaq (Resources Policy, 2024)

Nutraceutical and Health-Promoting Potential of Lactoferrin, an Iron-Binding Protein in Human and Animal: Current Knowledge - Muhammad Faizan Ashraf; Dawood Zubair; Muhammad Noaman Bashir; Mahmoud Alagawany; Shabbir Ahmed; Qurban Ali Shah; Jameel Ahmed Buzdar; Muhammad Asif Arain (Biological Trace Element Research, 2024)

Pathological effects of feeding aflatoxin-contaminated feed on immune status and reproductive performance of juvenile white leghorn males and its mitigation with ∝-tocopherol and Moringa oleifera - Muhammad Kashif Saleemi; Ahmad Raza; Aisha Khatoon; Muhammad Zubair; Shafia Tehseen Gul; Xu Yongping; Bilal Murtaza; Faqir Muhammad; Bushra Akhtar; Farhat Jubeen; Farzana Rizvi; Khawar Zubair; et al. (Environmental Science and Pollution Research, 2023)

RETRACTED: Machine learning based prediction and experimental validation of arsenite and arsenate sorption on biochars - Wei Zhang; Waqar Muhammad Ashraf; Sachini Supunsala Senadheera; Daniel S. Alessi; Filip M.G. Tack; Yong Sik Ok (Science of The Total Environment, 2023)

Alteration of microbial carbon and nitrogen metabolism within the soil metagenome with grazing intensity at semiarid steppe - Zhen Wang; Kai Tang; Paul C. Struik; Muhammad Nadeem Ashraf; Tongrui Zhang; Yanning Zhao; Riliga Wu; Ke Jin; Yuanheng Li (Journal of Environmental Management, 2023)

Influence of biochar produced from negative pressure-induced carbonization on transformation of potentially toxic metal(loid)s concerning plant physiological characteristics in industrially contaminated soil - Ayesha Imtiyaz Cheema; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muyuan Lu; Samina Irshad; Krzysztof Pikon; Mehr Ahmed Mujtaba Munir; Muhammad Saqib Rashid (Journal of Environmental Management, 2023)

Highly efficient PdNiB decorated over carbon supports for the electrochemical valorization of furfural and 5-hydroxymethylfurfural into fuels - Muhammad Ashraf Sabri; G. Bharath; Abdul Hai; Mohammad Abu Haija; Ricardo P. Nogueira; Fawzi Banat (Fuel, 2023)

RETRACTED: Bio-mitigation of organic pollutants using horseradish peroxidase as a promising biocatalytic platform for environmental sustainability - Muhammad Bilal; Anil Kumar Singh; Hafiz M.N. Iqbal; Tak H. Kim; Grzegorz Boczkaj; Khawlah Athmaneh; Syed Salman Ashraf (Environmental Research, 2023)

Correction to: Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

LC-ESI-MS analysis, antioxidant, anti-diabetic and molecular docking studies on Corchorus depressus (L.) C.Chr - Shazia Anjum; Humna Tahir; Sadia Sarwar; Wajid Raza; Irum Latif; Hafiz Muhammad Farhan Rasheed; Qaiser Jabeen; Wardah Shahid; Muhammad Ashraf; Syeda Sadaf Zehra; Zaheer Ul-Haq; Muhammad Ayaz; et al. (Natural Product Research, 2023)

Sustainable tourism and sustainable development goals (SDGs): a state-of-the-art review of past, present, and future trends - Muhammad Ashraf Fauzi (Environment, Development and Sustainability, 2023)

Using walnut shells as low-cost adsorbent materials in an anaerobic filter medium of a De-centralized wastewater treatment system (DEWATS) - Muhammad Zaheer; Muhammad Shaham Ali; Ning Huang; Muhammad Aqeel Ashraf (Chemosphere, 2023)

Unrivalled insight into potential biopharmaceutical application of Saussurea albescens (DC.) Sch.Bip.: Chemical profiling, antioxidant and enzyme inhibition activities and in silico studies - Muhammad Imran Tousif; Muhammad Saleem; Saba Tauseef; Mamona Nazir; Tahira Ruby; Reaz Uddin; Sharon Elaine D'souza; Muhammad Aleem Ashraf; Ghulam Mustafa Kamal; Jallat Khan; Gokhan Zengin (Biocatalysis and Agricultural Biotechnology, 2023)

Retraction Note: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Efficacy of zinc-based nanoparticles in alleviating the abiotic stress in plants: current knowledge and future perspectives - Ali Raza Khan; Wardah Azhar; Xingming Fan; Zaid Ulhassan; Abdul Salam; Muhammad Ashraf; Yihua Liu; Yinbo Gan (Environmental Science and Pollution Research, 2023)

Could climate change exacerbate droughts in Bangladesh in the future? - Mahfuzur Rahman; Md Sakib Hasan Tumon; Md Monirul Islam; Ningsheng Chen; Quoc Bao Pham; Kashif Ullah; Sumaiya Jarin Ahammed; Sharmina Naznin Liza; Md Abdul Aziz; Salit Chakma; Muhammad Esmat Enan; Md. Alomgir Hossain; et al. (Journal of Hydrology, 2023)

Sustainable EDM of Inconel 600 in Cu-mixed biodegradable dielectrics: Modelling and optimizing the process by artificial neural network for supporting net-zero from industry - Kashif Ishfaq; Muhammad Sana; Waqar Muhammad Ashraf; Vivek Dua (Journal of Cleaner Production, 2023)

Citric acid and hydrogen sulfide cooperate to mitigate chromium stress in tomato plants by modulating the ascorbate-glutathione cycle, chromium sequestration, and subcellular allocation of chromium - Cengiz Kaya; Muhammad Ashraf; Mohammed Nasser Alyemeni; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2023)

Nano priming for boosting growth and resilience in crops under abiotic stresses - Faizan Khalid; Kanza Asif; Yumna Rasheed; Humaira Ashraf; Muhammad Faisal Maqsood; Shamsa Rana; Usman Zulfiqar; Nargis Naz; Muhammad Shahbaz; Rehana Sardar; Zunaira Riaz (Biocatalysis and Agricultural Biotechnology, 2023)

Multiplex Cas9-based excision of CLCuV betasatellite and DNA-A revealed reduction of viral load with asymptomatic cotton plants - Sana Shakoor; Abdul Qayyum Rao; Sara Ajmal; Aneela Yasmeen; Muhammad Azmat Ullah Khan; Sahar Sadaqat; Naeem Mahmood Ashraf; Felix Wolter; Michael Pacher; Tayyab Husnain (Planta, 2023)

Contribution of Fluid Substitution and Cheetah Optimizer Algorithm in Predicting Rock-Physics Parameters of Gas-Bearing Reservoirs in the Eastern Mediterranean Sea, Egypt - Mohamed Abd Elaziz; Ashraf Ghoneimi; Muhammad Nabih; Ahmed Bakry; Mohammed Azmi Al-Betar (Natural Resources Research, 2023)
In this study, the elastic characteristics of reservoir rocks and their relationship to porosity and pore fluid were predicted using the fluid substitution method in combination with machine learning techniques. We first discarded the data at gas points to remove the erroneous effect of gas on the prediction process of Poisson’s ratio using the three proposed machine learning models. Then, the prediction was carried out after substituting the gas zones by oil and by water. As a result, the prediction was enhanced and showed stronger correlation coefficient values. The integration of fluid substitution and machine learning methods was applied in the reservoir of Scarab field as a case study from the Eastern Mediterranean to detect the effect of different pore fluids (gas, oil, and water) on Poisson's ratio estimation. The main objective of the study was to analyze the seismic and well log data to estimate and predict the Poisson’s ratio in four fluid-content cases; these are gas-bearing reservoir, reservoir after removal of log data of gas-bearing zones, and reservoirs after gas-substitution with oil and with water. These four cases were dealt with directly and by using the machine learning algorithms based on the proposed model of random vector functional link (RVFL), which was enhanced by the Cheetah optimizer (CO). This study shows how the performance of RVFL is affected by the presence or absence of gas zones. It is shown that the Poisson’s ratio value increases when gas is substituted with water more than when gas is substituted with oil. For validation of these results, regression analysis technique was used and the correlation coefficient of the CO–RVFL model increased after removing well log data of gas zones and was more enhanced after fluid substitution from gas to oil or to water.

A systematic review of physiological signals based driver drowsiness detection systems - Adil Ali Saleem; Hafeez Ur Rehman Siddiqui; Muhammad Amjad Raza; Furqan Rustam; Sandra Dudley; Imran Ashraf (Cognitive Neurodynamics, 2023)

Validation of the environmental Kuznets curve and role of economic globalization: an aggregate and sectoral analysis of an Indian economy - Ashfaq Ahmad; Muhammad Mobeen Shafqat; Muhammad Ilyas; Muhammad Umair Ashraf; Afshan Urooj; Zhao Yu huan (Air Quality, Atmosphere & Health, 2023)

Arsenic fractionation and speciation in different textured soils supplied with farmyard manure and accumulation by sunflower under alkaline calcareous conditions - Muhammad Awais Piracha; Muhammad Ashraf; Sher Muhammad Shahzad; Sajid Masood; Naeem Akhtar; Rizwana Kausar; Awais Shakoor (Environmental Science and Pollution Research, 2023)

Micro- and nanoplastics: Contamination routes of food products and critical interpretation of detection strategies - Muhammad Sohail; Zunaira Urooj; Sobia Noreen; Mirza Muhammad Faran Ashraf Baig; Xing Zhang; Bingzhi Li (Science of The Total Environment, 2023)

Assessment of essential and toxic elemental concentrations in tumor and non-tumor tissues with risk of colorectal carcinoma in Pakistan - Muhammad Abdul Qayyum; Tahir Farooq; Aqsa Baig; Tanveer Hussain Bokhari; Muhammad Naveed Anjum; Mian Habib-ur-Rahman Mahmood; Ahmad Raza Ashraf; Khawaja Muddassir; Muhammad Ahmad (Journal of Trace Elements in Medicine and Biology, 2023)

Allantoin alleviates chromium phytotoxic effects on wheat by regulating osmolyte accumulation, secondary metabolism, ROS homeostasis and nutrient acquisition - Rizwan Alam; Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain; Shafaqat Ali (Journal of Hazardous Materials, 2023)

Exploring the multifunctional roles of quantum dots for unlocking the future of biology and medicine - Muhammad Kashif Ali; Saher Javaid; Haseeb Afzal; Imran Zafar; Kompal Fayyaz; Qurat ul Ain; Mohd Ashraf Rather; Md. Jamal Hossain; Summya Rashid; Khalid Ali Khan; Rohit Sharma (Environmental Research, 2023)

Social media in disaster management: review of the literature and future trends through bibliometric analysis - Muhammad Ashraf Fauzi (Natural Hazards, 2023)

Pressmud and Farmyard Manure Improve Growth and Yield of Wheat Irrigated with Textile Dye-Contaminated Wastewater through Increasing Nutrient Uptake and Dye Degradation - Muhammad Imran; Muhammad Ashraf; Abdul Rasul Awan; Wajid Ishaque; Hadeeqa Arshad (Journal of Soil Science and Plant Nutrition, 2023)

Correction to: Molecular and genetic insights into secondary metabolic regulation underlying insect‑pest resistance in legumes - Muhammad Khuram Razzaq; Aiman Hina; Asim Abbasi; Benjamin Karikari; Hafiza Javaria Ashraf; Muhammad Mohiuddin; Sumaira Maqsood; Aqsa Maqsood; Inzamam Ul Haq; Guangnan Xing; Ghulam Raza; Javaid Akhter Bhat (Functional & Integrative Genomics, 2023)

Molecular and genetic insights into secondary metabolic regulation underlying insect-pest resistance in legumes - Muhammad Khuram Razzaq; Aiman Hina; Asim Abbasi; Benjamin Karikari; Hafiza Javaria Ashraf; Muhammad Mohiuddin; Sumaira Maqsood; Aqsa Maqsood; Inzamam Ul Haq; Guangnan Xing; Ghulam Raza; Javaid Akhter Bhat (Functional & Integrative Genomics, 2023)

Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Taurine protected Trifolium alexandrinum L. plants from damages of individual and interactive effects of chromium and drought stress - Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Mudassir Iqbal Shad; Wajeeha Nazim (Acta Physiologiae Plantarum, 2023)

Coumarin regulated redox homeostasis to facilitate phytoremediation of saline and alkaline soils by bitter gourd (Momordica charantia L.) - Kamila Iram; Muhammad Arslan Ashraf; Sobhy M. Ibrahim; Rizwan Rasheed; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

Experimental behaviour of unreinforced and confined rat-trap bond masonry - Muhammad Haris; Mohammad Ashraf; Muhammad Fahim; Samiullah (European Journal of Environmental and Civil Engineering, 2023)

The degradation of single-use plastics and commercially viable bioplastics in the environment: A review - Siti Norliyana Idris; Tan Suet May Amelia; Kesaven Bhubalan; Anim Maisara Mohd Lazim; Nurul Aliah Mohd Ahmad Zakwan; Muhammad Imran Jamaluddin; Rameshkumar Santhanam; Al-Ashraf Abdullah Amirul; Sevakumaran Vigneswari; Seeram Ramakrishna (Environmental Research, 2023)

Effect of exogenous taurine on growth, oxidative defense, and nickel (Ni) uptake in canola (Brassica napus L.) under Ni stress - Muhammad Arslan Ashraf; Arslan Hafeez; Rizwan Rasheed; Iqbal Hussain; Umer Farooq; Muhammad Rizwan; Shafaqat Ali (Physiology and Molecular Biology of Plants, 2023)

Proline Alleviates Abiotic Stress Induced Oxidative Stress in Plants - Faisal Zulfiqar; Muhammad Ashraf (Journal of Plant Growth Regulation, 2023)

Spectroscopic fingerprinting, pollution characterization, and health risk assessment of potentially toxic metals from urban particulate matter - Abdul Rehman; Guijian Liu; Balal Yousaf; Samra Ijaz; Samina Irshad; Ayesha Imtiyaz Cheema; Muhammad Umair Riaz; Aniqa Ashraf (Environmental Science and Pollution Research, 2023)

Exploring the asymmetric effects of urbanization and trade on CO2 emissions: fresh evidence from Pakistan - Xiongfeng Pan; Aneela Ashraf; Syed Muhammad Faraz Raza; Fazliddin Nasriddinov; Maaz Ahmad (Environmental Science and Pollution Research, 2023)

Use of remote sensing-based pressure-state-response framework for the spatial ecosystem health assessment in Langfang, China - Anam Ashraf; Muhammad Athar Haroon; Shakeel Ahmad; Ahmed Samir Abowarda; Chunyue Wei; Xuehua Liu (Environmental Science and Pollution Research, 2023)

Effect of seed priming by taurine on growth and chromium (Cr) uptake in canola (Brassica napus L.) under Cr stress - Muhammad Arslan Ashraf; Sobhy M. Ibrahim; Rizwan Rasheed; Muhammad Rizwan; Iqbal Hussain; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

Multifunctional catalyst-assisted sustainable reformation of lignocellulosic biomass into environmentally friendly biofuel and value-added chemicals - Muhammad Naeem; Muhammad Imran; Shoomaila Latif; Adnan Ashraf; Nazim Hussain; Grzegorz Boczkaj; Wojciech Smułek; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Evaluation of Physio-Morphological and Biochemical Responses for Salt Tolerance in Wheat (Triticum aestivum L.) Cultivars - Muhammad Arslan Ashraf; Arslan Hafeez; Rizwan Rasheed; Iqbal Hussain; Umer Farooq; Muhammad Rizwan; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Occurrence and risk evaluation of endocrine-disrupting chemicals in wastewater and surface water of Lahore, Pakistan - Muhammad Ashfaq; Yan Li; Muhammad Zubair; Muhammad Saif Ur Rehman; Sajjad Hussain Sumrra; Muhammad Faizan Nazar; Ghulam Mustafa; Muhammad Tahir Fazal; Humayun Ashraf; Qian Sun (Environmental Geochemistry and Health, 2023)

Temporal study of wastewater surveillance from September 2020 to March 2021: an estimation of COVID-19 patients in Lahore, Pakistan - Muhammad Adnan Ashraf; Muhammad Nawaz; Ali Asif; Muhammad Asad Ali; Adnan Mehmood; Muhammad Waqar Aziz; Muhammad Zubair Shabbir; Nadia Mukhtar; Muhammad Abu Bakr Shabbir; Sohail Raza; Tahir Yaqub (Environmental Science and Pollution Research, 2023)

Investigating the environmental externalities of digital financial inclusion and the COVID-19 pandemic: an environmental sustainability perspective - ShiYong Zheng; Bing Sheng; Abdul Ghafoor; Ahsan Ali Ashraf; Ghulam Muhammad Qamri (Environmental Science and Pollution Research, 2023)

Phytoremediation potential modulated by structural and functional traits in a saline desert halophyte Fagonia indica Burm. f - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Syed Mohsan Raza Shah; Farooq Ahmad; Majid Anwar; Sana Basharat; Ansa Asghar; Muhammad Ashraf (Environmental Science and Pollution Research, 2023)

Impregnation of biochar with montmorillonite and its activation for the removal of azithromycin from aqueous media - Muhammad Arif; Guijian Liu; Muhammad Zia ur Rehman; Md Manik Mian; Aniqa Ashraf; Balal Yousaf; Muhammad Saqib Rashid; Rafay Ahmed; Muhammad Imran; Mehr Ahmed Mujtaba Munir (Environmental Science and Pollution Research, 2023)

Physiological effects of some engineered nanomaterials on radish (Raphanus sativus L.) intercropped with pea (Pisum sativum L.) - Mehr-un-Nisa; Fahad Shafiq; Sumera Anwar; Arslan Mahmood; Muhammad Iqbal; Kaleem Ullah; Muhammad Zulqarnain; Imtiaz Haider; Muhammad Ashraf; Lixin Zhang (Environmental Science and Pollution Research, 2023)

Supplementation of Moringa based zinc oxide nanoparticles mitigates salt stress in Celosia argentea through reduced chloride (Cl −) uptake and modulation in physiochemical attributes - Musarrat Ramzan; Nabeera Naveed; Muhammad Zaheer Ahmed; Hina Ashraf; Anis Ali Shah; Muhammad Jamil; Zahoor Ahmad; Ryan Casini; Hosam O. Elansary (South African Journal of Botany, 2023)

Transcriptomic and proteomic profiling reveals toxicity and molecular action mechanisms of bioengineered chitosan‑iron nanocomposites against Xanthomonas oryzae pv. oryzae - Temoor Ahmed; Luqiong Lv; Muhammad Noman; Hafiza Ayesha Masood; Muhammad Rizwan; Munazza Ijaz; Ashraf Atef Hatamleh; Munirah Abdullah Al-Dosary; Hayssam M. Ali; Jianping Chen; Bin Li (Pesticide Biochemistry and Physiology, 2023)

Modulation of structural and functional traits in facultative halophyte Salvadora oleoides Decne. For adaptability under hyper-arid and saline environments - Ummar Iqbal; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Nargis Naz; Muhammad Ashraf; Muhammad Kaleem (Journal of Arid Environments, 2023)

Exploration of the bioenergy potential of Dactyloctenium aegyptium through pyrolysis, kinetics, and thermodynamic parameters to produce clean fuels and biochemicals - Hesham Alhumade; Omar S. Alayed; Muhammad Waqas Iqbal; Ayesha Shahid; Tanveer Iqbal; Muhammad Sajjad Ahmad; Ali Elkamel; Yusuf Al-Turki; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

A Novel Machine Learning Approach for Detecting Outliers, Rebuilding Well Logs, and Enhancing Reservoir Characterization - Muhammad Ali; Peimin Zhu; Ma Huolin; Heping Pan; Khizar Abbas; Umar Ashraf; Jar Ullah; Ren Jiang; Hao Zhang (Natural Resources Research, 2023)

Allicin Decreases Phytotxic Effects of Petroleum Hydrocarbons by Regulating Oxidative Defense and Detoxification of Cytotoxic Compounds in Wheat - Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Freeha Fatima Qureshi; Muhammad Rizwan; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Interactive Effects of Soil and Foliar-Applied Nanobiochar on Growth, Metabolites, and Nutrient Composition in Daucus carota - Habiba Khaliq; Sumera Anwar; Fahad Shafiq; Muhammad Ashraf; Lixin Zhang; Imtiaz Haider; Shahbaz Khan (Journal of Plant Growth Regulation, 2023)

Assessment of formulation variables of poor water soluble diacerein for its improved loading and anti-inflammatory activity - Maryam Shabbir; Kashif Barkat; Muhammad Umer Ashraf; Uzair Nagra; Syed Nisar Hussain Shah (Drug Delivery and Translational Research, 2023)

Mineralogy and PGE geochemistry of chromitites and peridotites of the sapat complex in the indus suture zone, northern Pakistan: implications for magmatic processes in the supra-subduction zone - Zaheen Ullah; Huan Li; Asad Khan; Shah Faisal; Yildirim Dilek; Michael W. Förster; Muhammad Farhan; Umar Ashraf; Salman Ahmed Khattak; Gohar Rehman; Syed Asim Hussain (International Geology Review, 2023)

Withametelin, a steroidal lactone, isolated from datura innoxa attenuates STZ-induced diabetic neuropathic pain in rats through inhibition of NF-kB/MAPK signaling - Adnan Khan; Bushra Shal; Ashraf Ullah Khan; Muhammad Waleed Baig; Ihsan ul Haq; Salman Khan (Food and Chemical Toxicology, 2023)

Dramatic changes in anatomical traits of a C4 grass Chrysopogon serrulatus Trin. (Poaceae) over a 1000 m elevational gradient - Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Mahwish Munir; Muhammad Ashraf; Syed Mohsan Raza Shah; Sana Basharat; Iftikhar Ahmad; Sangam Khalil (Journal of Mountain Science, 2023)

Long-term manure application increased soil organic carbon and nitrogen mineralization through accumulation of unprotected and physically protected carbon fractions - Muhammad Nadeem ASHRAF; Cheng HU; Xiangru XU; Tariq AZIZ; Lei WU; Muhammad Ahmed WAQAS; Muhammad FAROOQ; Xu HU; Wenju ZHANG; Minggang XU (Pedosphere, 2023)

Iron limitation effect on H2/CO2 biomethanation: Experimental and model analysis - Farinaz Ebrahimian; Giovanna Lovato; Merlin Alvarado-Morales; Muhammad Tahir Ashraf; José Alberto Domingues Rodrigues; Panagiotis Tsapekos; Irini Angelidaki (Journal of Environmental Chemical Engineering, 2023)

Effect of exogenous taurine on pea (Pisum sativum L.) plants under salinity and iron deficiency stress - Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Rizwan; Iqbal Hussain; Ramish Aslam; Freeha Fatima Qureshi; Barira Shoukat Hafiza; Rohina Bashir; Shafaqat Ali (Environmental Research, 2023)

Effect of Metals or Trace Elements on Wheat Growth and Its Remediation in Contaminated Soil - Iqbal Hussain; Sunnia Afzal; Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Hamzah Saleem; Aishah Alatawi; Farukh Ameen; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Methods to convert lignocellulosic waste into biohydrogen, biogas, bioethanol, biodiesel and value-added chemicals: a review - Nalok Dutta; Muhammad Usman; Muhammad Awais Ashraf; Gang Luo; Mohamed Gamal El-Din; Shicheng Zhang (Environmental Chemistry Letters, 2023)

Algae-Mediated Resource Recovery from Urban Wastewater - Muhammad Usman; Mahwish Amin; Iqra Kamal; Ayesha Shahid; Jingliang Xu; Md. Asraful Alam; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf; Raj Boopathy (Current Pollution Reports, 2023)

Exogenous Coumarin Decreases Phytotoxic Effects of Manganese by Regulating Ascorbate–Glutathione Cycle and Glyoxalase System to Improve Photosynthesis and Nutrient Acquisition in Sesame (Sesamum indicum L.) - Mudassir Iqbal Shad; Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2023)

Silicon Enhances Morpho–Physio–Biochemical Responses in Arsenic Stressed Spinach (Spinacia oleracea L.) by Minimizing Its Uptake - Muhammad Hamzah Saleem; Manar Fawzi Bani Mfarrej; Aishah Alatawi; Sahar Mumtaz; Muhammad Imran; Muhammad Arslan Ashraf; Muhammad Rizwan; Kamal Usman; Parvaiz Ahmad; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Fullerenol [60] Nano-cages for Protection of Crops Against Oxidative Stress: A Critical Review - Fahad Shafiq; Muhammad Iqbal; Syed Hammad Raza; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2023)

Levels of Genetic Variants Among Symptomatic Blastocystis Subtypes and their Relationship to Mucosal Immune Surveillance in the Precancerous Colons of Experimentally Infected Rats - Eman M. Hussein; Muhammad A. A. Muhammad; Abdalla M. Hussein; Sherine M. Elzagawy; Wafaa M. Zaki; Ashraf G. Temsah; Mohamed S. Badr; Maha M. Alabbassy (Acta Parasitologica, 2023)
Purpose The relationship between the genetic diversity of Blastocystis and immune surveillance in precancerous colons with blastocystosis is still under investigation. This study aimed to identify the genetic Blastocystis variants among 54 symptomatic human isolates and their relationship to mucosal immune surveillance in the precancerous polyps of experimentally infected rats. Methods Polymerase chain reaction and high-resolution melting (PCR/HRM) curves discriminated human symptomatic Blastocystis isolates into subtypes (STs)/intrasubtypes, which were orally administered to rats to induce experimental infection. Then, the mucosal immune responses of the infected colons were evaluated in relation to polyp formation through immunostaining to identify mucus MUC2 and determine mucosal immune cell (goblet, lymphocyte and mast) counts, secretory IgA levels and parasitic intestinal invasion. Results ST1, ST3, and ST4 were found in 18.5% (10/54), 54.7% (29/54), and 27.8% (15/54) of the samples, respectively. Then, the HRM curve discriminated ST3 into the wild, mutant, and heterozygous [17/54 (31.5%), 5/54 (9.3%), and 7/54 (12.9%)] intrasubtypes. ST1 and ST4 had no genetic variations. Precancerous polyps were detected in the colons of 40.5% of the infected rats. ST1 constituted 14.7% of these cases, while the wild, mutant, and heterozygous intrasubtypes of ST3 showed polyps in 12.9%, 5.5%, and 5.5% of cases, respectively. Only 1.9% of the polyps were related to ST4. MUC2 showed weak immunostaining in 44.5% of the infected colons, and 38.9% were polyp inducers. Low goblet cell numbers and high interepithelial lymphocyte counts were significantly associated with polyp formation, particularly with ST1 and wild ST3. Among the polyp inducers, high numbers of mast cells were detected in wild ST3 and ST4, while a low number was found with heterozygous ST3. The level of secretory IgA was low in polyp-inducing STs. Most of the results were statistically significant. Conclusion Immunosurveillance showed a potential relationship between ST1 and the ST3 intrasubtypes and precancerous polyps. This relationship may provide insight into the prevention and/or development of new immunotherapeutic strategies to combat colorectal cancer.

Phytotoxic effects of chemically synthesized copper oxide nanoparticles induce physiological, biochemical, and ultrastructural changes in Cucumis melo - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fiza Liaquat; Shazma Gulzar; Liying Chang; Yidong Zhang (Environmental Science and Pollution Research, 2023)

Recyclable Cu–Ag bimetallic nanocatalyst for radical scavenging, dyes removal and antimicrobial applications - Faisal Ali; Sadia Akbar; Mika Sillanpaa; Umer Younas; Adnan Ashraf; Muhammad Pervaiz; Rizwan Kausar; Ikram Ahmad; Asma A. Alothman; Mohamed Ouladsmane (Chemosphere, 2023)

Photocatalytic stimulation of peroxymonosulfate by novel MoO3@ZrO2 with Z-scheme heterojunction for diclofenac sodium degradation - Ghulam Abbas Ashraf; Raqiqa Tur Rasool; Rafiqat Ul Rasool; Muhammad Farooq Saleem; Jazib Ali; Djamel Ghernaout; Muhammad Hassan; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Hai Guo (Journal of Water Process Engineering, 2023)

An assessment of the efficacy of biochar and zero-valent iron nanoparticles in reducing lead toxicity in wheat (Triticum aestivum L.). - Muhammad Nauman Mahamood; Sihang Zhu; Ali Noman; Abid Mahmood; Sana Ashraf; Muhammad Aqeel; Muhammad Ibrahim; Sobia Ashraf; Rock Keey Liew; Su Shiung Lam; Muhammad Kashif Irshad (Environmental Pollution, 2023)

Production performance, protein digestibility, gut health and economic efficiency in sexed broilers with super dozing of lysine - Najam us Sahar; Muhammad Shoaib; Muhammad Aslam Mirza; Shaukat Ali Bhatti; Shahzad Ashraf; Noreen Aslam; Alishbah Roobi; Muhammad Arslan Asif (Tropical Animal Health and Production, 2023)

Clinical pharmacokinetics of terbutaline in humans: a systematic review - Khadeeja Sultan; Ammara Zamir; Waseem Ashraf; Imran Imran; Hamid Saeed; Anees ur Rehman; Abdul Majeed; Muhammad Fawad Rasool (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Assessment of climate change impacts on glacio-hydrological processes and their variations within critical zone - Muhammad Shafeeque; Yi Luo; Arfan Arshad; Sher Muhammad; Muhammad Ashraf; Quoc Bao Pham (Natural Hazards, 2023)

Exploring kuhl irrigation system potential in changing cryosphere regime of Astore river basin, Pakistan - Arshad Ashraf; Mehwish Iqbal; Muhammad Asif (Arabian Journal of Geosciences, 2023)

Assessment of aflatoxin M 1 exposure and associated determinants in children from Lahore, Pakistan - Waseela Ashraf; Abdul Rehman; Mansur-ud-Din Ahmad; Masood Rabbani; Muhammad Hassan Mushtaq; Khalida Aamir; Fareeha Akhtar; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2023)

Biocatalytic degradation of reactive blue 221 and direct blue 297 dyes by horseradish peroxidase immobilized on iron oxide nanoparticles with improved kinetic and thermodynamic characteristics - Umme Kalsoom; Nasira Khalid; Affaf Ibrahim; Syed Salman Ashraf; Haq Nawaz Bhatti; Zainab Ahsan; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Rock physics analysis from predicted Poisson's ratio using RVFL based on Wild Geese Algorithm in scarab gas field in WDDM concession, Egypt - Muhammad Nabih; Ashraf Ghoneimi; Ahmed Bakry; Samia Allaoua Chelloug; Mohammed Azmi Al-Betar; Mohamed Abd Elaziz (Marine and Petroleum Geology, 2023)

Role of biochar-based free radicals in immobilization and speciation of metals in the contaminated soil-plant environment - Muhammad Saqib Rashid; Guijian Liu; Balal Yousaf; Yasir Hamid; Abdul Rehman; Muhammad Arif; Rafay Ahmed; Yu Song; Aniqa Ashraf (Journal of Environmental Management, 2023)

Impact of seasons and wastewater cultivation on the biomass and biodiesel production by the Plectonema terebrans BERC10 as a candidate for a multiproduct algal biorefinery - Muhammad Nabeel Haider; Aqib Zafar Khan; Muhammad Usman; Deepanraj Balakrishnan; Muhammad Rizwan Javed; Sana Malik; Chen-Guang Liu; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

Insight into microwave-assisted synthesis of the chitosan-MOF composite: Pb(II) adsorption - Humaira Gul Zaman; Lavania Baloo; Shamsul Rahman Kutty; Khalid Aziz; Muhammad Altaf; Aniqa Ashraf; Faissal Aziz (Environmental Science and Pollution Research, 2023)

Morphophysiological responses of sweet basil (Ocimum basilicum L.) to the nickel stress and inoculation with Pseudomonas strains - Marzieh Davoudi; Behrooz Esmaielpour; Gholamreza Gohari; Ali Ashraf Soltani Toolarood; Morteza Sheikhalipour; Hamideh Fatemi; Maryam Haghighi; Muhammad Farooq (Acta Physiologiae Plantarum, 2023)

How do energy prices and climate shocks affect human health? Insights from BRICS - Wenxin Wang; Muhammad Hafeez; Hong Jiang; Muhammad Usman Ashraf; Muhammad Asif; Muhammad Wasim Akram (Environmental Science and Pollution Research, 2022)

A Review on Solid Microneedles for Biomedical Applications - Nimra Tariq; Muhammad Waseem Ashraf; Shahzadi Tayyaba (Journal of Pharmaceutical Innovation, 2022)

A green and environmental sustainable approach to synthesis the Mn oxide nanomaterial from Punica granatum leaf extracts and its in vitro biological applications - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Shazma Gulzar; Liying Chang; Yidong Zhang (Environmental Monitoring and Assessment, 2022)

A Comprehensive Review About Bioactive Peptides: Sources to Future Perspective - Muhammad Naeem; Muhammad Inamullah Malik; Talha Umar; Swaiba Ashraf; Adnan Ahmad (International Journal of Peptide Research and Therapeutics, 2022)

Effects of climate change on vegetation and snow cover area in Gilgit Baltistan using MODIS data - Zulqarnain Satti; Muhammad Naveed; Muhammad Shafeeque; Sikandar Ali; Farkhod Abdullaev; Tauseef Muhammad Ashraf; Muhammad Irshad; Lanhai Li (Environmental Science and Pollution Research, 2022)

Engineered and green natural pozzolan-nano silica-based alkali-activated concrete: shrinkage characteristics and life cycle assessment - Babatunde Abiodun Salami; Mohammed Ibrahim; Mohammed A. Al-Osta; Muhammad Nasir; Mohammed Rizwan Ali; Ashraf A. Bahraq; Alimi Wasiu (Environmental Science and Pollution Research, 2022)

Exogenous menadione sodium bisulphite alleviates detrimental effects of alkaline stress on wheat (Triticum aestivum L.) - Ali Akbar; Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Shafaqat Ali; Abida Parveen (Physiology and Molecular Biology of Plants, 2022)

The Interactive Effect of Selenium and Farmyard Manure on Soil Microbial Activities, Yield and Selenium Accumulation by Wheat (Triticum aestivum L.) Grains - Muhammad Usman Khalid; Muhammad Imran; Muhammad Aslam; Muhammad Ashraf (Journal of Plant Growth Regulation, 2022)

Photosynthetic Efficiency and Antioxidant Defense Potential are Key Players in Inducing Drought Tolerance in Transgenic Tobacco Plants Over-Expressing AVP1 - Hamid Manzoor; Muhammad Shahzad Anjam; Fozia Saeed; Sumaira Rasul; Saira Yousaf; Ayesha Kirn; Muhammad Kamran Qureshi; Zafar Ullah Zafar; Muhammad Ashraf; Habib-ur-Rehman Athar (Journal of Plant Growth Regulation, 2022)

How do multiple kernel functions in machine learning algorithms improve precision in flood probability mapping? - Muhammad Aslam Baig; Donghong Xiong; Mahfuzur Rahman; Md. Monirul Islam; Ahmed Elbeltagi; Belayneh Yigez; Dil Kumar Rai; Muhammad Tayab; Ashraf Dewan (Natural Hazards, 2022)

Oxytetracycline and Ciprofloxacin Antibiotics Exhibit Contrasting Effects on Soil Microflora, Nitrogen Uptake, Growth, and Yield of Wheat (Triticum aestivum L.) - Narmeen Mehboob Khan; Muhammad Imran; Muhammad Ashraf; Hadeeqa Arshad; Abdul Rasul Awan (Journal of Soil Science and Plant Nutrition, 2022)

Contribution of structural and functional adaptations of hyper-accumulator Suaeda vera Forssk. ex J.F. Gmel. for adaptability across salinity gradients in hot desert - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Ashraf; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Syed Mohsan Raza Shah; Faakeha Islam; Iftikhar Ahmad; Farial Ejaz; Mehwish Naseer (Environmental Science and Pollution Research, 2022)

Determination and detoxification of aflatoxin and ochratoxin in maize from different regions of Pakistan - Syed Wajih ul Hassan Shah Gillani; Yumna Sadef; Muhammad Imran; Hafiz Muhammad Fahad Raza; Aamir Ghani; Sumera Anwar; Muhammad Yasin Ashraf; Shabbir Hussain (Environmental Monitoring and Assessment, 2022)

Assessment of aflatoxin B 1 -lysine adduct in children and its effect on child growth in Lahore, Pakistan - Waseela Ashraf; Abdul Rehman; Mansur-ud-Din Ahmad; Masood Rabbani; Muhammad Hassan Mushtaq; Khalida Aamir; Kathy S. Xue; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2022)

Genome-wide identification and comparative analysis of MATE gene family in Cucurbitaceae species and their regulatory role in melon (Cucumis melo) under salt stress - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fazal Haq; Samiah Arif; Muhammad Abdullah; Qingliang Niu; Yidong Zhang (Horticulture, Environment, and Biotechnology, 2022)

Resveratrol and neuroprotection: an insight into prospective therapeutic approaches against Alzheimer’s disease from bench to bedside - Fahadul Islam; Mohamed H. Nafady; Md. Rezaul Islam; Susmita Saha; Salma Rashid; Aklima Akter; Md. Harun- Or-Rashid; Muhammad Furqan Akhtar; Asma Perveen; Ghulam Md. Ashraf; Md. Habibur Rahman; Sherouk Hussein Sweilam (Molecular Neurobiology, 2022)

Pathological effects of graded doses of aflatoxin B1 on the development of the testes in juvenile white leghorn males - Anas Ashraf; Muhammad Kashif Saleemi; Mashkoor Mohsin; Shafia Tehseen Gul; Muhammad Zubair; Faqir Muhammad; Sheraz Ahmed Bhatti; Muhammad Raza Hameed; Muhammad Imran; Hamid Irshad; Iqra Zaheer; Ishtiaq Ahmed; et al. (Environmental Science and Pollution Research, 2022)

In Vitro Testing of Sunscreens for Dermal Absorption: Method Comparison and Rank Order Correlation with In Vivo Absorption - Yang Yang; Ann-Marie Ako-Adounvo; Jiang Wang; Sergio G. Coelho; Steven A. Adah; Murali K. Matta; David Strauss; Theresa M. Michele; Jian Wang; Patrick J. Faustino; Thomas O’Connor; Muhammad Ashraf (AAPS PharmSciTech, 2022)

Unraveling the survival potential of a desert halophyte Salvadora oleoides Decne. across heterogenic environments - Ummar Iqbal; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf (Trees, 2022)

Predicting Shale Volume from Seismic Traces Using Modified Random Vector Functional Link Based on Transient Search Optimization Model: A Case Study from Netherlands North Sea - Mohamed Abd Elaziz; Ashraf Ghoneimi; Ammar H. Elsheikh; Laith Abualigah; Ahmed Bakry; Muhammad Nabih (Natural Resources Research, 2022)

Omics: a tool for resilient rice genetic improvement strategies - Muhammad Naeem; Zeeshan Ali; Anzal Khan; Sami-Ul-Allah; Hassan Javed Chaudhary; Javeria Ashraf; Faheem Shahzad Baloch (Molecular Biology Reports, 2022)

Comprehensive characterization of Guanosine monophosphate synthetase in Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Sajid Fiaz; Muhammad Imran; Ke Yanguo; Waseem Hassan; Umair Ashraf; Yuansheng He; Xuanjie Cai; Zhijiang Wang; Lei Yu; Xianwen Ye; et al. (Molecular Biology Reports, 2022)

Choline Chloride Mediates Chromium Tolerance in Spinach (Spinacia oleracea L.) by Restricting its Uptake in Relation to Morpho-physio-biochemical Attributes - Iqbal Hussain; Muhammad Hamzah Saleem; Sahar Mumtaz; Rizwan Rasheed; Muhammad Arslan Ashraf; Faisal Maqsood; Muzammal Rehman; Humaira Yasmin; Shakeel Ahmed; Muhammad Ishtiaq; Sana Anwar; Shafaqat Ali (Journal of Plant Growth Regulation, 2022)

Seasonal variation in species composition and relative abundance of mosquitoes in the District Bannu, Khyber Pakhtunkhwa, Pakistan: prospects of dengue fever in the study area - Muhammad Ashraf Khan (International Journal of Tropical Insect Science, 2022)

Taurine modulates dynamics of oxidative defense, secondary metabolism, and nutrient relation to mitigate boron and chromium toxicity in Triticum aestivum L. plants - Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Muhammad Iqbal; Muhammad Umar Farooq; Muhammad Hamzah Saleem; Shafaqat Ali (Environmental Science and Pollution Research, 2022)

Fertigation of calcium nitrate [Ca(NO3)2] confers metal tolerance in two chickpea (Cicer arietinum L.) cultivars - Abida Parveen; Iqbal Hussain; Shagufta Perveen; Muhammad Arslan Ashraf; Rizwan Rasheed; Saddam Hussain; Sajjad Hussain; Sumaira Thind; Arshad Ali; Zahid Ullah; Qaisar Mahmood (Arabian Journal of Geosciences, 2022)

Survival strategies in two high altitude Sorghum species from western Himalayas - Khwaja Shafique Ahmad; Anum Javaid; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Ashraf; Syed Mohsan Raza Shah; Muhammad Sajid Aqeel Ahmad; Iftikhar Ahmad (Acta Physiologiae Plantarum, 2022)

Anatomical and physiological features modulate ion homeostasis and osmoregulation in aquatic halophyte Fimbristylis complanata (Retz.) link - Muhammad Kaleem; Mansoor Hameed; Farooq Ahmad; Muhammad Ashraf; Muhammad Sajid Aqeel Ahmad (Acta Physiologiae Plantarum, 2022)

Synthesis of 1,2,3-benzotriazin-4(3H)-one derivatives as α-glucosidase inhibitor and their in-silico study - Zunera Khalid; Syed S. Shafqat; Hafiz A. Ahmad; Hafiz M. Rehman; Munawar A. Munawar; Matloob Ahmad; Abdullah M. Asiri; Muhammad Ashraf (Medicinal Chemistry Research, 2022)

Phyto-mediated photocatalysis: a critical review of in-depth base to reactive radical generation for erythromycin degradation - Aniqa Ashraf; Guijian Liu; Balal Yousaf; Muhammad Arif; Rafay Ahmed; Audil Rashid; Luqman Riaz; Muhammad Saqib Rashid (Environmental Science and Pollution Research, 2022)

Temporal variation in leachate composition of a newly constructed landfill site in Lahore in context to environmental pollution and risks - Mahsoon Ashraf; Muhammad Zeshan; Sadia Hafeez; Rahib Hussain; Abdul Qadir; Muzaffar Majid; Farman Ahmad; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2022)

Intelligent autonomous underwater vehicle mobility with energy efficient routing in sensor networks - Imran Shafi; Muhammad Junaid Ashraf; Gyu Sang Choi; Sadia Din; Imran Ashraf (Environment, Development and Sustainability, 2022)

Effects of Ferula asafetida, closantel, albendazole, oxfendazole, and ivermectin against Haemonchus contortus in goats and sheep - Abdul Jabbar; Muhammad Zahid Iqbal; Muhammad Ashraf; Aneela Zameer Durrani; Hira Sajjad; Mohammed Nasiru Wana; Asad Ullah; Muhammad Imran; Muhammad Shair Zaman Ghauri; Hafiz Ishfaq Ahmad (Tropical Animal Health and Production, 2022)

Lethal and parasitism effects of selected novel pesticides on the immature stages of Trichogramma chilonis (Trichogrammatidae: Hymenoptera) - Muhammad Ashraf Khan (International Journal of Tropical Insect Science, 2022)

Controlled nitrogen transformation in chemo-amended urea improves nitrogen use efficiency and productivity of wheat grown on alkaline calcareous soil - Arooba Ashraf; Muhammad Akhtar; Muhammad Ashraf; Saddam Hussain (Environmental Science and Pollution Research, 2022)

Modulation in Plant Micro-structures Through Soil Physicochemical Properties Determines Survival of Salsola imbricata Forssk. in Hypersaline Environments - Nargis Naz; Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Hina Shahid; Ummar Iqbal; Muhammad Kaleem; Syed Mohsan Raza Shah; Iftikhar Ahmad (Journal of Soil Science and Plant Nutrition, 2022)

Competency of groundwater recharge of irrigated cotton field subjacent to sowing methods, plastic mulch, water productivity, and yield under climate change - Muhammad Saeed; Ahsan Maqbool; Muhammad Adnan Ashraf; Muhammad Arshad; Kashif Mehmood; Muhammad Usman; Muhammad Arslan Farid (Environmental Science and Pollution Research, 2022)
Irrigated agriculture is a foremost consumer of water resources to fulfill the demand for food and fiber with an increasing population under climate changes; cotton is no exception. Depleting groundwater recharge and water productivity is critical for the sustainable cotton crop yield peculiarly in the semiarid region. This study investigated the water productivity and cotton yield under six different treatments: three sowing methods, i.e., flat, ridge, and bed planting with and without plastic mulch. Cotton bed planting without mulch showed maximum water productivity (0.24 kg.m −3 ) and the highest cotton yield (1946 kg.ha −1 ). Plastic mulching may reduce water productivity and cotton yield. HYDRUS-1D unsaturated flow model was used to access the groundwater recharge for 150 days under six treatments after model performance evaluation. Maximum cumulative recharge was observed 71 cm for the flat sowing method without plastic mulch. CanESM2 was used to predict climate scenarios for RCP 2.6, 4.5, and 8.5 for the 2050s and 2080s by statistical downscale modeling (SDSM) using historical data from 1975 to 2005 to access future groundwater recharge flux. Average cumulative recharge flux declined 36.53% in 2050 and 22.91% in 2080 compared to 2017 without plastic mulch. Multivariate regression analysis revealed that a maximum 23.78% reduction in groundwater recharge could influence future climate change. Further study may require to understand the remaining influencing factor of depleting groundwater recharge. Findings highlight the significance of climate change and the cotton sowing method while accessing future groundwater resources in irrigated agriculture.

A new endophytic fungus CJAN1179 isolated from the Cholistan desert promotes lateral root growth in Arabidopsis and produces IAA through tryptophan-dependent pathway - Adeela Naureen; Faiz-ul H. Nasim; Muhammad S. Choudhary; Muhammad Ashraf; Florian M. W. Grundler; A. Sylvia S. Schleker (Archives of Microbiology, 2022)
Fungi, important for growth of plants in arid lands, are expected to be involved in novel biochemical activities during fungal–plant interactions. We isolated 150 fungi associated with rhizosphere and root endosphere of two perennial grasses, Cymbopogon jwarancusa and Panicum antidotale , from Cholistan desert. The isolates were screened for their impact on plant growth and development using Arabidopsis thaliana (Col-0) as a model system. A root-endophytic fungus CJAN1179 from C. jwarancusa showed the highest plant growth-promoting effects. The most remarkable was enhanced number of lateral roots (3.1-fold). CJAN1179 produced indole-3-acetic acid (IAA) particularly in the presence of tryptophan. ITS sequence and phylogenetic analysis characterisation suggested the fungus to be a new species within Sordariomycetidae. CJAN1179 appears to promote plant growth by secreting IAA using tryptophan as a precursor. This fungus can be further explored for its suitability to promote growth of commercially important crops, particularly in arid regions.

Molecular Evidence and Hematological Profile of Bovines Naturally Infected with Ehrlichiosis in Southern Punjab, Pakistan - Muhammad Abdul Basit; Muhammad Ijaz; Jawaria Ali Khan; Kamran Ashraf; Rao Zahid Abbas (Acta Parasitologica, 2022)

Comparative microbiome analysis of Diaphorina citri and its associated parasitoids Tamarixia radiata and Diaphorencyrtus aligarhensis reveals Wolbachia as a dominant endosymbiont - Hafiza Javaria Ashraf; Luis Carlos Ramos Aguila; Komivi Senyo Akutse; Muhammad Ilyas; Asim Abbasi; Xiaofang Li; Liande Wang (Environmental Microbiology, 2022)
Summary Microbiome analysis in a host–parasitoid interaction network was conducted to compare the taxonomic composition of bacterial communities of Diaphornia citri , Tamarixia radiata , and Diaphorencyrtus aligarhensis . The comparative analysis revealed differences in the composition and diversity of the symbiont populations across the host and its associated parasitoids. Proteobacteria was the most dominant phylum, representing 67.80% of the total bacterial community, while Candidatus Profftella armature and Wolbachia were the dominant genera across the host and parasitoids. There were clear differences observed in alpha and beta diversity of microbiota through the host and its associated parasitoids. The function prediction of bacterial communities and Pearson correlation analysis showed that specific bacterial communities displayed positive correlations with the carbohydrate metabolism pathway. Furthermore, when symbiotic bacteria were eliminated using a broad‐spectrum antibiotic, tetracycline hydrochloride, the parasitoids' median survival time and longevity were significantly reduced. We confirmed the physiological effects of symbiotic bacteria on the fitness of parasitoids and demonstrated the effect of antibiotics in decreasing the food intake and measurement of amino acids in the hemolymph. This study sheds light on basic information about the mutualism between parasitoids and bacteria, which may be a potential source for biocontrol strategies for citrus psyllid, especially D. citri .

RNA interference-mediated knockdown of odorant-binding protein 2 and MP58 gene causes mortality in Myzus persicae - Iqra Mahmood; Amber Afroz; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Umer Rashid; Muhammad Azmat Ullah Khan; Naeem Mehmood Ashraf; Sadia Alam (International Journal of Tropical Insect Science, 2022)

Comparative seismic performance assessment of RC and RC/ECC hybrid frame structures: a shake table study - Fasih Ahmed Khan; Muhammad Rashid; Sajjad Wali Khan; Muhammad Rizwan; Yasir Irfan Badrashi; Muhammad Fahim; Muhammad Ashraf Tanoli; Wasim Khaliq; Akhtar Gul (Innovative Infrastructure Solutions, 2022)

Impact of COVID-19 on environmental ecosystem - Muhammad Aqeel Ashraf; Muhammad Faheem; Muhammad Azher Hassan (Environmental Science and Pollution Research, 2022)

A study on the contamination assessment, health risk and mobility of two heavy metals in the soil-plants-ruminants system of a typical agricultural region in the semi arid environment - Xiaoping Ge; Zafar Iqbal Khan; Fu Chen; Mubeen Akhtar; Kafeel Ahmad; Abid Ejaz; Muhammad Arslan Ashraf; Muhammad Nadeem; Shahzad Akhtar; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Do BRI policy and institutional quality influence economic growth and environmental quality? An empirical analysis from South Asian countries affiliated with the Belt and Road Initiative - Junaid Ashraf; Liangqing Luo; Muhammad Khalid Anser (Environmental Science and Pollution Research, 2022)

Knowledge, attitude, and practice of clinicians about antimicrobial stewardship and resistance among hospitals of Pakistan: a multicenter cross-sectional study - Sohaib Ashraf; Shoaib Ashraf; Moneeb Ashraf; Muhammad Ahmad Imran; Zawar Ahmad Choudhary; Hadiqa Tul Hafsa; Abeer Bin Awais; Larab Kalsoom; Iqra Farooq; Zaighum Habib; Sidra Ashraf; Qurrat Ul Ain Iqbal; et al. (Environmental Science and Pollution Research, 2022)

Value addition and risk assessment of dairy digestate as biofertilizer on crop yield and soil fertility - Sidra Mukhtar; Abdullah Yasar; Yusra Mahfooz; Rizwan Rasheed; Amtul Bari Tabinda; Muhammad Adnan Ashraf; Muhammad Nauman; Afifa Malik (Arabian Journal of Geosciences, 2022)

Energy-efficient dynamic channel allocation algorithm in wireless body area network - Muhammad Ashraf; Shahzad Hassan; Saddaf Rubab; Muhammad Attique Khan; Usman Tariq; Seifedine Kadry (Environment, Development and Sustainability, 2022)

Chemical characterisation, in vitro antioxidant, cytotoxicity and safety evaluation of Polystichum braunii (Spenn.) fee roots - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Azhar Rasul; Mirza Muhammad Faran Ashraf Baig (Natural Product Research, 2021)

Quantifying climate-induced drought risk to livelihood and mitigation actions in Balochistan - Muhammad Ashraf; Adnan Arshad; Praharsh M. Patel; Adeel Khan; Huma Qamar; Ristina Siti-Sundari; Muhammad Usman Ghani; Ali Amin; Jamilur Rehman Babar (Natural Hazards, 2021)

Anti-neuropathic pain activity of a cationic palladium (II) dithiocarbamate by suppressing the inflammatory mediators in paclitaxel-induced neuropathic pain model - Muhammad Naveed; Rahim Ullah; Adnan Khan; Bushra Shal; Ashraf Ullah Khan; Shahan Zeb Khan; Zia ur Rehman; Salman Khan (Molecular Biology Reports, 2021)

Soil microbial biomass and extracellular enzyme–mediated mineralization potentials of carbon and nitrogen under long-term fertilization (> 30 years) in a rice–rice cropping system - Muhammad Nadeem Ashraf; Gao Jusheng; Wu Lei; Adnan Mustafa; Ahmed Waqas; Tariq Aziz; Waqas-ud-Din Khan; Shafeeq-ur-Rehman; Babar Hussain; Muhammad Farooq; Zhang Wenju; Xu Minggang (Journal of Soils and Sediments, 2021)

Hydrogen Sulfide (H2S) Mitigates Arsenic (As)-Induced Toxicity in Pea (Pisum sativum L.) Plants by Regulating Osmoregulation, Antioxidant Defense System, Ascorbate Glutathione Cycle and Glyoxalase System - Abdulaziz Abdullah Alsahli; Javaid Akhter Bhat; Mohammed Nasser Alyemeni; Muhammad Ashraf; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2021)

Do neonicotinoids better than pyrethroids for Coccinella septempunctata L. (Coleoptera: Coccinellidae)? A comparative sub-lethal indirect age-stage, two-sex life tables laboratory bioassay - Muhammad Rizwan; Bilal Atta; Misbah Rizwan; Ijaz Ashraf; Muhammad Arshad; Muhammad Tahir; Mudassir Ali; Arshed Makhdoom Sabir; Muhammad Bilal; Muhammad Yasir Ali (International Journal of Tropical Insect Science, 2021)

Expression studies of stress responsive genes in cotton Gossypium hirsutum L. - Muhammad Naeem; Muhammad Iqbal; Sami Ul-Allah; Hassan Javed Chaudhary; Wajad Nazeer; Javeria Ashraf; Faheem Shahzad Baloch (Molecular Biology Reports, 2021)

Structural and Functional Determinants of Physiological Pliability in Kyllinga brevifolia Rottb. for Survival in Hyper-Saline Saltmarshes - Sahar Mumtaz; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Iftikhar Ahmad; Muhammad Ashraf; Muhammad Hamzah Saleem (Water, Air, & Soil Pollution, 2021)

Environmental impact and diversity of protease-producing bacteria in areas of leather tannery effluents of Sialkot, Pakistan - Muhammad Qasim Butt; Nadia Zeeshan; Naeem Mahmood Ashraf; Muhammad Aftab Akhtar; Hina Ashraf; Amber Afroz; Aqsa Shaheen; Shumaila Naz (Environmental Science and Pollution Research, 2021)

Evaluating socio‐economic and environmental factors influencing farm‐level water scarcity in Punjab, Pakistan * - Muhammad Awais Ali Khan; Khalid Mahmood Ch.; Ijaz Ashraf; Muhammad Tahir Siddiqui; Jerry W. Knox (Irrigation and Drainage, 2021)
Pakistan's economy is primarily dependent on agriculture, but it faces serious water challenges. This paper critically evaluates the water resources and socio‐economic and environmental factors contributing to increased farm‐level water scarcity in the Punjab region. The study involved conducting structured interviews with 370 farmers to gather data necessary for conducting a detailed sociotechnical factor analysis. From this, eight factors were identified that were found to directly impact farmer well‐being including climate change (rise in temperature and erratic rainfall), poor socio‐economic farmer conditions, issues linked to the warabandi (canal water distribution system), inadequate irrigation, reduced water availability, poor water course maintenance, and low adoption of efficient irrigation techniques. The Kruskal‐Wallis test was then used to assess statistical differences between the respondents' demographic attributes and the identified factors. Demographic factors including age, education, land size, farming experience, and cultivated area showed significant mean differences with the eight factors. Young farmers with higher education levels were more likely to adopt high‐efficiency irrigation systems to conserve water. The research also highlighted the importance of introducing crops with a lower water demand into the region and the need to proactively support agricultural extension services to encourage farmers to adopt more efficient irrigation systems to improve crop productivity and facilitate on‐farm water conservation.

Salicylic Acid– and Ascorbic Acid–Induced Salt Tolerance in Mung bean (Vigna radiata (L.) Wilczek) Accompanied by Oxidative Defense Mechanisms - Maria Nawaz; Muhammad Yasin Ashraf; Ameer Khan; Fahim Nawaz (Journal of Soil Science and Plant Nutrition, 2021)

The nexus between meteorological parameters and COVID-19 pandemic: case of Islamabad, Pakistan - Abdul Rehman; Fatima Ashraf; Zeeshan Javed; Mudassar Hussain; Taimoor Hassan Farooq; Awais Shakoor; Sher Muhammad Shahzad (Environmental Sustainability, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Social vulnerability to seismic-tsunami hazards in district Gwadar, Balochistan, Pakistan - Amanullah Mengal; Katsuichiro Goda; Muhammad Ashraf; Ghulam Murtaza (Natural Hazards, 2021)

Production of a broad spectrum streptothricin like antibiotic from halotolerant Streptomyces fimbriatus isolate G1 associated with marine sediments - Neelma Ashraf; Andreas Bechthold; Munir A. Anwar; Muhammad A. Ghauri; Muhammad S. Anjum; Ali N. Khan; Kalsoom Akhtar; Shazia Khaliq (Folia Microbiologica, 2021)

Genome-wide analysis of ARF transcription factors reveals HcARF5 expression profile associated with the biosynthesis of β-ocimene synthase in Hedychium coronarium - Farhat Abbas; Yanguo Ke; Yiwei Zhou; Yunyi Yu; Muhammad Waseem; Umair Ashraf; Xinyue Li; Rangcai Yu; Yanping Fan (Plant Cell Reports, 2021)

RETRACTED ARTICLE: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Menadione sodium bisulfite alleviated chromium effects on wheat by regulating oxidative defense, chromium speciation, and ion homeostasis - Sajjad Hassan Askari; Muhammad Arslan Ashraf; Shafaqat Ali; Muhammad Rizwan; Rizwan Rasheed (Environmental Science and Pollution Research, 2021)

Silicon attenuates the negative effects of chromium stress in tomato plants by modifying antioxidant enzyme activities, ascorbate–glutathione cycle and glyoxalase system - Pravej Alam; Thamer H. Balawi; Fahad H. Altalayan; Ashraf Atef Hatamleh; Muhammad Ashraf; Parvaiz Ahmad (Acta Physiologiae Plantarum, 2021)

A Core Logging, Machine Learning and Geostatistical Modeling Interactive Approach for Subsurface Imaging of Lenticular Geobodies in a Clastic Depositional System, SE Pakistan - Umar Ashraf; Hucai Zhang; Aqsa Anees; Hassan Nasir Mangi; Muhammad Ali; Xiaonan Zhang; Muhammad Imraz; Saiq Shakeel Abbasi; Ayesha Abbas; Zaheen Ullah; Jar Ullah; Shucheng Tan (Natural Resources Research, 2021)

Advances in Salt Tolerance of Some Major Fiber Crops Through Classical and Advanced Biotechnological Tools: A Review - Nudrat Aisha Akram; Fahad Shafiq; Muhammad Ashraf; Muhammad Iqbal; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2021)

Sustainable management of cut flowers waste by activation and its application in wastewater treatment technology - Muhammad Ashraf Sabri; Taleb Hassan Ibrahim; Mustafa Ibrahim Khamis; Adriane Ludwick; Paul Nancarrow (Environmental Science and Pollution Research, 2021)

Estimation of data-driven streamflow predicting models using machine learning methods - Tanveer Ahmed Siddiqi; Saima Ashraf; Sadiq Ali Khan; Muhammad Jawed Iqbal (Arabian Journal of Geosciences, 2021)

Alleviation of cadmium stress by silicon nanoparticles during different phenological stages of Ujala wheat variety - Sumaira Thind; Iqbal Hussain; Rizwan Rasheed; Muhammad Arslan Ashraf; Abida Perveen; Allah Ditta; Saddam Hussain; Nighat Khalil; Zahid Ullah; Qaisar Mahmood (Arabian Journal of Geosciences, 2021)

Growth and physio-biochemical responses of maize ( Zea mays L.) to drought and heat stresses - Madiha Ayub; Muhammad Yasin Ashraf; Abida Kausar; Salman Saleem; Sumera Anwar; Volkan Altay; Munir Ozturk (Plant Biosystems, 2021)

Menadione sodium bisulphite regulates physiological and biochemical responses to lessen salinity effects on wheat (Triticum aestivum L.) - Ali Akbar; Muhammad Arslan Ashraf; Rizwan Rasheed; Shafaqat Ali; Muhammad Rizwan (Physiology and Molecular Biology of Plants, 2021)

The effects of some heavy metals on some fish species - Saba Naeem; Muhammad Ashraf; Masroor Ellahi Babar; Sana Zahoor; Shaukat Ali (Environmental Science and Pollution Research, 2021)

Micro-morphological response of some native dicotyledonous species to particulate pollutants emitted from stone crushing activities - Iftikhar Ahmad; Lubaba Shamsi; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Anum Javaid; Muhammad Asim Sultan (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2021)

Scalp Hair Metal Analysis Concerning DNA Damage in Welders of Peshawar Khyber Pakhtunkhwa Pakistan - Muhammad Khisroon; Ajmal Khan; Ashraf Ali Shah; Ihsan Ullah; Javeed Farooqi; Abid Ullah (Biological Trace Element Research, 2021)

Whole exome sequencing revealed novel variants in consanguineous Pakistani families with intellectual disability - Iqra Ghulam Rasool; Muhammad Yasir Zahoor; Muhammad Iqbal; Aftab Ahmad Anjum; Fatima Ashraf; Hafiz Qamar Abbas; Hafiz Muhammad Azhar Baig; Tariq Mahmood; Wasim Shehzad (Genes & Genomics, 2021)

Growth and Physiology of Maize (Zea mays L.) in a Nickel-Contaminated Soil and Phytoremediation Efficiency Using EDTA - Muhammad Imran Tipu; Muhammad Yasin Ashraf; Nadeem Sarwar; Muhammad Akhtar; Muhammad Rashid Shaheen; Sajjad Ali; Christos A. Damalas (Journal of Plant Growth Regulation, 2021)

Nitric Oxide is Required for Aminolevulinic Acid-Induced Salt Tolerance by Lowering Oxidative Stress in Maize (Zea mays) - Cengiz Kaya; Muhammad Ashraf (Journal of Plant Growth Regulation, 2021)

Chemical characterization and anti-arthritic appraisal of Monotheca buxifolia methanolic extract in Complete Freund’s Adjuvant-induced arthritis in Wistar rats - Muhammad Furqan Akhtar; Khushdil Khan; Ammara Saleem; Mirza Muhammad Faran Ashraf Baig; Azhar Rasul; Mohamed M. Abdel-Daim (Inflammopharmacology, 2021)

Benzilydene and thiourea derivatives as new classes of carbonic anhydrase inhibitors: an in vitro and molecular docking study - Shama Qaiser; Mohammad S. Mubarak; Sajda Ashraf; Muhammad Saleem; Zaheer Ul-Haq; Muhammad Safdar; Abdur Rauf; Tareq Abu-Izneid; Malak I. Qadri; Aneela Maalik (Medicinal Chemistry Research, 2021)

Relative Effectiveness of Phosphorus and Potassium Along with Compost and Organic Acids on Maize Crop Grown in Calcareous Soil: a Multivariate Analysis - Saira Tabbasum; Muhammad Akhtar; Nadeem Sarwar; Muhammad Imran Tipu; Wasiq Ikram; Arooba Ashraf; Amjad Ejaz; Behzad Murtaza; Muhammad Rizwan Khan (Journal of Soil Science and Plant Nutrition, 2021)

Treatment of Wilms’ nephroblastoma cancer cells via EGFR targeting of dactinomycin loaded DNA-nanowires - Mirza Muhammad Faran Ashraf Baig; Chengfei Zhang; Muhammad Furqan Akhtar; Ammara Saleem; Naveed Nisar (Journal of Pharmaceutical Investigation, 2021)

Sustainability of Palm Biodiesel in Transportation: a Review on Biofuel Standard, Policy and International Collaboration Between Malaysia and Colombia - Mohd Nur Ashraf Mohd Yusoff; Nurin Wahidah Mohd Zulkifli; Nazatul Liana Sukiman; Ong Hwai Chyuan; Masjuki Haji Hassan; Muhammad Harith Hasnul; Muhammad Syahir Amzar Zulkifli; Muhammad Mujtaba Abbas; Muhammad Zulfattah Zakaria (BioEnergy Research, 2021)

Sedimentological evolution and diagenesis of lower Eocene limestones, the Sinn El-Kaddab Plateau, the southern extent of the Tethys Sea in Egypt - Kamal Abou Elmagd; Ashraf Emam; Muhammad Hazem; Maher I. Elsoughier (Arabian Journal of Geosciences, 2021)

Survival Strategies in Khavi Grass [Cymbopogon jwarancusa (Jones) Schult.] Colonizing Hot Hypersaline and Arid Environments - Sana Fatima; Mansoor Hameed; Nargis Naz; Syed Mohsan Raza Shah; Mehwish Naseer; Muhammad Sajid Aqeel Ahmad; Muheammad Ashraf; Farooq Ahmad; Sangam Khalil; Iftikhar Ahmad (Water, Air, & Soil Pollution, 2021)

Efficient water allocation strategy to overcoming water inequity crisis for sustainability of agricultural land: a case of Southern Punjab, Pakistan - Ahsan Maqbool; Muhammad Adnan Ashraf; Abdul Khaliq; Wang Hui; Muhammad Saeed (Stochastic Environmental Research and Risk Assessment, 2021)

Influence of silicon and chitosan on growth and physiological attributes of maize in a saline field - Hafiza Samra Younas; Muhammad Abid; Muhammad Shaaban; Muhammad Ashraf (Physiology and Molecular Biology of Plants, 2021)

Lead (Pb)-resistant bacteria inhibit Pb accumulation in dill (Anethum graveolens L.) by improving biochemical, physiological, and antioxidant enzyme response of plants - Akram Rahbari; Hamideh Fatemi; Behrooz Esmaiel Pour; Muhammad Rizwan; Ali-Ashraf Soltani (Environmental Science and Pollution Research, 2021)

Streamflow Variations in Monthly, Seasonal, Annual and Extreme Values Using Mann-Kendall, Spearmen’s Rho and Innovative Trend Analysis - Muhammad S. Ashraf; Ijaz Ahmad; Noor M. Khan; Fan Zhang; Ahmed Bilal; Jiali Guo (Water Resources Management, 2021)

Bioregulators: unlocking their potential role in regulation of the plant oxidative defense system - Faisal Zulfiqar; Muhammad Ashraf (Plant Molecular Biology, 2021)

A Report on Molecular Detection and Phylogenetic Evaluation of Anaplasma marginale in Ticks and Blood Samples Collected from Cattle in District Layyah in Punjab (Pakistan) - Sehrish Ashraf; Asia Parveen; Mian Muhammad Awais; Quratulane Gillani; Munir Aktas; Sezayi Ozubek; Furhan Iqbal (Current Microbiology, 2021)

Influence of Different Organic Manures and Their Combinations on Productivity and Quality of Bread Wheat - Nauman Ali; Muhammad Naeem Khan; Muhammad Saeed Ashraf; Sobia Ijaz; Hafiz Saeed-ur-Rehman; Muhammad Abdullah; Noor Ahmad; Hafiz Muhammad Akram; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2020)

24-Epibrassinolide Alleviates the Injurious Effects of Cr(VI) Toxicity in Tomato Plants: Insights into Growth, Physio-Biochemical Attributes, Antioxidant Activity and Regulation of Ascorbate–Glutathione and Glyoxalase Cycles - Sumira Jan; Ali Noman; Cengiz Kaya; Muhammad Ashraf; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2020)

Molecular identification of sugarcane black bug (Cavelarius excavates) from Pakistan using cytochrome C oxidase I (COI) gene as DNA barcode - Khadim Hussain; Kamran Rashid; Faisal Hafeez; Ikrma Amad; Muhammad Ashraf (International Journal of Tropical Insect Science, 2020)

Spatially analyzing food consumption inequalities using GIS with disaggregated data from Punjab, Pakistan. - Sana Khushi; Sajid Rashid Ahmad; Ather Ashraf; Muhammad Imran (Food Security, 2020)

Exploring the potential of Sentinel-2A satellite data for aboveground biomass estimation in fragmented Himalayan subtropical pine forest - Mobiishir Riaz Khan; Iftikhar Ahmad Khan; Muhammad Hasan Ali Baig; Zheng-jia Liu; Muhammad Irfan Ashraf (Journal of Mountain Science, 2020)

Biogeochemical transformation of greenhouse gas emissions from terrestrial to atmospheric environment and potential feedback to climate forcing - Awais Shakoor; Fatima Ashraf; Saba Shakoor; Adnan Mustafa; Abdul Rehman; Muhammad Mohsin Altaf (Environmental Science and Pollution Research, 2020)

Dietary intake assessment of pyrethroid residues from okra and eggplant grown in peri-urban areas of Punjab, Pakistan - Adnan Amjad; Muhammad Atif Randhawa; Muhammad Sameem Javed; Zafarullah Muhammad; Mussawar Ashraf; Zulfiqar Ahmad; Shamas Murtaza (Environmental Science and Pollution Research, 2020)

Predicting the non-carcinogenic health hazards associated with emissions from developing coal-fired power plants in Payra, Bangladesh - Mashiat Hossain; Tanvir Ahmed; Muhammad Ashraf Ali (Air Quality, Atmosphere & Health, 2020)

Single tube multiplex PCR assay for the identification of banned meat species - Memoona Iqbal; Muhammad Sulyman Saleem; Muhammad Imran; Waseem Ahmad Khan; Kamran Ashraf; M. Yasir Zahoor; Imran Rashid; Habib-Ur Rehman; Asif Nadeem; Saadat Ali; Sarwat Naz; Wasim Shehzad (Food Additives & Contaminants Part B-Surveillance, 2020)

Environmental toxicology and biogeochemistry of ecosystems - Muhammad Aqeel Ashraf; Muhammad Faheem (Environmental Science and Pollution Research, 2020)

Bacterial-mediated synthesis of silver nanoparticles and their significant effect against pathogens - Saira Saeed; Atia Iqbal; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2020)

Foliage application and seed priming with nitric oxide causes mitigation of salinity-induced metabolic adversaries in broccoli (Brassica oleracea L.) plants - Nudrat Aisha Akram; Naima Hafeez; Muhammad Farid-ul-Haq; Abrar Ahmad; Muhammad Sadiq; Muhammad Ashraf (Acta Physiologiae Plantarum, 2020)

Pharmacokinetic Advantage of ASD Device Promote Drug Absorption through the Epicardium - Reyaj Mikrani; Cunyu Li; Muhammad Naveed; Cuican Li; Mirza Muhammad Faran Ashraf Baig; Qin Zhang; Yue Wang; Juanjuan Peng; Lingzhi Zhao; Xiaohui Zhou (Pharmaceutical Research, 2020)

Sodium Exclusion Affects Seed Yield and Physiological Traits of Wheat Genotypes Grown Under Salt Stress - Muhammad Sohail Saddiq; Irfan Afzal; Shahzad M.A. Basra; Shahid Iqbal; Muhammad Ashraf (Journal of Soil Science and Plant Nutrition, 2020)

Interactive effects of chitosan and cadmium on growth, secondary metabolism, oxidative defense, and element uptake in pea (Pisum sativum L.) - Rizwan Rasheed; Muhammad Arslan Ashraf; Asma Arshad; Muhammad Iqbal; Iqbal Hussain (Arabian Journal of Geosciences, 2020)

Biological and phytochemical studies on Capparis decidua (Forssk) Edgew from Cholistan desert - Shazia Anjum; Muhammad Asif; Kashaf Zia; Bakhat Jahan; Muhammad Ashraf; Shafqat Hussain; Muhammad Qasim Hayat; Muhammad Raza Shah; Muhammad Nawaz Tahir (Natural Product Research, 2020)

Soil and microbial biomass stoichiometry regulate soil organic carbon and nitrogen mineralization in rice-wheat rotation subjected to long-term fertilization - Muhammad Nadeem Ashraf; Cheng Hu; Lei Wu; Yinghua Duan; Wenju Zhang; Tariq Aziz; Andong Cai; Muhammad Mohsin Abrar; Minggang Xu (Journal of Soils and Sediments, 2020)

Spatio-temporal assessment and climatology of atmospheric organic carbon over Pakistan - Muhammad Zaffar Hashmi; Khadija Ashraf; Shahzada Adnan; Shuhong Wang; Siwatt Pongpiachan; Xiaomei Su; Zulkfil Ahmed (Arabian Journal of Geosciences, 2020)

Silybum marianum (milk thistle) improves vancomycin induced nephrotoxicity by downregulating apoptosis - Naila Malkani; Ammara Naeem; Farah Ijaz; Sidra Mumtaz; Saima Ashraf; Muhammad Imran Sohail (Molecular Biology Reports, 2020)

Citric acid enhanced phytoextraction of nickel (Ni) and alleviate Mentha piperita (L.) from Ni-induced physiological and biochemical damages - Kashaf Ul Khair; Mujahid Farid; Umair Ashraf; Muhammad Zubair; Muhammad Rizwan; Sheharyaar Farid; Hafiz Khuzama Ishaq; Usman Iftikhar; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

Effects of Silicon and Phosphatic Fertilization on Rice Yield and Soil Fertility - Liying Wang; Umair Ashraf; Chunrong Chang; Muhammad Abrar; Xiong Cheng (Journal of Soil Science and Plant Nutrition, 2020)

Mitigation of Arsenic Toxicity in Wheat by the Exogenously Applied Salicylic Acid, 24-Epi-Brassinolide and Silicon - Kobra Maghsoudi; Mohammad Javad Arvin; Muhammad Ashraf (Journal of Soil Science and Plant Nutrition, 2020)

Integrated Effect of Algal Biochar and Plant Growth Promoting Rhizobacteria on Physiology and Growth of Maize Under Deficit Irrigations - Naseer Ullah; Allah Ditta; Azeem Khalid; Sajid Mehmood; Muhammad Shahid Rizwan; Muhammad Ashraf; Fathia Mubeen; Muhammad Imtiaz; Muhammad Mazhar Iqbal (Journal of Soil Science and Plant Nutrition, 2020)

Synthesis of Ligand Functionalized ErbB-3 Targeted Novel DNA Nano-Threads Loaded with the Low Dose of Doxorubicin for Efficient In Vitro Evaluation of the Resistant Anti-Cancer Activity - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Anam Ahsan; Mehreen Jabeen; Muhammad Asim Farooq; Reyaj Mikrani; Muhammad Abbas; Muhammad Naveed; Said Abasse Kassim; Faisal Raza; Afzal Ahmed Dar; Muhammad Tayyab Ansari (Pharmaceutical Research, 2020)

Implication of Physiological and Biochemical Variables of Prognostic Importance in Lead Exposed Subjects - Arif Malik; Muhammad Abdul Basit Ashraf; Muhammad Waqas Khan; Ayesha Zahid; Hassan Shafique; Sulayman Waquar; Siew Hua Gan; Muhammad Ashraf (Archives of Environmental Contamination and Toxicology, 2020)

Geotechnical properties of Lower Eocene limestones, Sinn El-Kaddab Plateau, southwest of Aswan, Egypt - Kamal Abou Elmagd; Ashraf Emam; Muhammad Hazem (Arabian Journal of Geosciences, 2020)

Exogenously applied 5-aminolevulinic acid modulates growth, secondary metabolism and oxidative defense in sunflower under water deficit stress - Rizwan Rasheed; Humaira Yasmeen; Iqbal Hussain; Muhammad Iqbal; Muhammad Arslan Ashraf; Abida Parveen (Physiology and Molecular Biology of Plants, 2020)

Foliar applied fullerol differentially improves salt tolerance in wheat through ion compartmentalization, osmotic adjustments and regulation of enzymatic antioxidants - Fahad Shafiq; Muhammad Iqbal; Muhammad Arslan Ashraf; Muhammad Ali (Physiology and Molecular Biology of Plants, 2020)

Organochlorine pesticides in the surrounding soils of POPs destruction facility: source fingerprinting, human health, and ecological risks assessment - Syeda Nazish Ali; Mujtaba Baqar; Mehvish Mumtaz; Uzma Ashraf; Muhammad Naveed Anwar; Abdul Qadir; Sajid Rashid Ahmad; Abdul-Sattar Nizami; Huang Jun (Environmental Science and Pollution Research, 2020)

Estimation of forest carbon stocks in temperate and subtropical mountain systems of Pakistan: implications for REDD+ and climate change mitigation - Anwar Ali; Muhammad Irfan Ashraf; Saeed Gulzar; Muhammad Akmal (Environmental Monitoring and Assessment, 2020)

Application of GIS/RS for monitoring of the ecological environment in a coastal zone - Rui Xie; Haihong Xiao; Muhammad Aqeel Ashraf (Arabian Journal of Geosciences, 2020)

First Report Regarding the Simultaneous Molecular Detection of Anaplasma marginale and Theileria annulata in Equine Blood Samples Collected from Southern Punjab in Pakistan - Muhammad Asif; Asia Parveen; Sehrish Ashraf; Mureed Hussain; Munir Aktas; Sezayi Ozubek; Rehan Sadiq Shaikh; Furhan Iqbal (Acta Parasitologica, 2020)

Datura suaveolens and Verbena tenuisecta mediated silver nanoparticles, their photodynamic cytotoxic and antimicrobial evaluation - Ahsan Ashraf; Nighat Fatima; Irum Shahzadi; Hina Tariq; Anam Shahzadi; Muhammad Arfat Yameen; Jamshed Iqbal; Muhammad Rafi (World Journal of Microbiology and Biotechnology, 2020)

Lethal and parasitism effects of selected novel pesticides on adult Trichogramma chilonis (Hymenoptera: Trichogrammatidae) - Muhammad Ashraf Khan (Journal of Plant Diseases and Protection, 2020)

Spatiotemporal variability in spate irrigation systems in Khirthar National Range, Sindh, Pakistan (case study) - Abdul Ghani Soomro; Muhammad Munir Babar; Muhammad Arshad; Anila Memon; Babar Naeem; Arshad Ashraf (Acta Geophysica, 2020)

Estimation of groundwater potential using GIS modeling in Kohistan region Jamshoro district, Southern Indus basin, Sindh, Pakistan (a case study) - Aneela Memon; Kamran Ansari; Abdul Ghani Soomro; Muhammad Afzal Jamali; Babar Naeem; Arshad Ashraf (Acta Geophysica, 2020)

Assessing Drug Release from Manipulated Abuse Deterrent Formulations - Xin Feng; Ahmed Zidan; Nahid S. Kamal; Xiaoming Xu; Dajun Sun; Ross Walenga; Heather Boyce; Celia N. Cruz; Muhammad Ashraf (AAPS PharmSciTech, 2020)

Osmoprotection in plants under abiotic stresses: new insights into a classical phenomenon - Faisal Zulfiqar; Nudrat Aisha Akram; Muhammad Ashraf (Planta, 2020)

Response of growth, antioxidant enzymes and root exudates production towards As stress in Pteris vittata and in Astragalus sinicus colonized by arbuscular mycorrhizal fungi - Liu Yizhu; Muhammad Imtiaz; Allah Ditta; Muhammad Shahid Rizwan; Muhammad Ashraf; Sajid Mehmood; Omar Aziz; Fathia Mubeen; Muhammad Ali; Nosheen Noor Elahi; Raina Ijaz; Sha Lele; et al. (Environmental Science and Pollution Research, 2020)

Land-use change in plateau lake basin and its impact on urban ecological security - Zijiang Yang; Xiong He; Muhammad Aqeel Ashraf (Arabian Journal of Geosciences, 2020)

The application of the intelligent algorithm in the prevention and early warning of mountain mass landslide disaster - Yuan Yan; Muhammad Aqeel Ashraf (Arabian Journal of Geosciences, 2020)

Effective plant-endophyte interplay can improve the cadmium hyperaccumulation in Brachiaria mutica - Muhammad Tayyab Ahsan; Razia Tahseen; Abida Ashraf; Abid Mahmood; Muhammad Najam-ul-haq; Muhammad Arslan; Muhammad Afzal (World Journal of Microbiology and Biotechnology, 2019)

Genome Wide Identification and Expression Profiles of TALE Genes in Pineapple (Ananas comosus L) - Hina Ali; Yanhui Liu; Syed Muhammad Azam; Imran Ali; Umair Ali; Weimin Li; Hafiza Javaria Ashraf; Yang Jie; Stefan Olsson; Yuan Qin (Tropical Plant Biology, 2019)

Effect of Methyl Jasmonate and Salicylic Acid on In Vitro Growth, Stevioside Production, and Oxidative Defense System in Stevia rebaudiana - Sajjad Moharramnejad; Amirali Taheri Azam; Jaber Panahandeh; Zahra Dehghanian; Muhammad Ashraf (Sugar Tech, 2019)

Seed Pre-treatment with Polyhydroxy Fullerene Nanoparticles Confer Salt Tolerance in Wheat Through Upregulation of H2O2 Neutralizing Enzymes and Phosphorus Uptake - Fahad Shafiq; Muhammad Iqbal; Muhammad Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2019)

Alpha-Tocopherol-Induced Regulation of Growth and Metabolism in Plants Under Non-stress and Stress Conditions - Muhammad Sadiq; Nudrat Aisha Akram; Muhammad Ashraf; Fahad Al-Qurainy; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2019)

Recent advances in the delivery of disulfiram: a critical analysis of promising approaches to improve its pharmacokinetic profile and anticancer efficacy - Muhammad Asim Farooq; Md Aquib; Daulat Haleem Khan; Zahid Hussain; Anam Ahsan; Mirza Muhammad Faran Ashraf Baig; Dickson Pius Wande; Muhammad Masood Ahmad; Hafiz Muhammad Ahsan; Jiang Jiajie; Bo Wang (DARU Journal of Pharmaceutical Sciences, 2019)

Exogenous menadione sodium bisulfite mitigates specific ion toxicity and oxidative damage in salinity-stressed okra (Abelmoschus esculentus Moench) - Muhammad Arslan Ashraf; Hafiza Farhat Asma; Muhammad Iqbal (Acta Physiologiae Plantarum, 2019)

Assessment of groundwater potential through vertical electrical sounding at Haji Rehmatullah Palari village, Nooriabad - Asadullah Soomro; Abdul Latif Qureshi; Muhammad Afzal Jamali; Arshad Ashraf; Asfand Yar Wali Arain (Acta Geophysica, 2019)

An Investigation into the Accumulation of Air Borne Trace Metals in the Lungs of Common Myna Acridotheres tristis and Bank Myna Acridotheres ginginianus Captured from Urban and Semi Urban Areas of Lahore and Pattoki, Pakistan - Nida Irshad; Safdar Sidra; Arshad Javid; Sitara Ashraf; Muhammad Rizwan Ullah; Rafia Zafar (Bulletin of Environmental Contamination and Toxicology, 2019)

Exogenously applied proline induced changes in key anatomical features and physio-biochemical attributes in water stressed oat (Avena sativa L.) plants - Rehmana Ghafoor; Nudrat Aisha Akram; Muhammad Rashid; Muhammad Ashraf; Muhammad Iqbal; Zhang Lixin (Physiology and Molecular Biology of Plants, 2019)

Thiourea-mediated Nitric Oxide Production Enhances Tolerance to Boron Toxicity by Reducing Oxidative Stress in Bread Wheat (Triticum aestivum L.) and Durum Wheat (Triticum durum Desf.) Plants - Cengiz Kaya; Ali Sarioğlu; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2019)

Characterization of recombinant endo-1,4-β-xylanase of Bacillus halodurans C-125 and rational identification of hot spot amino acid residues responsible for enhancing thermostability by an in-silico approach - Malik Siddique Mahmood; Faiz Rasul; Mahjabeen Saleem; Amber Afroz; Muhammad Faheem Malik; Naeem Mehmood Ashraf; Umar Rashid; Shumaila Naz; Nadia Zeeshan (Molecular Biology Reports, 2019)

Assessment of nematodes in Punjab Urial (Ovis vignei punjabiensis) population in Kalabagh Game Reserve: development of a DNA barcode approach - Amna Arshad Bajwa; Jordan Patrick Cuff; Muhammad Imran; Saher Islam; Riffat Mansha; Kamran Ashraf; Arman Khan; Muhammad Imran Rashid; Muhammad Yasir Zahoor; Waseem Ahmad Khan; Habib Ur Rehman; Asif Nadeem; et al. (European Journal of Wildlife Research, 2019)

Effect of Formulation Variables on the Nasal Permeability and Stability of Naloxone Intranasal Formulations - Hao-Jui Hsu; Yang Yang; Venkateswara Pavuluri; Ciby Abraham; Suresh Babu Naraharisetti; Muhammad Ashraf; Manar Al-Ghabeish (AAPS PharmSciTech, 2019)

Evaluation of Abuse-Deterrent Characteristics of Tablets Prepared via Hot-Melt Extrusion - Xiaoming Xu; Akhtar Siddiqui; Charudharshini Srinivasan; Adil Mohammad; Ziyaur Rahman; Maxwell Korang-Yeboah; Xin Feng; Mansoor Khan; Muhammad Ashraf (AAPS PharmSciTech, 2019)

Trehalose: A Key Organic Osmolyte Effectively Involved in Plant Abiotic Stress Tolerance - Firdos Kosar; Nudrat Aisha Akram; Muhammad Sadiq; Fahad Al-Qurainy; Muhammad Ashraf (Journal of Plant Growth Regulation, 2019)

Over 100 years of faults interaction, stress accumulation, and creeping implications, on Chaman Fault System, Pakistan - Muhammad Shahid Riaz; Shan Bin; Shahid Naeem; Wang Kai; Zujun Xie; Syed Mushhad M. Gilani; Umer Ashraf (International Journal of Earth Sciences, 2019)

Arsenic fractionation and its impact on physiological behavior of sunflower (Helianthus annuus L.) in three texturally different soils under alkaline calcareous conditions - Muhammad Awais Piracha; Muhammad Ashraf; Abid Niaz (Environmental Science and Pollution Research, 2019)

Biomarkers of pyrethroid toxicity in fish - Sana Ullah; Zhongqiu Li; Amina Zuberi; Muhammad Zain Ul Arifeen; Mirza Muhammad Faran Ashraf Baig (Environmental Chemistry Letters, 2019)

Sustaining life on earth system through clean air, pure water, and fertile soil - Muhammad Aqeel Ashraf; Marlia Mohd Hanafiah (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: Environmental factors affecting the frequency of road traffic accidents: a case study of sub-urban area of Pakistan - Hafiz Mohkum Hammad; Muhammad Ashraf; Farhat Abbas; Hafiz Faiq Bakhat; Saeed A. Qaisrani; Muhammad Mubeen; Shah Fahad; Muhammad Awais (Environmental Science and Pollution Research, 2019)

Evaluation of engine performance and exhaust emission characteristics in a diesel engine using isobutanol— Calophyllum inophyllum biodiesel—diesel ternary blends - Azham Alwi; Nurin Wahidah Zulkifli; Nazatul Liana Sukiman; Ashraf Yusoff; Zulfattah Zakaria; Muhammad Jamshaid; Muhammad Harith Hasnul; Muhammad Syahir Amzar (Environmental Science and Pollution Research, 2019)

Roles of potential plant hormones and transcription factors in controlling leaf senescence and drought tolerance - Sumira Jan; Nazia Abbas; Muhammad Ashraf; Parvaiz Ahmad (Protoplasma, 2019)

The mechanism of hydrogen sulfide mitigation of iron deficiency-induced chlorosis in strawberry (Fragaria × ananassa) plants - Cengiz Kaya; Muhammad Ashraf (Protoplasma, 2019)

Renal toxicity of heavy metals (cadmium and mercury) and their amelioration with ascorbic acid in rabbits - Shaukat Ali; Sidra Hussain; Rida Khan; Shumaila Mumtaz; Nasra Ashraf; Saiqa Andleeb; Hafiz Abdullah Shakir; Hafiz Muhammad Tahir; Muhammad Khalil Ahmad Khan; Mazhar Ulhaq (Environmental Science and Pollution Research, 2019)

Synthesis and applications of nano-TiO2: a review - Muhammad Tayyab Noman; Muhammad Azeem Ashraf; Azam Ali (Environmental Science and Pollution Research, 2019)

Groundwater investigation through vertical electrical sounding at hilly area from Nooriabad toward Karachi - Asadullah Soomro; Abdul Latif Qureshi; Muhammad Afzal Jamali; Arshad Ashraf (Acta Geophysica, 2019)

Ni tolerance and its distinguished amelioration by chelating agents is reflected in root radius of B. napus cultivars - Humera Nawaz; Stephan Manhalter; Aamir Ali; Muhammad Yasin Ashraf; Ingeborg Lang (Protoplasma, 2019)

Brassinosteroids Regulate Growth in Plants Under Stressful Environments and Crosstalk with Other Potential Phytohormones - Mohammad Abass Ahanger; Muhammad Ashraf; Andrzej Bajguz; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2018)

Epibrassinolide Application Regulates Some Key Physio-biochemical Attributes As Well As Oxidative Defense System in Maize Plants Grown Under Saline Stress - Cengiz Kaya; Salih Aydemir; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2018)

Kinetin and Indole Acetic Acid Promote Antioxidant Defense System and Reduce Oxidative Stress in Maize (Zea mays L.) Plants Grown at Boron Toxicity - Cengiz Kaya; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2018)

Bioremediation of tannery effluent by Cr- and salt-tolerant bacterial strains - Sobia Ashraf; Muhammad Naveed; Muhammad Afzal; Sana Ashraf; Khadeeja Rehman; Azhar Hussain; Zahir Ahmad Zahir (Environmental Monitoring and Assessment, 2018)

Effect of exogenous nitric oxide on sulfur and nitrate assimilation pathway enzymes in maize (Zea mays L.) under drought stress - Sadia Majeed; Fahim Nawaz; Muhammad Naeem; Muhammad Yasin Ashraf (Acta Physiologiae Plantarum, 2018)

Effect of salinity on osmotic adjustment, proline accumulation and possible role of ornithine-δ-aminotransferase in proline biosynthesis in Cakile maritima - Dorsaf Hmidi; Chedly Abdelly; Habib-ur-Rehman Athar; Muhammad Ashraf; Dorsaf Messedi (Physiology and Molecular Biology of Plants, 2018)

Synthesis, in vitro $$α $$ α -glucosidase inhibitory activity, and in silico study of (E)-thiosemicarbazones and (E)-2-(2-(arylmethylene)hydrazinyl)-4-arylthiazole derivatives - Muhammad Ali; Khalid Mohammed Khan; Uzma Salar; Mohammed Ashraf; Muhammad Taha; Abdul Wadood; Sujhla Hamid; Muhammad Riaz; Basharat Ali; Shahbaz Shamim; Farman Ali; Shahnaz Perveen (Molecular Diversity, 2018)

Ultrasonic seed treatment improved physiological and yield traits of rice under lead toxicity - Gangshun Rao; Umair Ashraf; Suihua Huang; Siren Cheng; Muhammad Abrar; Zhaowen Mo; Shenggang Pan; Xiangru Tang (Environmental Science and Pollution Research, 2018)

Behavioral activity patterns of adult and juvenile Greater Flamingos (Phoenicopterus roseus) with alteration of climatic pattern at Uchalli Lake, Punjab, Pakistan - Shabana Naz; Arnab Tanveer; Muhammad Abrar; Asma Ashraf (Environmental Science and Pollution Research, 2018)

Glutamic acid assisted phyto-management of silver-contaminated soils through sunflower; physiological and biochemical response - Mujahid Farid; Shafaqat Ali; Muhammad Zubair; Rashid Saeed; Muhammad Rizwan; Rasham Sallah-Ud-Din; Ahmad Azam; Rehman Ashraf; Wasim Ashraf (Environmental Science and Pollution Research, 2018)

Diagnosis of bovine mastitis: from laboratory to farm - Aqeela Ashraf; Muhammad Imran (Tropical Animal Health and Production, 2018)

Use of Eucalyptus camaldulensis as Biosorbent for Lead Removal from Aqueous Solution - Muhammad Ashraf Sabri; Taleb Hassan Ibrahim; Mustafa Ibrahim Khamis; Sameer Al-Asheh; Muhammad Faheem Hassan (International Journal of Environmental Research, 2018)

Correction to: Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Exogenously applied zinc and copper mitigate salinity effect in maize (Zea mays L.) by improving key physiological and biochemical attributes - Muhammad Naveed Iqbal; Rizwan Rasheed; Muhammad Yasin Ashraf; Muhammad Arslan Ashraf; Iqbal Hussain (Environmental Science and Pollution Research, 2018)

Activity of acetylcholinesterase and acid and alkaline phosphatases in different insecticide-treated Helicoverpa armigera (Hübner) - Muhammad Bilal; Shoaib Freed; Muhammad Zubair Ashraf; Syed Muhammad Zaka; Muhammad Bismillah Khan (Environmental Science and Pollution Research, 2018)

Geochemical assessment of Paleocene limestones of Sinn El-Kaddab Plateau, South Western Desert of Egypt, for industrial uses - Kamal Abou Elmagd; Ashraf Emam; Mohamed Wahbi Ali-Bik; Muhammad Hazem (Arabian Journal of Geosciences, 2018)

Impact of exogenously applied tocopherol on some key physio-biochemical and yield attributes in mungbean [Vigna radiata (L.) Wilczek] under limited irrigation regimes - Muhammad Sadiq; Nudrat Aisha Akram; Muhammad Ashraf (Acta Physiologiae Plantarum, 2018)

Cascades of Ionic and Molecular Networks Involved in Expression of Genes Underpin Salinity Tolerance in Cotton - Muhammad Ali Abid; Chengzhen Liang; Waqas Malik; Zhigang Meng; Zhu Tao; Zhaoghong Meng; Javaria Ashraf; Sandui Guo; Rui Zhang (Journal of Plant Growth Regulation, 2018)

Effectiveness of an improved form of insecticide-based diatomaceous earth against four stored grain pests on different grain commodities - Nadia Saeed; Muhammad Farooq; Muhammad Shakeel; Misbah Ashraf (Environmental Science and Pollution Research, 2018)

Development and validation of a loop-mediated isothermal amplification assay for the detection of Mycoplasma bovis in mastitic milk - Aqeela Ashraf; Muhammad Imran; Tahir Yaqub; Muhammad Tayyab; Wasim Shehzad; Claro N. Mingala; Yung-Fu Chang (Folia Microbiologica, 2018)

Hydrogen sulfide regulates the levels of key metabolites and antioxidant defense system to counteract oxidative stress in pepper (Capsicum annuum L.) plants exposed to high zinc regime - Cengiz Kaya; Muhammad Ashraf; Nudrat Aisha Akram (Environmental Science and Pollution Research, 2018)

Compatible above-ground biomass equations and carbon stock estimation for small diameter Turkish pine (Pinus brutia Ten.) - Oytun Emre Sakici; Omer Kucuk; Muhammad Irfan Ashraf (Environmental Monitoring and Assessment, 2018)

Prediction of river bank erosion and protection works in a reach of Chenab River, Pakistan - Muhammad Ashraf; Abdul Sattar Shakir (Arabian Journal of Geosciences, 2018)

Modification of Osmolytes and Antioxidant Enzymes by 24-Epibrassinolide in Chickpea Seedlings Under Mercury (Hg) Toxicity - Parvaiz Ahmad; Mohammad Abass Ahanger; Dilfuza Egamberdieva; Pravej Alam; Mohammed Nasser Alyemeni; Muhammad Ashraf (Journal of Plant Growth Regulation, 2018)

Association of textile industry effluent with mutagenicity and its toxic health implications upon acute and sub-chronic exposure - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Mohammad Saleem; Ghulam Mustafa; Moneeb Ashraf; Ammara Saleem; Bushra Akhtar (Environmental Monitoring and Assessment, 2018)

Immunomodulatory and therapeutic role of Cinnamomum verum extracts in collagen-induced arthritic BALB/c mice - Mirza Muhammad Fahd Qadir; Attya Bhatti; Muhammad Usman Ashraf; Mansur Abdullah Sandhu; Sidrah Anjum; Peter John (Inflammopharmacology, 2018)

Lead Concentrations in Soils and Some Wild Plant Species Along Two Busy Roads in Pakistan - Noreen Khalid; Mumtaz Hussain; Hillary S. Young; Muhammad Ashraf; Mansoor Hameed; Rashid Ahmad (Bulletin of Environmental Contamination and Toxicology, 2018)

PAAN135, a novel rhizospheric fungus associated with Cholistan desert grass Panicum antidotale, is a species of Saccharomycetales and a new source of cyclo-L-prolylglycine diketopiperazine - Faiz-ul-Hassan Nasim; Adeela Naureen; Muhammad Saleem; Naheed Riaz; Muhammad Shafiq Choudhary; Muhammad Ashraf (Symbiosis, 2018)

Aminolevulinic acid and nitric oxide regulate oxidative defense and secondary metabolisms in canola (Brassica napus L.) under drought stress - Nudrat Aisha Akram; Majid Iqbal; Atta Muhammad; Muhammad Ashraf; Fahad Al-Qurainy; Sidra Shafiq (Protoplasma, 2018)

A Brief Review on Fluorescent Copper Sensor Based on Conjugated Organic Dyes - Muhammad Saleem; Muhammad Rafiq; Muhammad Hanif; Muhammad Ashraf Shaheen; Sung-Yum Seo (Journal of Fluorescence, 2018)

Pcal_0632, a phosphorylating glyceraldehyde-3-phosphate dehydrogenase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2018)

Application of Optical Coherence Tomography Freeze-Drying Microscopy for Designing Lyophilization Process and Its Impact on Process Efficiency and Product Quality - Maxwell Korang-Yeboah; Charudharshini Srinivasan; Akhtar Siddiqui; David Awotwe-Otoo; Celia N. Cruz; Ashraf Muhammad (AAPS PharmSciTech, 2018)

Role of circulatory microRNAs in the pathogenesis of hepatitis C virus - Iqra Almas; Samia Afzal; Muhammad Idrees; Muhammad Usman Ashraf; Iram Amin; Muhammad Shahid; Khadija Zahid; Sadia Zahid (VirusDisease, 2017)

Influence of entomopathogenic fungus, Metarhizium anisopliae, alone and in combination with diatomaceous earth and thiamethoxam on mortality, progeny production, mycosis, and sporulation of the stored grain insect pests - Misbah Ashraf; Muhammad Farooq; Muhammad Shakeel; Naima Din; Shahbaz Hussain; Nadia Saeed; Qaiser Shakeel; Nasir Ahmed Rajput (Environmental Science and Pollution Research, 2017)

Basic leucine zipper domain transcription factors: the vanguards in plant immunity - Ali Noman; Zhiqin Liu; Muhammad Aqeel; Madiha Zainab; Muhammad Ifnan Khan; Ansar Hussain; Muhammad Furqan Ashraf; Xia Li; Yahong Weng; Shuilin He (Biotechnology Letters, 2017)

Phosphate-arsenate relations to affect arsenic concentration in plant tissues, growth, and antioxidant efficiency of sunflower (Helianthus annuus L.) under arsenic stress - Waqas Azeem; Muhammad Ashraf; Sher Muhammad Shahzad; Muhammad Imtiaz; Mumtaz Akhtar; Muhammad Shahid Rizwan (Environmental Science and Pollution Research, 2017)

Pcal_1311, an alcohol dehydrogenase homologue from Pyrobaculum calidifontis, displays NADH-dependent high aldehyde reductase activity - Raza Ashraf; Naeem Rashid; Tamotsu Kanai; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Recent advances in assessment on clear water, soil and air - Muhammad Aqeel Ashraf; Marlia Mohd Hanfiah (Environmental Science and Pollution Research, 2017)

The fate and transport of arsenic species in the aquatic ecosystem: a case study on Bestari Jaya, Peninsular Malaysia - Suzanne Christine Aboudi Mana; Ng Tham Fatt; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Chemical speciation and bioavailability of rare earth elements (REEs) in the ecosystem: a review - Aysha Masood Khan; Nor Kartini Abu Bakar; Ahmad Farid Abu Bakar; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Evolutionary insights into the fusion protein of Newcastle disease virus isolated from vaccinated chickens in 2016 in Egypt - Ahmed Orabi; Ashraf Hussein; Ayman A. Saleh; Mohammed Abu El-Magd; Muhammad Munir (Archives of Virology, 2017)

Using geographical information systems to assess groundwater contamination from arsenic and related diseases based on survey data in Lahore, Pakistan - Muhammad Imran; Sohail Jahanzaib; Ather Ashraf (Arabian Journal of Geosciences, 2017)

Foliar application of selenium increases fertility and grain yield in bread wheat under contrasting water availability regimes - Iram Shahzadi; Muhammad Iqbal; Rizwan Rasheed; M. Arslan Ashraf; Shagufta Perveen; Makhdoom Hussain (Acta Physiologiae Plantarum, 2017)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Risk-based framework for optimizing residual chlorine in large water distribution systems - Muhammad Nadeem Sharif; Ashraf Farahat; Husnain Haider; Muhammad A. Al-Zahrani; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2017)

Temporal changes in trace elements in brown soil and soybean after long-term fertilization - Muhammad Imran Ashraf; Na Li; Xiaori Han; Jinfeng Yang; Yue Wang; Shumao Fan; Muhammad Irshad; Qaisar Mahmood (Arabian Journal of Geosciences, 2017)

Vulnerability assessment of an agro-stressed aquifer using a source-pathway-receptor model in GIS - Yawar Hussain; Sadia F. Ullah; Abdul Q. Aslam; Muhammad B. Hussain; Gulraiz Akhter; Hernan E. Martinez-Carvajal; Frédéric Satgé; Arshad Ashraf; Bilal Iqbal; Martin Cárdenas-Soto (Modeling Earth Systems and Environment, 2017)

Retraction Note to: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2017)

Retraction Note to: Release, deposition and elimination of radiocesium (137Cs) in the terrestrial environment - Muhammad Aqeel Ashraf; Ayesha Masood Khan; Mushtaq Ahmad; Shatirah Akib; Khaled S. Balkhair; Nor Kartini Abu Bakar (Environmental Geochemistry and Health, 2017)

Levels of Organotin Compounds in Selected Fish Species from the Arabian Gulf - Muhammad Waqar Ashraf; Abdus Salam; Atiq Mian (Bulletin of Environmental Contamination and Toxicology, 2017)

Does exogenous application of ascorbic acid modulate growth, photosynthetic pigments and oxidative defense in okra (Abelmoschus esculentus (L.) Moench) under lead stress? - Iqbal Hussain; Asif Siddique; Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Ibrahim; Muhammad Iqbal; Sobia Akbar; Muhammad Imran (Acta Physiologiae Plantarum, 2017)

Exogenous application of urea and a urease inhibitor improves drought stress tolerance in maize (Zea mays L.) - Wei Gou; Pufan Zheng; Li Tian; Mei Gao; Lixin Zhang; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Research, 2017)

Identification of a novel copper-activated and halide-tolerant laccase in Geobacillus thermopakistaniensis - Saadia Basheer; Naeem Rashid; Raza Ashraf; Muhammad Sohail Akram; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Pcal_0111, a highly thermostable bifunctional fructose-1,6-bisphosphate aldolase/phosphatase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Qamar Bashir; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Exogenous application of plant growth regulators (PGRs) induces chilling tolerance in short-duration hybrid maize - Muhammad Ahmed Waqas; Imran Khan; Muhammad Javaid Akhter; Mehmood Ali Noor; Umair Ashraf (Environmental Science and Pollution Research, 2017)

Salicylic Acid Induced Salinity Tolerance Through Manipulation of Ion Distribution Rather than Ion Accumulation - Hadi Pirasteh-Anosheh; Yahya Emam; Mohammad Javad Rousta; Muhammad Ashraf (Journal of Plant Growth Regulation, 2017)

Respiratory syncytial virus and influenza are the key viral pathogens in children <2 years hospitalized with bronchiolitis and pneumonia in Islamabad Pakistan - Uzma Bashir; Nadia Nisar; Yasir Arshad; Muhammad Masroor Alam; Asiya Ashraf; Hajra Sadia; Birjees Mazher Kazi; Syed Sohail Zahoor Zaidi (Archives of Virology, 2017)

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil - Mahnaz Roohi; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Muhammad Arslan Ashraf; Muhammad Atif Riaz; Ishaq A. Mian (Environmental Science and Pollution Research, 2017)

Persistent organic pollutants (POPs): a global issue, a global challenge - Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Oxidative stress responses in Wistar rats on subacute exposure to pharmaceutical wastewater - Ali Sharif; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmed Anjum; Muhammad Furqan Akhtar; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

Protein profiling analysis of Gossypium hirsutum (Malvales: Malvaceae) leaves infested by cotton whitefly Bemisia tabaci (Homoptera: Aleyrodidae) - Muhammad Ibrahim; Sumaira Yasmeen; Ghanva Zaman; Li Bin; Fahad Al-Qurainy; Habib-ur-Rehman Athar; Kausar Hussain Shah; Muhammad Khurshid; Muhammad Ashraf (Applied Entomology and Zoology, 2016)

Comparison of antioxidant enzyme activities and DNA damage in chickpea (Cicer arietinum L.) genotypes exposed to vanadium - Muhammad Imtiaz; Muhammad Adnan Mushtaq; Muhammad Shahid Rizwan; Muhammad Saleem Arif; Balal Yousaf; Muhammad Ashraf; Xiong Shuanglian; Muhammad Rizwan; Sajid Mehmood; Shuxin Tu (Environmental Science and Pollution Research, 2016)

Aluminum and Chromium Toxicity in Maize: Implications for Agronomic Attributes, Net Photosynthesis, Physio-Biochemical Oscillations, and Metal Accumulation in Different Plant Parts - Shakeel Ahmad Anjum; Umair Ashraf; Imran Khan; Mohsin Tanveer; Muhammad Farrukh Saleem; Longchang Wang (Water, Air, & Soil Pollution, 2016)

Syntheses, in vitro evaluation and molecular docking studies of 5-bromo-2-aryl benzimidazoles as α-glucosidase inhibitors - Tanzila Arshad; Khalid Mohammed Khan; Najma Rasool; Uzma Salar; Shafqat Hussain; Tehreem Tahir; Mohammed Ashraf; Abdul Wadood; Muhammad Riaz; Shahnaz Perveen; Muhammad Taha; Nor Hadiani Ismail (Medicinal Chemistry Research, 2016)

Influence of sub-lethal crude oil concentration on growth, water relations and photosynthetic capacity of maize (Zea mays L.) plants - Habib-ur-Rehman Athar; Sarah Ambreen; Muhammad Javed; Mehwish Hina; Sumaira Rasul; Zafar Ullah Zafar; Hamid Manzoor; Chukwuma C. Ogbaga; Muhammad Afzal; Fahad Al-Qurainy; Muhammad Ashraf (Environmental Science and Pollution Research, 2016)

New lipoxygenase and cholinesterase inhibitory sphingolipids from Carthamus oxyacantha - Muhammad Dilshad; Naheed Riaz; Muhammad Saleem; Nusrat Shafiq; Muhammad Ashraf; Tayaba Ismail; Hafiza Mehwish Rafiq; Abdul Jabbar (Natural Product Research, 2016)

Immobilization of Pb and Cu in polluted soil by superphosphate, multi-walled carbon nanotube, rice straw and its derived biochar - Muhammad Shahid Rizwan; Muhammad Imtiaz; Guoyong Huang; Muhammad Afzal Chhajro; Yonghong Liu; Qingling Fu; Jun Zhu; Muhammad Ashraf; Mohsin Zafar; Saqib Bashir; Hongqing Hu (Environmental Science and Pollution Research, 2016)

RETRACTED ARTICLE: Floristic and ethnoecological diversity in various habitats of a semi-arid area in the Chakwal district (Pakistan), with special emphasis on medicinal plants - Mehwish Jamil Noor; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Ismail Yusoff; Yatimah Alias; Muhammad Aqeel Ashraf (Plant Ecology, 2016)

Optimization of chlorination boosters in drinking water distribution network for Al-Khobar City in Saudi Arabia - Muhammad Nadeem Sharif; Ashraf Farahat; Muhammad A. Al-Zahrani; Nilufar Islam; Manuel J. Rodriguez; Rehan Sadiq (Arabian Journal of Geosciences, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Sediment yield assessment and identification of check dam sites for Rawal Dam catchment - Nida Samad; Muhammad Hamid Chauhdry; Muhammad Ashraf; Muhammad Saleem; Qudsia Hamid; Umair Babar; Hassan Tariq; Muhammad Shahid Farid (Arabian Journal of Geosciences, 2016)

Growth stage-based modulation in physiological and biochemical attributes of two genetically diverse wheat (Triticum aestivum L.) cultivars grown in salinized hydroponic culture - Muhammad Arslan Ashraf; Muhammad Ashraf (Environmental Science and Pollution Research, 2016)

Toxicity Appraisal of Untreated Dyeing Industry Wastewater Based on Chemical Characterization and Short Term Bioassays - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Ammara Saleem; Bushra Akhtar; Abdul Muqeet Khan; Imran Altaf (Bulletin of Environmental Contamination and Toxicology, 2016)

Morpho-anatomical and physiological adaptations to high altitude in some Aveneae grasses from Neelum Valley, Western Himalayan Kashmir - Khawaja Shafique Ahmad; Mansoor Hameed; Sana Fatima; Muhammad Ashraf; Farooq Ahmad; Mehwish Naseer; Noreen Akhtar (Acta Physiologiae Plantarum, 2016)

Foliar NK application mitigates drought effects in sunflower (Helianthus annuus L.) - Rai Altaf Hussain; Rashid Ahmad; Fahim Nawaz; Muhammad Yasin Ashraf; Ejaz Ahmad Waraich (Acta Physiologiae Plantarum, 2016)

Pharmaceutical wastewater being composite mixture of environmental pollutants may be associated with mutagenicity and genotoxicity - Ali Sharif; Muhammad Ashraf; Aftab Ahmed Anjum; Aqeel Javeed; Imran Altaf; Muhammad Furqan Akhtar; Mateen Abbas; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

River bank erosion and channel evolution in sand-bed braided reach of River Chenab: role of floods during different flow regimes - Muhammad Ashraf; Muhammad Tousif Bhatti; Abdul Sattar Shakir (Arabian Journal of Geosciences, 2016)

A review of the pollen analysis of South Asian honey to identify the bee floras of the region - Mehwish Jamil Noor; Mushtaq Ahmad; Muhammad Aqeel Ashraf; Muhammad Zafar; Shazia Sultana (Palynology, 2016)

Trehalose pretreatment induces drought tolerance in radish (Raphanus sativus L.) plants: some key physio-biochemical traits - Nudrat Aisha Akram; Muhammad Waseem; Rabia Ameen; Muhammad Ashraf (Acta Physiologiae Plantarum, 2016)

Prevalence and distribution of human Plasmodium infection in Federally Administrative Tribal Areas of Pakistan - Irfan Hussain; Naveeda Akhtar Qureshi; Muhammad Afzal; Nargis Shaheen; Abid Ali; Asma Ashraf (Acta Parasitologica, 2016)
About 3.6 million Pashtun and over 1.5 million immigrants from Afghanistan live in the federally administered tribal areas (FATA) on the border between Pakistan’s Khyber Pakhtunkhwa Province and southern Afghanistan. Although malaria cases are common in FATA, no detailed studies have yet been performed to reveal the actual status of malaria in the local population and epidemiological data are insufficient to elucidate the actual incidence. A malariometric survey of 691 patients of all ages and genders in seven agencies (districts) in FATA was carried out in 2013 using whole blood samples. Microscopically confirmed positive species were subjected to nested-PCR for the reconfirmation and detection of four species of

Use of statistical and GIS techniques to assess and predict concentrations of heavy metals in soils of Lahore City, Pakistan - Nayab Alam; Sajid Rashid Ahmad; Abdul Qadir; Muhammad Imran Ashraf; Calvin Lakhan; V. Chris Lakhan (Environmental Monitoring and Assessment, 2015)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Exogenous application of trehalose alters growth, physiology and nutrient composition in radish (Raphanus sativus L.) plants under water-deficit conditions - Nudrat Aisha Akram; Sidra Noreen; Tabassum Noreen; Muhammad Ashraf (Brazilian Journal of Botany, 2015)

Heterogeneous expansion of end-moraine dammed lakes in the Hindukush-Karakoram-Himalaya ranges of Pakistan during 2001–2013 - Arshad Ashraf; Rozina Naz; Muhammad Bilal Iqbal (Journal of Mountain Science, 2015)

Isolation of buffalo poxvirus from clinical case and variations in the genetics of the B5R gene over fifty passages - Mohsan Ullah Goraya; Zafar ul Ahsan Qureshi; Muhammad Abbas; Muhammad Ashraf; Muhammad Munir (Virus Genes, 2015)

Larvicidal activity of endophytic fungal extract of Cochliobolus spicifer (Pleosporales: Pleosporaceae) on Aedes caspius and Culex pipiens (Diptera: Culicidae) - Nael Abutaha; Ashraf M. A. Mashaly; Fahd A. Al-Mekhlafi; Muhammed Farooq; Mohammed Al-shami; Muhammad A. Wadaan (Applied Entomology and Zoology, 2015)

Synthesis of phenyl thiazole hydrazones and their activity against glycation of proteins - Khalid Mohammed Khan; Muhammad Irfan; Mahwish Ashraf; Muhammad Taha; Syed Muhammad Saad; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Hydrological response to environment change in Himalayan watersheds: Assessment from integrated modeling approach - Zulfiqar Ahmad; Arshad Ashraf; Muhammad Zaheer; Humaira Bashir (Journal of Mountain Science, 2015)

RETRACTED ARTICLE: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2015)

Exogenous application of silicon at the boot stage decreases accumulation of cadmium in wheat (Triticum aestivum L.) grains - Iqbal Hussain; Muhammad Arslan Ashraf; Rizwan Rasheed; Anum Asghar; Muhammad Asim Sajid; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Growth, V uptake, and antioxidant enzymes responses of chickpea (Cicer arietinum L.) genotypes under vanadium stress - Muhammad Imtiaz; Shuxin Tu; Zhijian Xie; Dan Han; Muhammad Ashraf; Muhammad Shahid Rizwan (Plant and Soil, 2015)

Spatio-temporal characteristics of precipitation and drought in Balochistan Province, Pakistan - Muhammad Ashraf; Jayant K. Routray (Natural Hazards, 2015)

Triarylimidazoles-synthesis of 3-(4,5-diaryl-1H-imidazol-2-yl)-2-phenyl-1H-indole derivatives as potent α-glucosidase inhibitors - Sadia Naureen; Shazia Noreen; Areesha Nazeer; Muhammad Ashraf; Umber Alam; Munawar Ali Munawar; Misbahul Ain Khan (Medicinal Chemistry Research, 2015)

Evaluating pasture and soil allowance of manganese for Kajli rams grazing in semi-arid environment - Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Ashraf; Syed Ali Hassan Naqvi; Alireza Seidavi; Nudrat Aisha Akram; Vito Laudadio; Vincenzo Tufarelli (Tropical Animal Health and Production, 2015)

Physiological and biochemical markers to optimize sugar mill wastewater for irrigation in maize (Zea mays L.) crop - Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain; Abida Parveen; Rizwan Alam; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Application of GIS for the identification and demarcation of selective heavy metal concentrations in the urban groundwater - Sobia Ashraf; Farhat Abbas; Muhammad Ibrahim; Umer Rashid; Shoaib Khalid; Hammad Raza Ahmad; Khalid Rehman Hakeem; Tahir Majeed (Journal of Geographical Sciences, 2015)

RETRACTED ARTICLE: Release, deposition and elimination of radiocesium (137Cs) in the terrestrial environment - Muhammad Aqeel Ashraf; Ayesha Masood Khan; Mushtaq Ahmad; Shatirah Akib; Khaled S. Balkhair; Nor Kartini Abu Bakar (Environmental Geochemistry and Health, 2014)

Exogenous proline and glycinebetaine mitigate cadmium stress in two genetically different spring wheat (Triticum aestivum L.) cultivars - Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain; Muhammad Zulqurnain Haider; Uzma Kanwal; Muhammad Iqbal (Brazilian Journal of Botany, 2014)

Time-course changes in growth and biochemical indices of mung bean [Vigna radiata (L.) Wilczek] genotypes under salinity - Syed Hammad Raza; Muhammad Bilal Ahmad; Muhammad Arslan Ashraf; Fahad Shafiq (Brazilian Journal of Botany, 2014)

Morpho-anatomical and physiological attributes for salt tolerance in sewan grass (Lasiurus scindicus Henr.) from Cholistan Desert, Pakistan - Nargis Naz; Tanzila Rafique; Mansoor Hameed; Muhammad Ashraf; Riffat Batool; Sana Fatima (Acta Physiologiae Plantarum, 2014)

Determinants of farmers’ choice of coping and adaptation measures to the drought hazard in northwest Balochistan, Pakistan - Muhammad Ashraf; Jayant K. Routray; Muhammad Saeed (Natural Hazards, 2014)

Physiological adaptative characteristics of Imperata cylindrica for salinity tolerance - Mansoor Hameed; Muhammad Ashraf; Nargis Naz; Tahira Nawaz; Riffat Batool; Sana Fatima; Farooq Ahmad (Biologia, 2014)

Cesium-137: Radio-Chemistry, Fate, and Transport, Remediation, and Future Concerns - Muhammad Aqeel Ashraf; Shatirah Akib; Mohd. Jamil Maah; Ismail Yusoff; Khaled S. Balkhair (Critical Reviews in Environmental Science and Technology, 2014)

A review of the stabilization of tropical lowland peats - Mohamad Tarmizi Mohamad Zulkifley; Tham Fatt Ng; John Kuna Raj; Roslan Hashim; Ahmad Farid Abu Bakar; S. Paramanthan; Muhammad Aqeel Ashraf (Bulletin of Engineering Geology and the Environment, 2014)

Synergistic effects of drought and ascorbic acid on growth, mineral nutrients and oxidative defense system in canola (Brassica napus L.) plants - Sidra Shafiq; Nudrat Aisha Akram; Muhammad Ashraf; Amara Arshad (Acta Physiologiae Plantarum, 2014)

Erratum to: Current and future therapies for hepatitis C virus infection: from viral proteins to host targets - Muhammad Imran; Sobia Manzoor; Nasir Mahmood Khattak; Madiha Khalid; Qazi Laeeque Ahmed; Fahed Parvaiz; Muqddas Tariq; Javed Ashraf; Waseem Ashraf; Sikandar Azam; Muhammad Ashraf (Archives of Virology, 2014)

Current and future therapies for hepatitis C virus infection: from viral proteins to host targets - Muhammad Imran; Sobia Manzoor; Nasir Mahmood Khattak; Madiha Khalid; Qazi Laeeque Ahmed; Fahed Parvaiz; Muqddas Tariq; Javed Ashraf; Waseem Ashraf; Sikandar Azam; Muhammad Ashraf (Archives of Virology, 2014)

Monitoring impacts of air pollution: PIXE analysis and histopathological modalities in evaluating relative risks of elemental contamination - Sohail Ejaz; Gerry Amor Camer; Khaleeq Anwar; Muhammad Ashraf (Ecotoxicology, 2014)

MRI and neuropathological validations of the involvement of air pollutants in cortical selective neuronal loss - Sohail Ejaz; Khaleeq Anwar; Muhammad Ashraf (Environmental Science and Pollution Research, 2014)

Co-inoculation integrated with P-enriched compost improved nodulation and growth of Chickpea (Cicer arietinum L.) under irrigated and rainfed farming systems - Sher Muhammad Shahzad; Azeem Khalid; Muhammad Saleem Arif; Muhammad Riaz; Muhammad Ashraf; Zafar Iqbal; Tahira Yasmeen (Biology and Fertility of Soils, 2014)

Definitions and engineering classifications of tropical lowland peats - Mohamad Tarmizi Mohamad Zulkifley; Tham Fatt Ng; John Kuna Raj; Roslan Hashim; Azman Ghani; Mustaffa Kamal Shuib; Muhammad Aqeel Ashraf (Bulletin of Engineering Geology and the Environment, 2013)

Regulation in Plant Stress Tolerance by a Potential Plant Growth Regulator, 5-Aminolevulinic Acid - Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2013)

Cytotoxic, phytotoxic, and mutagenic appraisal to ascertain toxicological potential of particulate matter emitted from automobiles - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Imran Altaf; Aftab Ahmad Anjum (Environmental Science and Pollution Research, 2013)

Study of contaminant transport at an open-tipping waste disposal site - Muhammad Aqeel Ashraf; Ismail Yusoff; Mohamad Yusof; Yatimah Alias (Environmental Science and Pollution Research, 2013)

Monitoring trace elements generated by automobiles: air pollutants with possible health impacts - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2013)

Prospects of raising Sahiwal cow calves for veal production under tropical environment - Shaukat Ali Bhatti; Kamran Nazir; Muhammad Jamil Basra; Muhammad Sajjad Khan; Muhammad Sarwar; Muhammad Ashraf Iqbal Mughal (Tropical Animal Health and Production, 2013)

Flow Karyotyping of Wheat Addition Line “T240” with a Haynaldia villosa 6VS Telosome - Dong-wei Guo; Dong-hong Min; Zhao-shi Xu; Ming Chen; Lian-cheng Li; Muhammad Ashraf; Abdul Ghafoor; You-zhi Ma (Plant Molecular Biology Reporter, 2013)

Alleviation of salinity-induced perturbations in ionic and hormonal concentrations in spring wheat through seed preconditioning in synthetic auxins - Muhammad Iqbal; Muhammad Ashraf (Acta Physiologiae Plantarum, 2013)

Antioxidant and lipoxygenase inhibiting new iridoid glucosides from Caryopteris odorata - Tayyaba Shahzadi; Muhammad Athar Abbasi; Aziz Ur-Rehman; Tauheeda Riaz; Khalid Mohammed Khan; Muhammad Ashraf; Iftikhar Afzal; Muhammad Nadeem Akhtar; Muhammad Ajaib (Natural Product Research, 2013)

Synthesis, characterization and in vitro hydrolysis studies of ester and amide prodrugs of dexibuprofen - Zaman Ashraf; Muhammad Imran; Shahid Amin (Medicinal Chemistry Research, 2012)

Stem cell-based delivery of Hypoxamir-210 to the infarcted heart: implications on stem cell survival and preservation of infarcted heart function - Ha Won Kim; Shujia Jiang; Muhammad Ashraf; Khawaja Husnain Haider (Journal of Molecular Medicine, 2012)

The anti-arthritic and anti-oxidative effect of NBD (6-nitro-1,3-benzodioxane) in adjuvant-induced arthritis (AIA) in rats - Syed Uzair Ali Shah; Nadeem Ashraf; Zahid H. Soomro; Muhammad Raza Shah; Nurul Kabir; Shabana Usman Simjee (Inflammation Research, 2012)

Screening sugarcane (Saccharum sp.) genotypes for salt tolerance using multivariate cluster analysis - Suriyan Cha-um; Sasiwimon Chuencharoen; Chareerat Mongkolsiriwatana; Muhammad Ashraf; Chalermpol Kirdmanee (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Leaf structural modifications for drought tolerance in some differentially adapted ecotypes of blue panic (Panicum antidotale Retz.) - Mansoor Hameed; Saima Batool; Nargis Naz; Tahira Nawaz; Muhammad Ashraf (Acta Physiologiae Plantarum, 2012)

Non-hypoxic stabilization of HIF-Iα during coordinated interaction between Akt and angiopoietin-1 enhances endothelial commitment of bone marrow stem cells - Vien Khach Lai; Muhammad Rizwan Afzal; Muhammad Ashraf; Shujia Jiang; Husnain Kh Haider (Journal of Molecular Medicine, 2012)

High-density growth and crude protein productivity of a thermotolerant Chlorella vulgaris: production kinetics and thermodynamics - Shahid Mahboob; Abdul Rauf; Muhammed Ashraf; Tayyaba Sultana; Salma Sultana; Farhat Jabeen; Muhammad Ibrahim Rajoka; H. F. Alkahem Al-Balawi; Khalid A. Al-Ghanim (Aquaculture International, 2012)

Polycyclic Aromatic Hydrocarbons (PAHs) in Vegetables and Fruits Produced in Saudi Arabia - Muhammad Waqar Ashraf; A. Salam (Bulletin of Environmental Contamination and Toxicology, 2012)

Characterization of tannery effluent wastewater by proton-induced X-ray emission (PIXE) analysis to investigate their role in water pollution - Lubna Shakir; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2012)

Lead (Pb)-Induced Regulation of Growth, Photosynthesis, and Mineral Nutrition in Maize (Zea mays L.) Plants at Early Growth Stages - Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Qaisra Tabassam; Mumtaz Hussain; Humaira Firdous (Biological Trace Element Research, 2011)

Toxic Effect of Nickel (Ni) on Growth and Metabolism in Germinating Seeds of Sunflower (Helianthus annuus L.) - Muhammad Yasin Ashraf; Rumana Sadiq; Mumtaz Hussain; Muhammad Ashraf; M. Sajid Aqeel Ahmad (Biological Trace Element Research, 2011)

Evaluation of Molybdenum Status of Cows: The Use of Blood Plasma and Milk as Indicators Under Semi-Arid Environmental Conditions in Punjab, Pakistan - Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Ashraf; Nasra Raza (Biological Trace Element Research, 2011)

Assessment of Molybdenum Status in Soil and Forage for Ruminant Production Under Semiarid Environmental Conditions in Sargodha, Pakistan - Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Ashraf; Nasra Raza; Muhammad Sher (Biological Trace Element Research, 2011)

A Study on the Transfer of Iron in Soil–Plant–Animal Continuum Under Semi-arid Environmental Conditions in Sargodha, Pakistan - Zafar Iqbal Khan; Muhammad Ashraf; Muhammad Khalid Mukhtar; Nasra Raza; Kafeel Ahmad; Nudrat Aisha Akram (Biological Trace Element Research, 2011)

A Study on the Transfer of Cadmium from Soil to Pasture Under Semi-Arid Conditions in Sargodha, Pakistan - Zafar Iqbal Khan; Muhammad Ashraf; Kafeel Ahmad; Nudrat Aisha Akram (Biological Trace Element Research, 2011)

Anatomical and physiological characteristics relating to ionic relations in some salt tolerant grasses from the Salt Range, Pakistan - Mansoor Hameed; Muhammad Ashraf; Nargis Naz (Acta Physiologiae Plantarum, 2011)

Salt-induced modulation in growth, photosynthetic capacity, proline content and ion accumulation in sunflower (Helianthus annuus L.) - Muhammad Shahbaz; Muhammad Ashraf; Nudrat Aisha Akram; Asma Hanif; Shumaila Hameed; Sundus Joham; Rehana Rehman (Acta Physiologiae Plantarum, 2011)

Studies on the Transfer of Copper from Soil to Pastures at Different Sampling Periods: A Case Study of a Semiarid Region (Sargodha) in Pakistan - Zafar Iqbal Khan; Muhammad Ashraf; F. Al-Qurainy; Kafeel Ahmad; Sumaira Gondal; Asia Fardous (Biological Trace Element Research, 2011)

Evaluation of Pakistan wheat germplasms for stripe rust resistance using molecular markers - Tabassum Sobia; Ashraf Muhammad; XianMing Chen (Science China Life Sciences, 2010)

Anatomical adaptations to salinity in cogon grass [Imperata cylindrica (L.) Raeuschel] from the Salt Range, Pakistan - Mansoor Hameed; Muhammad Ashraf; Nargis Naz (Plant and Soil, 2009)

Methionine+cystine requirement of broiler chickens fed low-density diets under tropical conditions - Usama Aftab; Muhammad Ashraf (Tropical Animal Health and Production, 2009)

Recent developments in biodegradation of industrial pollutants by white rot fungi and their enzyme system - Muhammad Asgher; Haq Nawaz Bhatti; Muhammad Ashraf; Raymond L. Legge (Biodegradation, 2008)

The detection of antibody against peste des petits ruminants virus in Sheep, Goats, Cattle and Buffaloes - Haider Ali Khan; Muhammad Siddique; Sajjad-ur-Rahman; Muhammad Abubakar; Muhammad Ashraf (Tropical Animal Health and Production, 2008)

Genetic variability in bread wheat (Triticum aestivum L.) of Pakistan based on polymorphism for high molecular weight glutenin subunits - Tayyaba Sultana; Abdul Ghafoor; Muhammad Ashraf (Genetic Resources and Crop Evolution, 2007)

Diagnosis of heavy metal contamination in agro-ecology of Gujranwala, Pakistan using cattle egret (Bubulcus Ibis) as bioindicator - Nazish Bostan; Muhammad Ashraf; Abdul S. Mumtaz; Iftikhar Ahmad (Ecotoxicology, 2007)

Morphological Variability of Prosopis cineraria (L.) Druce, from the Cholistan Desert, Pakistan - Mohammad Arshad; Muhammad Ashraf; Niala Arif (Genetic Resources and Crop Evolution, 2006)

Inoculating wheat seedlings with exopolysaccharide-producing bacteria restricts sodium uptake and stimulates plant growth under salt stress - Muhammad Ashraf; Shahida Hasnain; Odile Berge; Tariq Mahmood (Biology and Fertility of Soils, 2004)

Fate and Interaction with Soil N of Fertilizer 5N Applied to Wheat at Different Growth Stages - Muhammad Ashraf; Farooq-e-Azam (Cereal Research Communications, 1998)

Fluctuations in Fe, Cu, Zn, Br, As, Se, and Rb concentrations in C57L/J mice bearing BW7756 murine hepatoma using radioisotope-induced X-ray fluorescence - Muhammad Ashraf Tariq; Ivor L. Preiss (Biological Trace Element Research, 1994)